Effects of surgical implantation of electronic tags in fishes: a review and meta-analysis - Mitchell B. Shorgan; Graham D. Raby; Amber L. Fedus; Bradley E. Howell; Laura S. E. Haniford; Leah C. Howitt; Natalie V. Klinard; Jordan K. Matley; Jacob W. Brownscombe; Steven J. Cooke; Aaron T. Fisk (Reviews in Fish Biology and Fisheries, 2026)

Susceptibility of field populations of Ostrinia nubilalis from Minnesota and Wisconsin to Cry1Ab, Cry1Fa, and Cry1A.105 Bt proteins - Tatum Dwyer; Graham P. Head; Krista L. Hamilton; Caroline Placidi de Bortoli; Wilfrid Calvin; Juan Luis Jurat-Fuentes; Fei Yang (Crop Protection, 2026)

Fifty years of riverine harmful algal bloom modeling: A global synthesis of approaches, challenges, and opportunities - Jennifer C. Murphy; Rebecca M. Gorney; Lisa V. Lucas; Jacob A. Zwart; Jennfier L. Graham (Water Research, 2026)

Early life exposure to an episode of extreme air pollution and lung function later in childhood: the Hazelwood early life follow-up (ELF) study - Evelien A.M. Graven; Caroline Gao; Myriam Ziou; Bibian D.M. Wijs; Marita Dalton; Graham L. Hall; Michael J. Abramson; Graeme R. Zosky; Shyamali C. Dharmage; Fay Johnston; Lieke E.J.M. Scheepers (Environmental Research, 2026)

Exploring the effect of dissolved oxygen concentration on the heterogeneous oxidation of veratryl alcohol over a Pd/C catalyst - Sophie Graham; Faiz M. Mahdi; Thomas W. Chamberlain; Richard A. Bourne; Leon van de Water; Robert W. Gallen; Frans L. Muller (Chemical Engineering Journal, 2026)

Oceanographic parameters associated with spatial occurrence of cephalopods in standardized demersal fishing trawls in the NE Atlantic - Daniel Oesterwind; Anne Marie Power; Esther Abad; Gregoire Certain; Nikolaos Fotiadis; Alexey Golikov; Ángel F. González; Vladimir Laptikhovsky; Silvia S. Monteiro; Carlos Montero-Castaño; Ana Moreno; Hassan Moustahfid; et al. (Marine Biology, 2026)
In this work, the environmental occurrence ranges of different European cephalopod species are described for the whole NE Atlantic shelf including the greater North Sea and Baltic Sea. This is done based on the environmental parameters collected in-situ during surveys that caught commercially important cephalopod species (1990–2022). Results are supplemented and compared with information available in the published literature and are discussed in relation to available habitat across the range, survey design, etc., and, in particular, which species are most likely to be affected by climate change. Our analyses illustrate that Loligo forbesii occupies a broader depth range than Loligo vulgaris and Alloteuthis spp. Because L. forbesii occurs further offshore and at greater depths, this species is likely more resilient to warming than the other loliginids in our study. Octopus vulgaris is documented in areas close to the coast with a more southerly distribution, whereas Eledone cirrhosa occurs further north and further away from the coast. Eledone cirrhosa occurs at lower temperatures and has a much broader depth range, which may provide resilience against warming. By contrast, both ommastrephid squid species ( Illex coindetii and Todaropsis eblanae ) showed a very similar tolerance to the three environmental variables (salinity, temperature, depth). This information should contribute to future species distribution modelling by allowing validation of realistic results against each species’ range, habitat requirements, and environmental ranges, while appreciating the data limitations caused by the timing and gear used in the survey cruises that supply occurrence and density data.

Trends in awareness and uptake of genetic testing among the United States population, 2011–2022 - Ariana Naaseh; Mengyao Shi; Steven Tohmasi; Erin L. Linnenbringer; Julie A. Margenthaler; Graham A. Colditz; Yin Cao (Journal of Community Genetics, 2026)
While genetic testing (GT) has become more available over the past decade, it is unclear whether public awareness and use have increased proportionally. We aimed to evaluate national trends in GT awareness and usage. We performed a cross-sectional analysis of nationally representative data from the National Cancer Institute’s Health Information National Trends Survey (HINTS). We analyzed survey responses from HINTS 4 Cycle 1–4 (2011–2014), 5 Cycle 1 and 4 (2017, 2020), and 6 (2022). Primary outcomes were overall genetic testing awareness and uptake. Secondary analyses evaluated awareness and uptake of health-related genetic testing (e.g. disease risk, cancer, and carrier testing) among survey cycles in which specific testing modalities were available. Linear regression assessed crude trends and multivariable logistic regression estimated odds ratios (OR). Among 22,256 respondents, overall awareness of GT increased from 36.6% in 2011 to 81.7% in 2022 (trend p < .001). Awareness was lower among individuals who were older (e.g., ref: age 18–34 , age 75+: OR 0.53 , 95% confidence interval [CI]: 0.43–0.64 ), male ( ref: female , OR 0.85 , CI: 0.77–0.95 ), non-Hispanic Black ( ref: non-Hispanic White , OR 0.63 , CI: 0.54–0.74 ), non-Hispanic Asian ( ref: non-Hispanic White , OR 0.38 , CI: 0.29–0.48 ), Hispanic ( ref: non-Hispanic White , OR 0.60 , CI: 0.52–0.69 ), with less than a college education (e.g., ref: some college , less than high school: OR 0.60 , CI: 0.47–0.77 ), and with annual household income <$75,000 (e.g., ref: >$75 , 000 , <$20 , 000: OR 0.49 , CI: 0.42–0.59 ). GT uptake increased from 21.4% in 2020 to 35.6% in 2022 (trend p < .001). GT uptake was lower among individuals who were non-Hispanic Asian ( ref: non-Hispanic White , OR 0.60 , CI: 0.38–0.96 ) and had household incomes <$35,000 (e.g., ref: >$75 , 000 , <$20 , 000: OR 0.68 , CI: 0.49–0.94 ), but higher among those with a personal history of cancer ( ref: no cancer history , OR 1.44 , CI: 1.07–1.92 ). Although GT awareness has grown, there are notable gaps across sociodemographic groups. Further study should better characterize factors influencing health-related GT uptake patterns.

Comparing loss-on-ignition, acid decarbonation and combustion elemental analysis for measuring organic carbon concentrations – recommendations for best practice - Robert B. Sparkes; Stuart A. Rae; Lucy McMahon; Hannah L. Mossman; David McKendry; Clare E. Dean; Graham Tinsley; Frances Fowden; Connor J. Grisdale; Hafiza Begum; Holly Hope; Charlotte McEnhill; et al. (Organic Geochemistry, 2026)

Effect of dissolved versus total zinc levels on bacterial zinc-dependent meropenem co-resistance in River Tyne sediments - Catherine L. Hands; Sonia Gupta; Anke Neumann; Charles W. Knapp; S.Z. Ahammad; Jason Snape; David W. Graham (Environmental Pollution, 2026)

Gibbsite solubility and aluminum speciation in alkaline nuclear waste containing nitrate, nitrite, and phosphate - Trent R. Graham; Ashley R. Kennedy; Winnie Liu; Daria V. Boglaienko; Robert G. Felsted; Jacob G. Morton; Micah P. Prange; Mark E. Bowden; Teresa L. Lemmon; Marie S. Swita; Hsiu-Wen Wang; Michael D. Britton; et al. (Chemical Engineering Journal, 2026)

Quantitative Mineral Resource Assessment of Lithium Pegmatite Deposits in the Southern Appalachian Orogen - Joshua M. Rosera; Kelsey E. Crocker; Laura S. Pianowski; Jacob T. Murchek; Ashton M. Wiens; Margaret M. Sanders; Lucas L. Evart; Jacob DeAngelo; Graham W. Lederer; Joshua A. Coyan (Natural Resources Research, 2026)
The first quantitative mineral resource assessment for undiscovered lithium pegmatite deposits in the southern Appalachian region of the United States was conducted. Permissive tracts for lithium pegmatite deposits were delineated by integrating lithological, tectonic, geochemical, geophysical and mineral occurrence data. Lithium pegmatite prospectivity of the tracts was ranked with simplified mappable criteria, including proximity to Paleozoic felsic intrusions and major lithotectonic structures, stream sediment geochemical anomalies, and pegmatite occurrence data. The geospatial data and permissive tracts were used to estimate the number of undiscovered lithium pegmatite deposits. These estimates were integrated into probabilistic simulations along with a new global lithium pegmatite grade and tonnage dataset to quantify potential contained undiscovered lithium resources. An economic filter was applied to convert the probabilistic estimates of contained lithium into recoverable material. The identified lithium pegmatite resources for the Carolina Lithium and Kings Mountain deposits, North Carolina, contain 1589 thousand tons (kt) of Li 2 O. The median contained undiscovered resource for the southern Appalachian orogen was estimated to be 2240 kt Li 2 O. At 90% confidence, the region contains at least 130 kt Li 2 O, and 10,700 kt at 10% confidence. After applying economic filters, the median recoverable contained resource was 1430 kt Li 2 O, corresponding to approximately 201 years of current lithium imports for consumption in the United States. North and South Carolina are likely to contain most of these resources. Coarse data resolution and intra-state variations in the geological data contribute to uncertainty of undiscovered lithium pegmatite resources. Continued efforts to harmonize disparate geospatial datasets with updated or new information can improve the accuracy and precision of estimated undiscovered lithium pegmatite resources in the study area and at broader scales.

An ecosystem service value chain for sustainable environmental management - Anthea Coggan; Jeremy De Valck; Diane Jarvis; Victoria Graham; Petina L. Pert; Cindy Huchery; Michelle Dyer (Ambio, 2026)

Variable feeding strategies of the whelk Dicathais orbita (Gmelin, 1791) in the south-eastern Indian Ocean - Fred E. Wells; Graham L. Cobby; Marthe M. Gagnon (Molluscan Research, 2026)

Catalyzing community-led conservation governance through integrated conservation and development in coastal Mozambique - Rafaella Lobo; Althea Skinner; Matthew Clark; Milton Xavier; Graham Epstein; Mark Andrachuk; Dalila Sequeira; Matheus De Nardo; Brendan Fisher; Shauna L. Mahajan (Marine Policy, 2026)

Novel rock luminescence dating of snow petrel stomach-oil deposits from East Antarctica - Rachel K. Smedley; David Small; Erin L. McClymont; Michael J. Bentley; Dominic A. Hodgson; Alice Graham (Quaternary Geochronology, 2026)

Neoproterozoic-Early Ordovician sedimentation on the eastern margin of Laurentia: A detrital zircon provenance perspective on the Dalradian Supergroup, Scotland and Ireland - Elias J. Rugen; Rob Strachan; David Chew; Jessica Molesworth; James Lee; Pieter Vermeesch; Dirk Frei; Andrew Morton; Zoe Whittaker; Craig Storey; Marina Seraine; Christopher L. Kirkland; et al. (Earth-Science Reviews, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Strategic deep tillage of deep sand soils impacts the sorption and biological availability of trifluralin - Tom J. Edwards; Stephen L. Davies; Ron J. Yates; Michael T. Rose; Benedict Arthur; John G. Howieson; Graham O’Hara; Emma J. Steel; David JM Hall (Soil and Tillage Research, 2026)

Mechanisms of Strong Hearts, Healthy Communities-2.0 Effects on Weight: A Mediation Analysis - Chad D. Rethorst; Margaret Demment; Meredith L. Graham; Seungyeon Ha; Alexandra L. MacMillan Uribe; Brian K. Lo; Jacob Szeszulski; Phrashiah Githinji; David Strogatz; Sara C. Folta; Miriam E. Nelson; Rebecca A. Seguin-Fowler (Journal of Nutrition Education and Behavior, 2026)

Enhanced enzymatic hydrolysis of pretreated polyester textile at high solids loading through fusion with a carbohydrate binding module - Rosie Graham; Brooke H. Wain; Robbie A. Clark; Victoria L. Bemmer; Gustavo P. Borin; Luisana Avilan; Elaine M. Rudge; Ciaran W. Lahive; Michael P. Shaver; Andrew R. Pickford (Bioresource Technology, 2026)

A 2026 horizon scan for biodiversity conservation in South Africa - Colleen L. Seymour; Krystal A. Tolley; Tsungai Zengeya; Dian Spear; Jeran A. Cloete; Anisha Dayaram; Jessica M. da Silva; Graham J. Alexander; Kate Handley; Grant S. Joseph; Lavhelesani D. Simba; Kate Snaddon; et al. (Ambio, 2026)
Horizon scans identify potential changes, enabling proactive rather than reactive conservation strategies. Here, in a follow up to the 2020 horizon scan, 14 biodiversity professionals from different sectors identify ten emerging issues potentially relevant to biodiversity conservation in South Africa over the next 5–10 years. The issues identified highlight three critical needs: adaptive governance systems, cross-sectoral collaboration capacity, and vigilance around new technologies that may simultaneously offer solutions and create new environmental pressures. We plotted these issues along axes of social agreement and scientific certainty, to ascertain whether issues might be "simple" (amenable to solutions from science alone), "complicated" (socially agreed upon but technically complicated), "complex" (scientifically challenging and condisderable levels of social disagreement) or "chaotic" (high social disagreement and highly scientifically challenging). Only one issue was likely to be addressed with improved science alone, but the remainder were all “complex”, requiring social, economic and political engagement.

Using herd frailty estimates from survival models in a mortality-based syndromic surveillance system - Jaden M. Carlson; T. Brendan Murphy; Luke O’Grady; Jonas Brock; Maria P. Guelbenzu-Gonzalo; David A. Graham; Guy McGrath; Jamie A. Tratalos; Rafael de Andrade Moral; Niamh Mimnagh; Niamh L. Field; John F. Mee; et al. (Preventive Veterinary Medicine, 2026)

Small methane emissions from pasture observed with eddy covariance and flux-gradient methods: are they real or artefacts? - Johannes Laubach; Aaron M. Wall; John E. Hunt; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; Louis A. Schipper (Agricultural and Forest Meteorology, 2026)

Mangrove species of Southeast Asian origin dispersed into coastal forests of the western Amazon (Early Miocene, Brazil) - Carina Hoorn; Giovanni Bogotá-Ángel; Angelo Plata-Torres; Diana Ochoa; Limi Mao; Hanna van den Hil; Jelle J.J. Kraak; Brenda L. Orosco-Arango; Shweta Basnett; Huasheng Huang; Carlos Jaramillo; Shirley A. Graham; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Associations Between Diet Quality and Psychosocial and Environmental Factors in Rural Adults - Rebecca A. Seguin-Fowler; Karla L. Hanson; Galen D. Eldridge; Grace A. Marshall; Meredith L. Graham; Miriam E. Nelson; Deyaun L. Villarreal; Johanna Y. Andrews Trevino; Jay E. Maddock (Journal of Nutrition Education and Behavior, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The 4th global coral bleaching event: ushering in an era of near-annual bleaching - Blake L. Spady; William J. Skirving; Jacqueline L. De La Cour; Erick F. Geiger; Gang Liu; Ove Hoegh-Guldberg; Andrew Norrie; Scott F. Heron; Morgan W. Pomeroy; Graham Kolodziej; Kristen T. Brown; Derek P. Manzello (Coral Reefs, 2026)
Increasingly frequent marine heatwaves have escalated the prevalence and extent of mass coral bleaching events. Global-scale coral bleaching events (GCBEs) can unfold when marine heatwaves impact reefs across all tropical ocean basins within a common period. Here, we define an objective, quantifiable index to compare periods of satellite-derived coral heat stress accumulation globally from 1985 to 2025 and examine their relationship to confirmed GCBEs. We uncover an uninterrupted and ongoing period of global coral heat stress from 2018 to 2025, affecting an unprecedented 87% of reef areas globally. The average intensity has also been record-setting, with the median global heat stress accumulation on reef areas nearly 50% greater than the previous GCBE record. This has largely been driven by general ocean warming, as recent baseline global surface ocean temperatures (2019–2023) are comparable to extreme anomalous conditions observed ~ 25 years ago. The development of a strong El Niño event in 2023, superimposed upon the already anomalously warm ocean, culminated in the 4th GCBE, the most extensive and intensive on record. Qualitative observations of coral bleaching have been reported from 84 countries spanning all coral-containing ocean basins. An analysis of the extent and magnitude of heat stress suggests that bleaching may have impacted 98 of the 102 countries with coral reefs. GCBE4 (2023–present) marks a period of heat stress that is unprecedented by every investigated metric. However, global-scale coral bleaching-level heat stress has persisted for almost the entirety of the last decade, bringing many reef areas into an era of near-annual bleaching.

DNA methylation-based surrogate markers of C-reactive protein and their associations with health-related traits - Danmeng Lily Li; Allison M. Hodge; Joanne Ryan; Melissa C. Southey; Graham G. Giles; Roger L. Milne; Pierre-Antoine Dugué (GeroScience, 2026)
Several methylation-based surrogate markers of C-reactive protein ( mCRP ) have been proposed and used to assess the risk of age-related phenotypes and construct novel ageing markers. We aimed to (i) assess the variance in plasma CRP explained by several mCRP markers; (ii) compare their associations with three health-related traits: mortality, body mass index (BMI), and PCGrimAge ; and (iii) assess the stability of CRP and mCRP over a decade. Blood samples were collected from 947 participants in the Melbourne Collaborative Cohort Study at baseline (1990–1994) and wave 2 (2003–2007). High-sensitivity CRP was measured in plasma samples. Five mCRP markers were calculated: mCRP-Ligthart , mCRP-Wielscher , mCRP-EpiScore , mCRP-GrimAge2 , and mCRP-Hillary . Intraclass correlation coefficients (ICCs) were calculated to assess the stability of CRP/ mCRP between baseline and wave 2. Associations of wave 2 CRP/ mCRP with mortality ( N deaths = 319) were assessed using Cox models and linear regression for BMI and age-adjusted PCGrimAge . mCRP explained 6.0% ( mCRP-Wielscher ) to 16.8% ( mCRP-GrimAge2 ) of the variance in plasma CRP. The ICCs for CRP and mCRP markers were similar, ranging from 0.44 ( mCRP-GrimAge2 ) to 0.63 ( mCRP-Wielscher ). Compared with CRP, mCRP had stronger associations with PCGrimAge , whereas for mortality and BMI, the associations were similar or weaker for mCRP . Associations between mCRP and mortality were greatly attenuated after adjusting for PCGrimAge but less so after adjusting for CRP. The association of CRP with mortality remained strong after adjusting for mCRP . Our study validated mCRP markers and clarified the role of CRP and mCRP in ageing, which may inform the use and development of ageing biomarkers.

Cumulative environmental exposures adversely impact social behaviour and are associated with dysregulation of genes and proteins involved in epigenetic, ribosomal, and immune regulation in male mice - Morgan C. Bucknor; Brooke A. Keating; Velda X. Han; Brian S. Gloss; Pinki Dey; Nader Aryamanesh; Lee L. Marshall; Mark E. Graham; Ruwani Dissanayake; Xianzhong Lau; Shrujna Patel; Stela P. Petkova; et al. (Inflammation Research, 2026)
Objective This study investigated how cumulative environmental exposures influence offspring behaviour and inflammation-related molecular signatures in the brain and peripheral immune system. Methods A novel "triple-hit" mouse model was developed using C57Bl/6JAusB mice (N = 70), combining preconceptual social stress, antenatal high-fat diet, and a postnatal immune challenge (poly(I:C), 10 mg/kg). At 12 weeks, offspring underwent behavioural tests relevant to neurodevelopmental disorders (NDDs), including the Elevated Plus Maze, 3-Chamber Social Preference, Self-Grooming, and Marble Burying. A composite NDD-risk index was calculated. Single-cell RNA sequencing (scRNA-seq) and bulk proteomics were performed on male triple-hit offspring to identify differentially expressed genes and proteins associated with inflammatory pathways. Results Male triple-hit offspring showed elevated NDD-related behavioural risk and social deficits, not observed in females. scRNA-seq revealed altered inflammatory and ribosomal pathways in brain glia and peripheral immune cells. Proteomic analysis showed decreased abundance of proteins involved in inflammation, translation, chromatin remodelling, and synaptic function in both brain and blood. Conclusion Combined environmental stressors may drive male-specific behavioural and inflammatory changes relevant to NDDs. The identification of overlapping inflammatory signatures in brain and peripheral immune cells supports a role for shared immune mechanisms in brain–immune axis dysfunction. However, these pathway-level findings should be interpreted as preliminary hypotheses and warrant independent validation to confirm their mechanistic significance.

Selective Receptor Modulation by Truncated Neuropeptide Y (3–36) Dissociates Vasoconstriction from Neuroprotection in Experimental Glaucoma - Viswanthram Palanivel; Devaraj Basavarajappa; Akanksha Salkar; András M. Komáromy; Ole Tietz; Taslima Akter Eva; Nitin Chitranshi; Mehdi Mirzaei; Veer Gupta; Yuyi You; Stuart L. Graham; Vivek Gupta (Molecular Neurobiology, 2026)

The Dynamic Roles of Repressor Element 1-Silencing Transcription Factor (REST): A Double-Edged Sword in Neural Health and Disease - Taslima Akter Eva; Avinash Shenoy; Veer B. Gupta; Viswanthram Palanivel; Akanksha Salkar; Sohrab Nowroozi Nasab; Nitin Chitranshi; Mehdi Mirzaei; Yuyi You; Stuart L. Graham; Devaraj Basavarajappa; Vivek Gupta (Molecular Neurobiology, 2026)

Contributions of benthic microalgal biofilms to sediment organic carbon stocks across a salt marsh gradient - Graham J. C. Underwood; Nicola J. D. Slee; Jessica C. J. Underwood; Christopher I. D. Underwood; James L. Pinckney (Limnology and Oceanography, 2026)
Benthic microalgal (BMA) communities contribute significantly to food webs, nutrient cycling, and carbon flows in intertidal habitats. However, the contribution of BMA to saltmarsh carbon stocks (“blue carbon”) is unclear. BMA and sediment total organic carbon (TOC) stocks were measured in an east coast American Atlantic saltmarsh, revealing key relationships between biofilm biomass, carbohydrate, and carbon content. BMA biomass (chlorophyll a ) was highest in Sporobolus stands and mudflat habitats, with diatoms the dominant algal group, and cyanobacteria more important in upper saltmarsh sites. Habitat‐specific differences in biofilm properties (biomass, carbohydrates, photopigments, near‐infrared spectra) corresponded to differences in overall contributions to sediment TOC. Carbohydrates contributed between 8% and 23% of sediment TOC, with the highest levels in Sporobolus and mudflat habitats. BMA biomass and colloidal carbohydrate were significantly correlated, except on lower shore sandflats. The greatest relative contribution of colloidal carbohydrate to %TOC was in upper marsh and tidal channel habitats (1%). Mudflats had the highest %TOC (up to 5% dry weight), but TOC stocks (2000 g C m −2 to a depth of 10 cm) were highest in Sporobolus habitats. A modeling approach, based on LIDAR and sediment measures, determined a BMA carbon contribution of 1.3–8% of sediment TOC, with the lowest values in Sporobolus and mudflat habitats. Upscaling from m 2 , incorporating habitat heterogeneity, gave median values of 14–16 t TOC ha −1 for the North Inlet Estuary saltmarshes, of which BMA contributed 0.06–0.08 t C ha −1 . This approach could permit BMA contributions to blue carbon to be estimated across other saltmarshes.

From sample to sonde to Sentinel-2: insights from a multi-scale chlorophyll-a monitoring effort in the Hudson River, New York - Wilson B. Salls; Robert J. Welk; Tyler V. King; Natasha A. Scavotto; Rebecca M. Gorney; Sabina R. Gifford; Michael D. Stouder; Elizabeth A. Nystrom; Jennifer L. Graham (Environmental Monitoring and Assessment, 2025)
Monitoring cyanobacteria and other nuisance phytoplankton in the Hudson River is of great interest given its societal and ecological importance. Satellite remote sensing provides a cost-effective method to monitor chlorophyll- a (chl-a), a common proxy for algal biomass; however, the dynamic nature of rivers complicates approaches traditionally applied to lakes and oceans. During 2021–2023, we collected discrete samples for laboratory measurement of chl-a and measured in situ chl-a fluorescence during a series of longitudinal boat surveys along a 220-km reach of the lower Hudson River. Surveys were timed to coincide with Sentinel-2 satellite overpasses. We first investigated relations between laboratory-measured chl-a concentration and field-measured chl-a fluorescence, observing a weak correlation ( r 2 = 0.25) that improved substantially after splitting data by day (mean r 2 = 0.53). Separately, to estimate chl-a fluorescence using satellite data, we developed a series of random forest models leveraging the rich fluorescence dataset collected. We tested three model types: individual day models, leave-one-out models trained on all days except a holdout test day, and a single pooled model trained on all days. Generally, individual day models exhibited lowest error (mean of mean absolute error [MAE] = 0.16 relative fluorescence units [RFU]), followed by the single pooled model (MAE = 0.22 RFU). Daily holdout models showed highest error (mean MAE = 0.40 RFU); this approach was intended to represent model performance on a day unseen in the training set, providing a more conservative estimate of performance than the more traditional pooled approach. Findings from both analyses emphasize the importance of considering temporal variability when modeling riverine systems.

Assessing behavioural economic demand for morphine after an acute dose in individuals with- and without childhood trauma: a double-blind, randomised, controlled trial - Martin Trøstheim; Benjamin L. Berey; Elizabeth R. Aston; Matthew J. Gullo; Lee Hogarth; Graham Simpson; Rupert Broomby; Celia J. Morgan; Molly Carlyle (Psychopharmacology, 2025)
Background Childhood trauma is associated with positive subjective responses to acute opioids in the laboratory. Yet, its impact on behavioural economic demand for opioids remains unclear. Because demand can predict future use and misuse, we investigated whether individuals with childhood trauma also display greater demand for opioids in the laboratory. Methods This secondary analysis used data from a double-blind, randomised, controlled, counterbalanced trial. Across two sessions, individuals with ( n = 26) and without ( n = 21) childhood trauma received a high (0.15 mg/kg) and low (0.01 mg/kg) dose of intramuscular morphine 120 min before a hypothetical purchase task. Participants also regularly reported their subjective desire for the study drug. Area under the consumption and expenditure curves, and specific demand indices ( O max , P max , breakpoint , intensity , elasticity ), were analysed with non-parametric mixed models. Results Consumption and expenditure for low dose morphine was lower in the childhood trauma group when compared to high dose morphine in this group, and low dose morphine in the control group ( p s ≤ 0.03). Consistent results were obtained for specific demand indices O max , P max , and breakpoint , but not intensity or elasticity . Positive correlations between subjective desire and consumption and expenditure were only observed in the childhood trauma group ( Tau-c = 0.24–0.34, p s ≤ 0.03). Conclusion Under laboratory conditions, desires to use opioids among individuals with childhood traumas may not manifest in strong intentions to acquire these drugs. Diverging results from psychometric measures of subjective and economic opioid value highlight the need for future research to explore contextual and resilience factors to understand how problematic opioid use emerges after childhood traumas.

Projections from the supragenual nucleus to the lateral mammillary and dorsal tegmental nuclei - Jalina A. Graham; Moriah E. McGuier; Jennifer L. Marcroft; Anna C. Gundlach; Jeffrey S. Taube (Brain Structure and Function, 2025)

Place-based neighbourhood planning approaches to net zero transport - Liton Kamruzzaman; Graham Currie; Hai L. Vu; Eric J. Miller; Roger Vickerman (Journal of Transport Geography, 2025)

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

Genealogical Analysis of Replicate Flower Colour Hybrid Zones in Antirrhinum - Arka Pal; Daria Shipilina; Alan Le Moan; Adrian J. McNairn; Jennifer K. Grenier; Marek Kucka; Graham Coop; Yingguang Frank Chan; Nicholas H. Barton; David L. Field; Sean Stankowski (Molecular Ecology, 2025)
A major goal of speciation research is identifying loci that underpin barriers to gene flow. Population genomics takes a ‘bottom‐up’ approach, scanning the genome for molecular signatures of processes that drive or maintain divergence. However, interpreting the ‘genomic landscape’ of speciation is complicated, because genome scans conflate multiple processes, most of which are not informative about gene flow. However, studying replicated population contrasts, including multiple incidences of secondary contact, can strengthen inferences. In this paper, we use linked‐read sequencing (haplotagging), F ST scans and genealogical methods to characterise the genomic landscape associated with replicate hybrid zone formation. We studied two flower colour varieties of the common snapdragon, Antirrhinum majus subspecies majus , that form secondary hybrid zones in multiple independent valleys in the Pyrenees. Consistent with past work, we found very low differentiation at one well‐studied zone (Planoles). However, at a second zone (Avellanet), we found stronger differentiation and greater heterogeneity, which we argue is due to differences in the amount of introgression following secondary contact. Topology weighting of genealogical trees identified loci where haplotype diversity was associated with the two snapdragon varieties. Two of the strongest associations were at previously identified flower colour loci: Flavia , that affects yellow pigmentation, and Rosea/Eluta , two linked loci that affect magenta pigmentation. Preliminary analysis of coalescence times provides additional evidence for selective sweeps at these loci and barriers to gene flow. Our study highlights the impact of demographic history on the differentiation landscape, emphasising the need to distinguish between historical divergence and recent introgression.

The life of Evan J. Kidson (1930–2025) - Brenda Kidson Beller; Graham L. Williams; James B. Riding; Robert Scott; Merrell A. Miller (Palynology, 2025)

New taxa of dinoflagellate cysts from the Upper Cretaceous to Palaeocene strata of Bylot Island, eastern Nunavut, Canada - Graham L. Williams; Robert A. Fensome (Palynology, 2025)

Improved allometry and heartwood development of Sequoia sempervirens in secondary forests - Stephen C. Sillett; Alana R. Chin; Allyson L. Carroll; Mark E. Graham; Marie E. Antoine (Forest Ecology and Management, 2025)

Umbilical Cord Blood Endothelial Progenitor Cells Modulate Neurovascular Unit Damage in a Neonatal Rat Model of Hypoxia Ischemia - Tayla R. Penny; Yen Pham; Amy E. Sutherland; Graham Jenkin; Tamara Yawno; Suzanne L. Miller; Courtney A. McDonald (Stem Cell Reviews and Reports, 2025)
Introduction Neonatal hypoxia ischemia (HI) causes injury to the blood brain barrier (BBB), which in turn is associated with widespread cell loss. Cell therapies are currently being investigated for use in perinatal neuroprotection and umbilical cord blood (UCB) endothelial progenitor cells (EPCs; CD133+) have been previously shown to reduce gross neuropathology associated with HI; however, no study has investigated the effect of EPC treatment on the vulnerable BBB. Therefore, in this study, we investigated the effect of EPC treatment on BBB integrity in a neonatal rat model of HI. Methods HI brain injury was induced in postnatal day (PND) 7 rat pups via permanent ligation of the left carotid artery, followed by a 180-minute hypoxic challenge at 8% O 2 . At 24 h post-insult, 2 × 10 5 EPCs were administered via intraperitoneal injection. At 7 days post-HI, brains and choroid plexuses were collected for immunohistochemistry or molecular analyses. Results Neonatal HI resulted in neuropathology, with a significant increase in left hemisphere tissue loss. This was associated with microglial activation, astrogliosis and increased expression of Aquaporin 4 in the somatosensory cortex, and EPC administration significantly reduced these outcomes. Assessment of the BBB revealed GLUT1 and claudin-5 expression were significantly increased in HI animals compared to sham, and treatment with EPCs reduced these to sham control levels. Conclusion EPCs are a promising treatment option for neonatal HI as they modulate BBB changes. However, further studies are needed to understand early effects of EPC treatment and how EPC therapy modulates BBB dysfunction post HI brain injury. Graphical Abstract

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

A double-blind, randomized, placebo-controlled test of the effects of cannabidiol on fear elicited by a 10% carbon dioxide-enriched air breathing challenge - Ellen W. Leen-Feldner; Teah-Marie Bynion; Graham M. L. Eglit; Marcel O. Bonn-Miller; L. Riley Gournay; Matthew T. Feldner (Psychopharmacology, 2025)

Using mid-infrared spectroscopy to estimate soil microbial properties at the continental scale - Soni Ghimire; Yakun Zhang; Jingyi Huang; Erica L.-W. Majumder; Alfred E. Hartemink; Emily B. Graham; Odeta Qafoku; Joseph Andrews; Zachary B. Freedman (Applied Soil Ecology, 2025)

At the far end of everything: A likely Ahrensburgian presence in the far north of the Isle of Skye, Scotland - Karen Hardy; Natasha L.M. Barlow; Edward Taylor; Sarah L. Bradley; John McCarthy; Graham Rush (Journal of Quaternary Science, 2025)
A Late Upper Paleolithic (LUP) site containing Ahrensburgian‐type stone tools has been discovered at South Cuidrach, Isle of Skye, Scotland. Together with a group of intertidal stone circular alignments also recently discovered on the island, this new evidence for the occupation of northern Scotland also represents the most northerly LUP site in Britain. The timing of the continental Ahrensburgian culture is closely linked to the later part of the Younger Dryas, also known regionally as the Loch Lomond Stadial (LLS), a cold period that saw a significant ice cap and glacier expansion across the mainland of western Scotland. Here, we examine the climatic, environmental and relative sea‐level contexts and reflect on the location of this site on an island to the north‐west of the Younger Dryas ice mass. South Cuidrach is situated on the north coast of Skye, lying around 25 km north‐west of the maximum known local extent of the Younger Dryas ice mass. Most of the lithic assemblage is made from locally available baked mudstone. The site has good access to coastal and riverine resources and readily available ochre, suggesting it was deliberately chosen. Together with the new stone alignments and several other nearby sites, this region now contains more evidence for the LUP than anywhere else in Scotland. The geography and Late Glacial environment of west Scotland comprised a volatile landscape of water, mountains and fluctuating glaciers and coastlines, a challenging area at the north‐westerly limit of the European landmass that was very different to the Ahrensburgian core territories in mainland Europe. We anticipate that by examining this new evidence within the various broad geographical and geomorphological conditions, there is significant potential for the discovery of further LUP locations both on and off‐shore in this region.

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Cross-scale patterns of structure and maximum biomass in late-seral Douglas-fir-dominated rainforests - Russell D. Kramer; Stephen C. Sillett; Sean M.A. Jeronimo; Mark E. Graham; Miles E. LeFevre; Allyson L. Carroll; Robert Van Pelt (Forest Ecology and Management, 2025)

Methods for quantifying low populations of root-knot nematode (Meloidogyne spp.) in vegetable soils and their potential for use in monitoring programs to improve nematode management decisions - Graham Roy Stirling; Neil L. Wilson; Jennifer A. Cobon; Wayne T. O’Neill (Australasian Plant Pathology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Carbon footprints of greenhouse gas mitigation measures for a grass-based beef cattle finishing system in the UK - Asma Jebari; Taro Takahashi; Michael R. F. Lee; Adrian L. Collins; Kevin Coleman; Alison Carswell; Carmen Segura; Laura Cardenas; Graham A. McAuliffe (The International Journal of Life Cycle Assessment, 2025)
Purpose Agri-food systems across the globe are faced with the challenge of reducing their supply-chain emissions of greenhouse gases (GHGs) such as nitrous oxide (N 2 O), carbon dioxide (CO 2 ), and methane (CH 4 ). For instance, 10% of the UK’s GHG emissions are generated by agriculture, and ~ 56% of these are generated by livestock production. Numerous mitigation measures are being proposed to reduce GHG emissions from ruminants (representing 70 to 80% of total livestock emissions), particularly from beef cattle (presenting 30–40% of total livestock emissions). Methods To explore such potential, first, a business-as-usual (BAU) partial cradle-to-finishing farmgate scale modelling framework was developed. The BAU systems (i.e. steady-state productivity based on primary data from the North Wyke Farm Platform) were built using ensemble modelling wherein the RothC process-based soil organic carbon (SOC) model was integrated into the life cycle assessment (LCA) framework to conduct a trade-off analysis related to mitigation measures applicable to the study system. Potential mitigation measures were applied to the BAU scenario. The interventions assessed included: (i) extensification; (ii) adopting anaerobic digestion technology; and (iii) the use of the nitrification inhibitor DCD and substitution of fertiliser nitrogen with symbiotically fixed nitrogen from legumes. Results The partial carbon footprint for 1 kg of beef liveweight gain leaving the farmgate could be reduced by 7.5%, 12%, or 26% by adopting nitrification inhibitors, white clover introduction (pending establishment success), and anaerobic digestion for manure management, respectively. Conclusions The findings highlight the importance of including emissions beyond the farmgate level to analyse the carbon footprint of different management scenarios in order to assess the sustainability of agri-food production systems.

Conservation genetics of Stylophorum diphyllum (Papaveraceae): investigating the genetic diversity and differentiation of peripheral and core populations across the range - Linda A. Lait; Brendan A. Graham; David A. Galbraith; Theresa M. Burg; J. L. McCune (Conservation Genetics, 2025)

How much seagrass does a dugong need? Metabolic rate of live wild dugongs, Dugong dugon , determined through indirect calorimetry (oxygen consumption) - Janet M. Lanyon; Helen L. Sneath; Trevor Long; Wendy H. Blanshard; Graham A. J. Worthy; David T. Booth (Marine Mammal Science, 2025)
Deterioration of seagrass beds worldwide has raised concern about the future of dugongs because almost all aspects of their life history depend on availability of seagrass. Understanding their energy metabolism and consequently how much seagrass they need will inform protective conservation strategies for dugongs. This study determined resting metabolic rate (RMR) in five wild‐caught adult dugongs by measuring oxygen consumption (O 2 ). Measurement conditions met assumptions for RMR, except that dugongs were not postabsorptive, thus a postprandial (pp) allometric equation for herbivorous mammals of similar size was used to predict an expected RMR pp for dugongs of known mass. O 2 was measured for 30 min in a metabolic tank after brief habituation. Dugongs' RMR pp was approximately half that predicted for their body mass but was higher than for manatees. Based on dugongs' RMR pp and considering plant caloric and water content, the daily minimum intake of fresh weight seagrass was 40–65 kg Halophila ovalis , or 20–40 kg Halodule spp. Greater seagrass intake would be required for growing and reproducing dugongs. Slow growth and protracted reproductive rates of dugongs are likely related to limitations in seagrass energy and nutrients. To ensure viability of this vulnerable species, it is critically important to conserve extensive healthy seagrass beds.

Comprehensive extractables and leachables sensitization analysis and practical application of a risk-based approach to sensitization assessment for parenteral drug products - Patricia Parris; Geraldine Whelan; Martyn L. Chilton; Claire Beaumont; Anders Burild; Uma Bruen; Courtney Callis; Jessica Graham; Natalia Kovalova; Elizabeth A. Martin; Melisa Masuda-Herrera; Carsten Worsøe; et al. (Regulatory Toxicology and Pharmacology, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Detecting 127Xe in an atmospheric tracer experiment - Paul W. Eslinger; Matthew A. Goodwin; Ramesh S. Sarathi; Glen A. Warren; Brian T. Schrom; Michael Foxe; Daniel Chester; Graham Galvin; Reagan S. Turley; L. Daniel Hardy (Journal of Environmental Radioactivity, 2025)

Corrigendum to “Dissecting the Enterococcal Polysaccharide Antigen (EPA) structure to explore innate immune evasion and phage specificity” [Carbohydr. Polym. 347 (1 January 2025) 122686] - Jessica L. Davis; Joshua S. Norwood; Robert E. Smith; Finn O'Dea; Krishna Chellappa; Michelle L. Rowe; Mike P. Williamson; Graham P. Stafford; Evguenii Vinogradov; Emmanuel Maes; Yann Guérardel; Stéphane Mesnage (Carbohydrate Polymers, 2025)

Validation of Markerless Motion Capture for Soldier Movement Patterns Assessment Under Varying Body-Borne Loads - Isabel Coll; Matthew P. Mavor; Thomas Karakolis; Ryan B. Graham; Allison L. Clouthier (Annals of Biomedical Engineering, 2025)

Reaping what we sow: Centering values in food systems transformations research - O. Care; Julie G. Zaehringer; Michael J. Bernstein; Mollie Chapman; Cecilie Friis; Sonia Graham; L. Jamila Haider; Mónica Hernández-Morcillo; Harry Hoffmann; Maria Lee Kernecker; Hannah Pitt; Verena Seufert (Ambio, 2025)
In many transdisciplinary research settings, a lack of attention to the values underpinning project aims can inhibit stakeholder engagement and ultimately slow or undermine project outcomes. As a research collective (The Careoperative), we have developed a set of four shared values through a facilitated visioning process, as central to the way we work together: care, reflexivity, inclusivity, and collectivity. In this paper, we explore the implications of a values-centered approach to collaboration in food system transformation research. The paper presents two cases that illustrate how researchers might approach centering values in practice. Where much research on food system transformation focuses on values of food system stakeholders, we contribute insights into the values of researchers in such transdisciplinary endeavors. Specifically, we argue that researchers working on sustainability transformations need to be better prepared to engage in such reflections and aspire to embody values aligned with the transformations they seek to research.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Balancing boat‐electrofishing sampling effort against costs for nearshore fish communities in the Toronto waterfront, Lake Ontario - Sebastian Theis; Angela Wallace; Brian Graham; Brynn Coey; Lyndsay Cartwright; Mark Poesch; Rick Portiss; Jonathan L. W. Ruppert (Fisheries Management and Ecology, 2025)
To enhance management of aquatic systems, long‐term monitoring programs are crucial. However, managers often lack sufficient guidance in decision‐making. In this study, we analyzed nearshore electrofishing data from Lake Ontario spanning 18 years and over 100,000 caught fish to assess sampling designs for various coastal habitats. Using simulation, we evaluated precision of catch per unit effort (CPUE) for all species, piscivores, and specialist species, at different levels of electrofishing sampling effort. For overall CPUE in any habitat type, increased precision declined with additional electrofishing runs, particularly after reaching 30–40 runs. Adjustments in sampling effort, such as adding 10 runs per year for open‐coast sites, increased precision of overall CPUE by 10%. Adding 8 runs per year for wetlands increased precision of specialist‐species CPUE by 10%. However, additional runs in embayments did not increase precision for all species, piscivores, or specialist species. Our findings underscore the importance of considering community composition and abundance when evaluating CPUE precision and illustrates a flexible approach to optimize sampling effort in aquatic monitoring programs.

Correlations between postmortem quantitative MRI parameters and demyelination, axonal loss and gliosis in multiple sclerosis: A systematic review and meta-analysis - Ting Shen; Samran Sheriff; Yanlin Qu; Vivek K. Gupta; Stuart L. Graham; Alexander Klistorner; Huixun Jia; Xiaodong Sun; Yuyi You (Brain Imaging and Behavior, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Dissecting the Enterococcal Polysaccharide Antigen (EPA) structure to explore innate immune evasion and phage specificity - Jessica L. Davis; Joshua S. Norwood; Robert E. Smith; Finn O'Dea; Krishna Chellappa; Michelle L. Rowe; Mike P. Williamson; Graham P. Stafford; Evguenii Vinogradov; Emmanuel Maes; Yann Guérardel; Stéphane Mesnage (Carbohydrate Polymers, 2025)

A Probabilistic View of Forbidden Links: Their Prevalence and Their Consequences for the Robustness of Plant–Hummingbird Communities - François Duchenne; Elisa Barreto; Esteban A. Guevara; Holger Beck; Carolina Bello; Rafaela Bobato; Daniela Bôlla; Emanuel Brenes; Nicole Büttner; Ana P. Caron; Nelson Chaves‐Elizondo; María J. Gavilanes; et al. (Ecology Letters, 2025)
The presence in ecological communities of unfeasible species interactions, termed forbidden links, due to physiological or morphological exploitation barriers has been long debated, but little direct evidence has been found. Forbidden links are likely to make ecological communities less robust to species extinctions, stressing the need to assess their prevalence. Here, we used a dataset of plant–hummingbird interactions, coupled with a Bayesian hierarchical model, to assess the importance of exploitation barriers in determining species interactions. We found evidence for exploitation barriers between flowers and hummingbirds across the 32 studied communities; however, the proportion of forbidden links changed drastically among communities because of changes in trait distributions. The higher the proportion of forbidden links, the more they decreased network robustness because of constraints on interaction rewiring. Our results suggest that exploitation barriers are not rare in plant–hummingbird communities and have the potential to limit the rescue of species experiencing partner extinction.

Seagrass wasting disease prevalence and lesion area increase with invertebrate grazing across the northeastern Pacific - Lillian R. Aoki; Carmen J. Ritter; Deanna S. Beatty; Lia K. Domke; Ginny L. Eckert; Olivia J. Graham; Carla P. Gomes; Collin Gross; Timothy L. Hawthorne; Eliza Heery; Margot Hessing‐Lewis; Kevin Hovel; et al. (Ecology, 2025)
Disease is a key driver of community and ecosystem structure, especially when it strikes foundation species. In the widespread marine foundation species eelgrass ( Zostera marina ), outbreaks of wasting disease have caused large‐scale meadow collapse in the past, and the causative pathogen, Labyrinthula zosterae , is commonly found in meadows globally. Research to date has mainly focused on abiotic environmental drivers of seagrass wasting disease, but there is strong evidence from other systems that biotic interactions such as herbivory can facilitate plant diseases. How biotic interactions influence seagrass wasting disease in the field is unknown but is potentially important for understanding dynamics of this globally valuable and declining habitat. Here, we investigated links between epifaunal grazers and seagrass wasting disease using a latitudinal field study across 32 eelgrass meadows distributed from southeastern Alaska to southern California. From 2019 to 2021, we conducted annual surveys to assess eelgrass shoot density, morphology, epifauna community, and the prevalence and lesion area of wasting disease infections. We integrated field data with satellite measurements of sea surface temperature and used structural equation modeling to test the magnitude and direction of possible drivers of wasting disease. Our results show that grazing by small invertebrates was associated with a 29% increase in prevalence of wasting disease infections and that both the prevalence and lesion area of disease increased with total epifauna abundances. Furthermore, these relationships differed among taxa; disease levels increased with snail ( Lacuna spp.) and idoteid isopod abundances but were not related to abundance of ampithoid amphipods. This field study across 23° of latitude suggests a prominent role for invertebrate consumers in facilitating disease outbreaks with potentially large impacts on coastal seagrass ecosystems.

Development of bovine IgG3-specific assays using a novel recombinant single-domain binding reagent - Alistair Noble; Elliot Moorhouse; Abigail L. Hay; Basudev Paudyal; William Mwangi; Danish Munir; Marie Bonnet-Di Placido; Elma Tchilian; John A. Hammond; Simon P. Graham (Veterinary Immunology and Immunopathology, 2024)

qPCR-based phytoplankton abundance and chlorophyll a: A multi-year study in twelve large freshwater rivers across the United States - Chiqian Zhang; Kyle D. McIntosh; Nathan Sienkiewicz; Erin A. Stelzer; Jennifer L. Graham; Jingrang Lu (Science of The Total Environment, 2024)

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Commercial harvest and population characteristics of freshwater drum and buffalo Ictiobus spp. in Ohio waters of Lake Erie - Graham F. Montague; Douglas L. Zentner; Richard A. Snow; Jory B. Bartnicki; Daniel E. Shoup; Brian A. Schmidt (Environmental Biology of Fishes, 2024)

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

Physical activity and DNA methylation–based markers of ageing in 6208 middle-aged and older Australians: cross-sectional and longitudinal analyses - Haoxin Tina Zheng; Danmeng Lily Li; Makayla W. C. Lou; Allison M. Hodge; Melissa C. Southey; Graham G. Giles; Roger L. Milne; Brigid M. Lynch; Pierre-Antoine Dugué (GeroScience, 2024)
Epigenetic age quantifies biological age using DNA methylation information and is a potential pathway by which physical activity benefits general health. We aimed to assess the cross-sectional and longitudinal associations between physical activity and epigenetic age in middle-aged and older Australians. Blood DNA methylation data for 6208 participants (40% female) in the Melbourne Collaborative Cohort Study (MCCS) were available at baseline (1990–1994, mean age, 59 years) and, of those, for 1009 at follow-up (2003–2007, mean age, 69 years). Physical activity measurements (weighted scores at baseline and follow-up and total MET hours per week at follow-up) were calculated from self-reported questionnaire data. Five blood methylation–based markers of ageing ( PCGrimAge , PCPhenoAge , bAge , DNAmFitAge , and DunedinPACE ) and four fitness-related markers ( DNAmGaitspeed , DNAmGripmax , DNAmVO2max , and DNAmFEV1 ) were calculated and adjusted for age. Linear regression was used to examine the cross-sectional and longitudinal associations between physical activity and epigenetic age. Effect modification by age, sex, and BMI was assessed. At baseline, a standard deviation (SD) increment in physical activity was associated with 0.03-SD ( DNAmFitAge , 95%CI = 0.01, 0.06, P = 0.02) to 0.07-SD ( bAge , 95%CI = 0.04, 0.09, P = 2 × 10 −8 ) lower epigenetic age. These associations were attenuated after adjustment for other lifestyle variables. Only weak evidence was found for the longitudinal association ( N = 1009) of changes in physical activity and epigenetic age (e.g. DNAmFitAge : adjusted β = − 0.04, 95%CI = − 0.08, 0.01). The associations were not modified by age, sex, or BMI. In middle-aged and older Australians, higher levels of self-reported physical activity were associated with slightly lower epigenetic age.

U–Pb–Hf and morphological evolution of zircon from granites associated with world-class tungsten skarn deposits in the northern Canadian Cordillera - Kirsten L. Rasmussen; Hendrik Falck; Yan Luo; D. Graham Pearson; Pilar Lecumberri–Sanchez (Lithos, 2024)

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Rapid remote volcanic ashfall impact assessment for the 2022 eruption of Hunga volcano, Tonga: a bespoke approach and lessons identified - Alana M. Weir; James H. Williams; Thomas M. Wilson; Josh L. Hayes; Carol Stewart; Graham S. Leonard; Christina Magill; Susanna F. Jenkins; Shaun Williams; Heather M. Craig; Taaniela Kula; Stuart Fraser; et al. (Bulletin of Volcanology, 2024)
When disasters occur, rapid impact assessments are required to prioritise response actions, support in-country efforts and inform the mobilisation of aid. The 15 January 2022 eruption of Hunga volcano, Tonga, and the resulting atmospheric shockwave, ashfall, underwater mass disturbance and tsunami, caused substantial impacts across the Kingdom of Tonga. Volcanic impacts on the scale observed after the eruption are rare, necessitating a reliance on international advice and assistance. The situation was complicated by the loss of Tonga’s international submarine fibreoptic cable (causing a complete loss of communications for approximately 20 days) along with border closures due to the COVID-19 pandemic. A need emerged for a rapid remote volcanic impact assessment and provision of specialist advice to help inform the response of international partners. Here we present a novel methodology for conducting rapid remote volcanic ashfall impact assessments, conducted over a 10-day period following the eruption. We used three different hazard models for ashfall thickness across the main island of Tongatapu and available asset information and vulnerability functions for buildings, agriculture, electricity networks, water supply and roads, to provide initial estimates of losses due to ashfall from the 15 January eruption. For buildings, we estimated losses both as total losses and as percentages of the total replacement cost of buildings on Tongatapu. For agriculture, we made probabilistic estimates of production losses for three different crop classes. For ashfall clean-up, we estimated ranges of ashfall volumes requiring clean-up from road surfaces and roofs. For water supply, electricity networks and roads, our analysis was limited to assessing the exposure of important assets to ashfall, as we had insufficient information on system configurations to take the analysis further. Key constraints on our analysis were the limited nature of critical infrastructure asset inventories and the lack of volcanic vulnerability models for tropical regions including Pacific Island nations. Key steps towards iteratively improving rapid remote impact assessments will include developing vulnerability functions for tropical environments as well as ground-truthing estimated losses from remote approaches against in-person impact assessment campaigns.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Developing Oak Buds Produce Volatile Emissions in Response to Herbivory by Freshly Hatched Caterpillars - Jessica L. Graham; Michael Staudt; Bruno Buatois; Samuel P. Caro (Journal of Chemical Ecology, 2024)

Navigating Research Challenges to Estimate Blue Carbon Benefits From Saltmarsh Restoration - Victoria G. Mason; Annette Burden; Graham Epstein; Lucy L. Jupe; Kevin A. Wood; Martin W. Skov (Global Change Biology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Dietary factors and DNA methylation-based markers of ageing in 5310 middle-aged and older Australian adults - Lachlan Cribb; Allison M. Hodge; Melissa C. Southey; Graham G. Giles; Roger L. Milne; Pierre-Antoine Dugué (GeroScience, 2024)
The role of nutrition in healthy ageing is acknowledged but details of optimal dietary composition are still uncertain. We aimed to investigate the cross-sectional associations between dietary exposures, including macronutrient composition, food groups, specific foods, and overall diet quality, with methylation-based markers of ageing. Blood DNA methylation data from 5310 participants (mean age 59 years) in the Melbourne Collaborative Cohort Study were used to calculate five methylation-based measures of ageing: PCGrimAge , PCPhenoAge , DunedinPACE , ZhangAge , TelomereAge . For a range of dietary exposures, we estimated (i) the ‘equal-mass substitution effect’, which quantifies the effect of adding the component of interest to the diet while keeping overall food mass constant, and (ii) the ‘total effect’, which quantifies the effect of adding the component of interest to the current diet. For ‘equal-mass substitution effects’, the strongest association for macronutrients was for fibre intake (e.g. DunedinPACE , per 12 g/day − 0.10 [standard deviations]; 95%CI − 0.15, − 0.05, p < 0.001). Associations were positive for protein (e.g. PCGrimAge , per 33 g/day 0.04; 95%CI 0.01–0.08, p = 0.005). For food groups, the evidence tended to be weak, though sugar-sweetened drinks showed positive associations, as did artificially-sweetened drinks (e.g. DunedinPACE , per 91 g/day 0.06, 95%CI 0.03–0.08, p < 0.001). ‘Total effect’ estimates were generally very similar. Scores reflecting overall diet quality suggested that healthier diets were associated with lower levels of ageing markers. High intakes of fibre and low intakes of protein and sweetened drinks, as well as overall healthy diets, showed the most consistent associations with lower methylation-based ageing in our study.

Highly siderophile element evidence for mantle plume involvement during opening of the Atlantic Ocean - James M.D. Day; Sarah J. Woodland; Kimberley L. Nutt; Nicole Stroncik; Lotte M. Larsen; Robert B. Trumbull; D. Graham Pearson (Earth and Planetary Science Letters, 2024)

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Is it time to get over the X? Assessing the global impact and future of social media conferences in animal behaviour - Jessica A. Cusick; Ebi Antony George; E.V. (Ginny) Greenway; Mukta Watve; Kirsty Graham; Cassandra L. Raby (Animal Behaviour, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

The 15 January 2022 Hunga (Tonga) eruption: A gas-driven climactic explosion - Richard W. Henley; Cornel E.J. de Ronde; Richard J. Arculus; Graham Hughes; Thanh-Son Pham; Ana S. Casas; Vasily Titov; Sharon L. Walker (Journal of Volcanology and Geothermal Research, 2024)

Effects of dairy farming management practices on carbon balances in New Zealand’s grazed grasslands: Synthesis from 68 site-years - Aaron M. Wall; Johannes Laubach; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; John E. Hunt; Paul L. Mudge; David Whitehead; Louis A. Schipper (Agriculture, Ecosystems & Environment, 2024)

Self-rated health, epigenetic ageing, and long-term mortality in older Australians - Danmeng Lily Li; Allison M. Hodge; Melissa C. Southey; Graham G. Giles; Roger L. Milne; Pierre-Antoine Dugué (GeroScience, 2024)
Self-rated health (SRH) is a subjective indicator of overall health based on a single questionnaire item. Previous evidence found that it is a strong predictor of mortality, although the underlying mechanism is poorly understood. Epigenetic age is an objective, emerging biomarker of health, estimated using DNA methylation data at hundreds of sites across the genome. This study aimed to assess the overlap and interaction between SRH and epigenetic ageing in predicting mortality risk. We used DNA methylation data from 1059 participants in the Melbourne Collaborative Cohort Study (mean age: 69 years) to calculate three age-adjusted measures of epigenetic ageing: GrimAge , PhenoAge , and DunedinPACE . SRH was assessed using a five-category questionnaire item (“excellent, very good, good, fair, poor”). Cox models were used to assess the associations of SRH, epigenetic ageing, and their interaction, with all-cause mortality over up to 17 years of follow-up ( N deaths = 345). The association of SRH with mortality per category increase was HR = 1.29; 95%CI: 1.14–1.46. The association was slightly attenuated after adjusting for all three epigenetic ageing measures (HR = 1.25, 95%CI: 1.10–1.41). A strong gradient was observed in the association of GrimAge ( P interaction = 0.006) and DunedinPACE ( P interaction = 0.002) with mortality across worsening SRH strata. For example, the association between DunedinPACE and mortality in participants with “excellent” SRH was HR = 1.02, 95%CI: 0.73–1.43 and for “fair/poor” HR = 1.72, 95%CI: 1.35–2.20. SRH and epigenetic ageing were synergistic risk factors of mortality in our study. These findings suggest that consideration of subjective and objective factors may improve general health assessment, which has implications for the ongoing development of molecular markers of ageing.

A global review of urban blue-green planning tools - A.Chathurika S. Perera; Peter J. Davies; Petra L. Graham (Land Use Policy, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Methane emissions from animal agriculture: Micrometeorological solutions for challenging measurement situations - Johannes Laubach; Thomas K. Flesch; Christof Ammann; Mei Bai; Zhiling Gao; Lutz Merbold; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; John E. Hunt; Aaron M. Wall; Louis A. Schipper (Agricultural and Forest Meteorology, 2024)

Randomized trial in rural Native American homes heated with wood stoves: results from the EldersAIR study - Curtis W. Noonan; Ethan S. Walker; Erin O. Semmens; Annie Belcourt; Johna Boulafentis; Crissy Garcia; Jon Graham; Nolan Hoskie; Eugenia Quintana; Julie Simpson; Paul Smith; Howard L. Teasley; et al. (Air Quality, Atmosphere & Health, 2024)

Herbert J. Sullivan (1933–2023): an AASP pioneer - Graham L. Williams (Palynology, 2024)

Associations between violent crime inside and outside, air temperature, urban heat island magnitude and urban green space - Heather R. Stevens; Petra L. Graham; Paul J. Beggs; Alessandro Ossola (International Journal of Biometeorology, 2024)
There are more incidents of violence in summer and on hot days, a trend likely to be exacerbated by climate change. Urban areas experience additional temperature modulation due to the urban form, however, to date, no studies have considered the effect of the urban heat island (UHI) or green space with respect to the temperature–violence relationship. This study modelled the relationship between the number of daily violent crime incidents that occurred inside or outside between July 2013 and June 2018, and the average surface UHI or percentage greencover (including grasses, shrubs and trees) within each local government area in Greater Sydney, Australia. Panelised negative binomial time series regression models indicated that the violent crime rate was associated with higher surface UHI for crimes committed outside ( p = 0.006) but not inside ( p = 0.072). Greater percentage of all vegetation was associated with significantly lower rates of violent crime committed outside ( p = 0.011) but was not associated with violent crimes committed inside ( p = 0.430). More socio-economic disadvantage was associated with higher rates of violent crime committed inside ( p = 0.002) but not outside ( p = 0.145). Greater temperature was non-linearly associated with higher rates of violent crime committed both inside and outside ( p < 0.001). The findings of this study are important because both violence and heat exposure are critical health issues and will be stressed by urbanisation and climate change. The expansion of green space and/or reduction in UHI may mitigate these effects.

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Spawning and larval development of Colossendeis megalonyx , a giant A ntarctic sea spider - Amy L. Moran; Graham T. Lobert; Ming Wei Aaron Toh (Ecology, 2024)

ELSSIE: A compact stereo spectral imager for planetary surface morphology and composition - Scott L. Murchie; Frank P. Seelos; Bethany L. Ehlmann; John D. Boldt; Lawrence E. Brown; Jacob M. Greenberg; Karl A. Hibbitts; W. Jeffrey Lees; David M. Linko; Joseph J. Linden; Graham P. Murphy; Jorge I. Núñez; et al. (Planetary and Space Science, 2024)

Prediction of solar energetic events impacting space weather conditions - Manolis K. Georgoulis; Stephanie L. Yardley; Jordan A. Guerra; Sophie A. Murray; Azim Ahmadzadeh; Anastasios Anastasiadis; Rafal Angryk; Berkay Aydin; Dipankar Banerjee; Graham Barnes; Alessandro Bemporad; Federico Benvenuto; et al. (Advances in Space Research, 2024)

Mean reef fish body size decreases towards warmer waters - Amy Rose Coghlan; Julia L. Blanchard; Simon Wotherspoon; Rick D. Stuart‐Smith; Graham J. Edgar; Neville Barrett; Asta Audzijonyte (Ecology Letters, 2024)
Aquatic ectotherms often attain smaller body sizes at higher temperatures. By analysing ~15,000 coastal‐reef fish surveys across a 15°C spatial sea surface temperature (SST) gradient, we found that the mean length of fish in communities decreased by ~5% for each 1°C temperature increase across space, or 50% decrease in mean length from 14 to 29°C mean annual SST. Community mean body size change was driven by differential temperature responses within trophic groups and temperature‐driven change in their relative abundance. Herbivores, invertivores and planktivores became smaller on average in warmer temperatures, but no trend was found in piscivores. Nearly 25% of the temperature‐related community mean size trend was attributable to trophic composition at the warmest sites, but at colder temperatures, this was

Synchrotron speciation of umbilical cord mercury and selenium after environmental exposure in Niigata - Monica Weng; Natalia V. Dolgova; Linda I. Vogt; Muhammad Qureshi; Dimosthenis Sokaras; Thomas Kroll; Hisashi Saitō; John L. O’Donoghue; Gene E. Watson; Gary J. Myers; Tomoko Sekikawa; Ingrid J. Pickering; et al. (NeuroToxicology, 2024)

Genetic parameter estimates for sensory and meat quality traits measured at 3 and 29 days of aging of beef from Canadian crossbred cattle - Marcos Claudio S. Virtuoso; Anahid Hosseini; Jennifer L. Aalhus; Manuel Juárez; Heather L. Bruce; Changxi Li; John A. Basarab; Tiago S. Valente; Graham Plastow (Meat Science, 2024)

Pectoral muscle removal in mammogram images: A novel approach for improved accuracy and efficiency - Simin Chen; Debbie L. Bennett; Graham A. Colditz; Shu Jiang (Cancer Causes & Control, 2024)
Purpose Accurate pectoral muscle removal is critical in mammographic breast density estimation and many other computer-aided algorithms. We propose a novel approach to remove pectoral muscles form mediolateral oblique (MLO) view mammograms and compare accuracy and computational efficiency with existing method (Libra). Methods A pectoral muscle identification pipeline was developed. The image is first binarized to enhance contrast and then the Canny algorithm was applied for edge detection. Robust interpolation is used to smooth out the pectoral muscle region. Accuracy and computational speed of pectoral muscle identification was assessed using 951 women (1,902 MLO mammograms) from the Joanne Knight Breast Health Cohort at Washington University School of Medicine. Results Our proposed algorithm exhibits lower mean error of 12.22% in comparison to Libra’s estimated error of 20.44%. This 40% gain in accuracy was statistically significant ( p < 0.001). The computational time for the proposed algorithm is 5.4 times faster when compared to Libra (5.1 s for proposed vs. 27.7 s for Libra per mammogram). Conclusion We present a novel approach for pectoral muscle removal in mammogram images that demonstrates significant improvement in accuracy and efficiency compared to existing method. Our findings have important implications for the development of computer-aided systems and other automated tools in this field.

Too much too soon? Risk factors for fear behaviour in foster kittens prior to adoption - Courtney Graham; David L. Pearl; Lee Niel (Applied Animal Behaviour Science, 2024)

Characterisation of typical enteropathogenic Escherichia coli (tEPEC) lineages and novel bfpA variants detected in Australian fruit bats (Pteropus poliocephalus) - Fiona McDougall; David Gordon; Roy Robins-Browne; Vicki Bennett-Wood; Wayne S.J. Boardman; Petra L. Graham; Michelle Power (Science of The Total Environment, 2023)

Synchrotron X-ray methods in the study of mercury neurotoxicology - Ashley K. James; Bogdan F. Popescu; Monica Weng; Gary J. Myers; John L. O’Donoghue; Gene E. Watson; Ingrid J. Pickering; Graham N. George (NeuroToxicology, 2023)

Anti-inflammatory Effects of Siponimod in a Mouse Model of Excitotoxicity-Induced Retinal Injury - Devaraj Basavarajappa; Vivek Gupta; Nitin Chitranshi; Deepa Viswanathan; Veer Gupta; Roshana Vander Wall; Viswanthram Palanivel; Mehdi Mirzaei; Yuyi You; Alexander Klistorner; Stuart L. Graham (Molecular Neurobiology, 2023)
Glaucoma is a leading cause of permanent blindness worldwide and is characterized by neurodegeneration linked to progressive retinal ganglion cell (RGC) death, axonal damage, and neuroinflammation. Glutamate excitotoxicity mediated through N-methyl-D-aspartate (NMDA) receptors plays a crucial role in glaucomatous RGC loss. Sphingosine 1-phosphate receptors (S1PRs) are important mediators of neurodegeneration and neuroinflammation in the brain and the retina. Siponimod is an immunomodulatory drug for multiple sclerosis and is a selective modulator of S1PR subtypes 1 and 5 and has been shown to have beneficial effects on the central nervous system (CNS) in degenerative conditions. Our previous study showed that mice administered orally with siponimod protected inner retinal structure and function against acute NMDA excitotoxicity. To elucidate the molecular mechanisms behind these protective effects, we investigated the inflammatory pathways affected by siponimod treatment in NMDA excitotoxicity model. NMDA excitotoxicity resulted in the activation of glial cells coupled with upregulation of the inflammatory NF-kB pathway and increased expression of TNFα, IL1-β, and IL-6. Siponimod treatment significantly reduced glial activation and suppressed the pro-inflammatory pathways. Furthermore, NMDA-induced activation of NLRP3 inflammasome and upregulation of neurotoxic inducible nitric oxide synthase (iNOS) were significantly diminished with siponimod treatment. Our data demonstrated that siponimod induces anti-inflammatory effects via suppression of glial activation and inflammatory singling pathways that could protect the retina against acute excitotoxicity conditions. These findings provide insights into the anti-inflammatory effects of siponimod in the CNS and suggest a potential therapeutic strategy for neuroinflammatory conditions.

Blue carbon benefits from global saltmarsh restoration - Victoria G. Mason; Annette Burden; Graham Epstein; Lucy L. Jupe; Kevin A. Wood; Martin W. Skov (Global Change Biology, 2023)
Coastal saltmarshes are found globally, yet are 25%–50% reduced compared with their historical cover. Restoration is incentivised by the promise that marshes are efficient storers of ‘blue’ carbon, although the claim lacks substantiation across global contexts. We synthesised data from 431 studies to quantify the benefits of saltmarsh restoration to carbon accumulation and greenhouse gas uptake. The results showed global marshes store approximately 1.41–2.44 Pg carbon. Restored marshes had very low greenhouse gas (GHG) fluxes and rapid carbon accumulation, resulting in a mean net accumulation rate of 64.70 t CO 2 e ha −1 year −1 . Using this estimate and potential restoration rates, we find saltmarsh regeneration could result in 12.93–207.03 Mt CO 2 e accumulation per year, offsetting the equivalent of up to 0.51% global energy‐related CO 2 emissions—a substantial amount, considering marshes represent

Examination of the potential of refrigerated seawater to improve live transport of the mussel Perna canaliculus: Physiological responses, meat quality and safety implications under different chilled storage conditions - Nicholas P.L. Tuckey; Belinda A. Timms; Graham C. Fletcher; Graeme Summers; Natalí J. Delorme; Jessica A. Ericson; Norman L.C. Ragg; Poppy Miller; Reginald Wibisono; Roland Taylor; Serean L. Adams; Leonardo N. Zamora (Aquaculture, 2023)

Exploratory analysis of reflective, reactive, and homeostatic eating behaviour traits on weight change during the 18-month NoHoW weight maintenance trial - Clarissa A. Dakin; Graham Finlayson; Graham Horgan; António L. Palmeira; Berit L. Heitmann; Sofus C. Larsen; Falko F. Sniehotta; R. James Stubbs (Appetite, 2023)

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

Geological controls of discharge variability in the Thames Basin, UK from cross-spectral analyses: Observations versus modelling - Graham P. Weedon; Emma L. Robinson; John P. Bloomfield; Stephen Turner; Emily J. Crane; Martin J. Best (Journal of Hydrology, 2023)

Cheetah spatiotemporal overlap with other large carnivores and prey at camera-trap sites: do they fit the niche-complementarity hypothesis? - Kristina L. Cornhill; Guy A. Balme; Luke T. B. Hunter; Graham I. H. Kerley (Mammalian Biology, 2023)
In guilds, such as the large predators, species compete over multiple resources that are both consumable and non-consumable. The niche complementary hypothesis states that competitors can overlap in resource use if there is low overlap for at least one shared resource. In Africa, cheetah, Acinonyx jubatus , compete with other large carnivores across space, time and prey and are known to be subordinate; however, rarely has the entire guild been considered when assessing resource partitioning by cheetah. Using camera-trap data from four areas sampled over 4 years, we compared spatial and temporal overlap between cheetah and other large carnivores. Moreover, we estimated short-term avoidance of sites by cheetah after another large carnivore had visited. We show that cheetah align with the niche complementary hypothesis to avoid other large carnivores. Cheetah experienced high overlap with African wild dog, Lycaon pictus, activity patterns but avoided sites that were used frequently by them. The inverse was observed for lion, Panthera leo , and spotted hyena, Crocuta crocuta , with cheetah avoiding them across time but not space. Cheetah experienced moderate overlap with leopard, Panthera pardus, across both space and time, with only possible short-term avoidance occurring. Finally, cheetah exhibited high levels of spatial and temporal overlap with preferred prey species, suggesting a novel demonstration of the trade-off between resource acquisition and predator avoidance. Our results showcase the importance of taking multiple scales and resource axes into consideration when determining species abilities to co-exist and provides tools for managers working in highly managed systems.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

An integrated clinoform trajectory and sequence stratigraphic model for the Labrador margin, offshore eastern Canada - Lynn T. Dafoe; Kate Dickie; Graham L. Williams (Marine and Petroleum Geology, 2023)

Effectiveness of Qualitative and Quantitative Instruments in Assessment and Evaluation of Community Based Nutrition Education Programs - O. Udenyi; C. Castor; L. Thompson; T. Fungwe; A. Graham (Journal of the Academy of Nutrition and Dietetics, 2023)

Widespread distribution of honey bee-associated pathogens in native bees and wasps: Trends in pathogen prevalence and co-occurrence - Kaitlin R. Deutsch; Jason R. Graham; Humberto F. Boncristiani; Tomas Bustamante; Ashley N. Mortensen; Daniel R. Schmehl; Ashlyn E. Wedde; Dawn L. Lopez; Jay D. Evans; James D. Ellis (Journal of Invertebrate Pathology, 2023)

Canada and ocean climate adaptation: tracking law and policy responses, charting future directions - David L. VanderZwaag; Sara L. Seck; Laura Graham; Jonathon Frontain; Kieran Simpson (Frontiers in Marine Science, 2023)
This research article provides a law and policy summary of climate change adaptation initiatives in Canada at the ocean-climate nexus. Three levels of governance are examined (national, provincial, and Indigenous) with a focus on the Atlantic region. The research method was the review of relevant and newly amended laws, regulations and policy statements, and related commentaries. The roles of the federal government are first described with key developments including the launch of a Climate Adaptation Platform in 2012 to share adaptation experiences and information and release of a National Adaptation Strategy and accompanying Adaptation Action Plan in November 2022. Federal adaptation efforts in the areas of fisheries, aquaculture and shipping are also reviewed along with progress in establishing marine protected areas (MPAs) and other effective area-based conservation measures. Provincial adaptation initiatives are next summarized with a focus on the four Atlantic provinces. Those provinces have established a regional hub, CLIMAtlantic, to provide climate information and advance climate-related research and training. Each province has developed a climate action plan which includes climate adaptation priorities. Indigenous-led climate engagement and adaptation initiatives are finally described including the publication in 2019 of a National Inuit Climate Change Strategy , regional initiatives of the Atlantic Policy Congress of First Nations Chiefs Secretariat, and the development of climate adaptation plans by select First Nation communities in the Atlantic region. The paper concludes by discussing future law and policy directions to make Canada more “climate ready.” Adoption of climate adaptation strategies for governmental departments and agencies with ocean and coastal responsibilities should be a priority. Incorporating climate change adaptation responsibilities through legislative and regulatory changes also needs to be considered, for example, by amending Canada’s Oceans Act to recognize the role of oceans in climate adaptations and mitigation, to authorize the designation of MPAs as climate refuges and to require adaptive and dynamic MPA management plans through strict monitoring and timely review provisions. Indigenous peoples must be effectively included in all climate adaptation discussions and planning.

An analogous scale model for laboratory mixing studies - J. Wu; L. Graham; S. Peacock; B. Nguyen; Y. Feng; M. Hurley; G. Short; D. Harris; W. Bruckard (Minerals Engineering, 2023)

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Mechanisms and shapes of causal exposure-response functions for asbestos in mesotheliomas and lung cancers - Louis Anthony Cox; Kenneth T. Bogen; Rory Conolly; Uschi Graham; Suresh Moolgavkar; Günter Oberdörster; Victor L. Roggli; Francesco Turci; Brooke Mossman (Environmental Research, 2023)

Changes in Floral Induction Genes During Photoperiod Induction in Flowering and Reluctant-to-Flowering Sugarcane Varieties - Donna Glassop; Graham D. Bonnett; Anne L. Rae (Sugar Tech, 2023)

Designing an Extensive Conservation Reserve Network with Economic, Ecological and Spatial Criteria - Hayri Önal; Robert L. Pressey; Graham I. H. Kerley; Malcolm Ridges (Environmental Modeling & Assessment, 2023)

The phytotoxicity of soil-applied herbicides is enhanced in the first-year post strategic deep tillage - Tom J. Edwards; Stephen L. Davies; Ron J. Yates; Mick Rose; John G. Howieson; Graham O’Hara; Emma J. Steel; David JM Hall (Soil and Tillage Research, 2023)

Heritable methylation marks associated with prostate cancer risk - James G. Dowty; Chenglong Yu; Mahnaz Hosseinpour; Jihoon Eric Joo; Ee Ming Wong; Tu Nguyen-Dumont; Joseph Rosenbluh; Graham G. Giles; Roger L. Milne; Robert J. MacInnis; Pierre-Antoine Dugué; Melissa C. Southey (Familial Cancer, 2023)
DNA methylation marks that are inherited from parents to offspring are known to play a role in cancer risk and could explain part of the familial risk for cancer. We therefore conducted a genome-wide search for heritable methylation marks associated with prostate cancer risk. Peripheral blood DNA methylation was measured for 133 of the 469 members of 25 multiple-case prostate cancer families, using the EPIC array. We used these families to systematically search the genome for methylation marks with Mendelian patterns of inheritance, then we tested the 1,000 most heritable marks for association with prostate cancer risk. After correcting for multiple testing, 41 heritable methylation marks were associated with prostate cancer risk. Separate analyses, based on 869 incident cases and 869 controls from a prospective cohort study, showed that 9 of these marks near the metastable epiallele VTRNA2-1 were also nominally associated with aggressive prostate cancer risk in the population.

Recent progress on understanding coronal mass ejection/flare onset by a NASA living with a star focused science team - Mark G. Linton; Spiro K. Antiochos; Graham Barnes; Yuhong Fan; Yang Liu; Benjamin J. Lynch; Andrey N. Afanasyev; C. Nick Arge; Joan Burkepile; Mark C.M. Cheung; Joel T. Dahlin; Marc L. DeRosa; et al. (Advances in Space Research, 2023)

Experimental Protocol and Phantom Design and Development for Performance Characterization of Conventional Devices for Peripheral Vascular Interventions - Yara Alawneh; James J. Zhou; Alykhan Sewani; Mohammadmahdi Tahmasebi; Trisha L. Roy; Ahmed Kayssi; Andrew D. Dueck; Graham A. Wright; M. Ali Tavallaei (Annals of Biomedical Engineering, 2023)

Rock-to-metal ratios of the rare earth elements - Nedal T. Nassar; Graham W. Lederer; Abraham J. Padilla; Joseph Gambogi; Daniel J. Cordier; Jamie L. Brainard; Joseph D. Lessard; Ryan Charab (Journal of Cleaner Production, 2023)

Chilling injury in human kidney tubule cells after subzero storage is not mitigated by antifreeze protein addition - Heather E. Tomalty; Laurie A. Graham; Virginia K. Walker; Peter L. Davies (Cryobiology, 2023)

A robust discrimination scheme for ocean island basalts based on Ce/Rb, Tb/La, and Ba/Nb ratios - Meysam Akbari; Mohammad Reza Ghorbani; Brian L. Cousens; Ian T. Graham (Chemical Geology, 2023)

Spatial ecology of a newly described oceanic manta ray population in the Atlantic Ocean - F. Garzon; Z. T. A. Seymour; Z. L. Monteiro; R. T. Graham (Marine Biology, 2023)
The oceanic manta ray ( Mobula birostris ) is a circumglobally distributed species, but little to no information exists for many parts of their range. The eastern central Atlantic Ocean is a particularly data-deficient area, where manta ray presence has seldom been reported and regional descriptions of the distribution, movement, and connectivity of populations are unavailable. This study makes use of satellite telemetry, coupled with ecological niche modeling, to provide the first description an oceanic manta ray population in the region based on observations from Cabo Verde, and describes the most likely distribution of the species in the region. Repeated surveys between 2015 and 2019 and data from 11 satellite-tracked individuals revealed a reliable and continued presence of manta rays in the archipelago, although the number of sightings was considerably lower than those reported for some of the major aggregation sites for the species and no individual was ever re-sighted. Ecological niche modeling indicates suitable habitat for manta rays exists in Cabo Verde for most of the year, though in considerably higher extent during the summer months. The model furthermore suggests possible seasonal connections between the archipelago and the wider Gulf of Guinea. The role of Cabo Verde in the life-history of oceanic manta rays in the region remains to be elucidated, though the low abundance and re-sighting frequency, coupled with modeling suggesting expanding and contracting suitable habitat, suggests that Cabo Verde might be a key stop-over along a potentially longer movement corridor.

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Using cyanobacteria and other phytoplankton to assess trophic conditions: A qPCR-based, multi-year study in twelve large rivers across the United States - Chiqian Zhang; Kyle D. McIntosh; Nathan Sienkiewicz; Erin A. Stelzer; Jennifer L. Graham; Jingrang Lu (Water Research, 2023)

84 Relationships between feed protein fractions and the hindgut microbiome in the exercising horse - P. Graham-Thiers; L. Bowen (Journal of Equine Veterinary Science, 2023)

On the relevance of animal behavior to the management and conservation of fishes and fisheries - Steven J. Cooke; Heather L. Auld; Kim Birnie-Gauvin; Chris K. Elvidge; Morgan L. Piczak; William M. Twardek; Graham D. Raby; Jacob W. Brownscombe; Jonathan D. Midwood; Robert J. Lennox; Christine Madliger; Alexander D. M. Wilson; et al. (Environmental Biology of Fishes, 2023)

The compositional diversity and temporal evolution of an active andesitic arc stratovolcano: Tongariro, Taupō Volcanic Zone, New Zealand - Leo R. Pure; Colin J. N. Wilson; Bruce L. A. Charlier; John A. Gamble; Dougal B. Townsend; Graham S. Leonard (Contributions to Mineralogy and Petrology, 2023)
New geochemical data, including Sr–Nd–Pb isotopes for whole-rock and groundmass samples, are reported for edifice-forming eruptives at Tongariro volcano, New Zealand, which span its ~ 350 ka to late Holocene history. Tongariro eruptives are medium-K basaltic-andesites to dacites (53.0–66.2 wt% SiO 2 ) that evolved via assimilation-fractional crystallisation (AFC) processes partly or mostly in the uppermost 15 km of the crust. When ordered chronologically using a high-resolution 40 Ar/ 39 Ar-dated eruptive stratigraphy, the compositional data show systematic 10–130 kyr cycles. Mafic replenishment events inferred from MgO values occurred at ~ 230, ~ 151, ~ 88 and ~ 56 ka and in the late Holocene, with high-MgO flank vents erupting at ~ 160, ~ 117, ~ 35 and ~ 17.5 ka. Cycles in Sm/Nd, 87 Sr/ 86 Sr, 143 Nd/ 144 Nd and Pb isotopic ratios, which are decoupled from MgO, K 2 O and Rb/Sr cycles, indicate periods of prolonged crustal residence of magmas from ~ 230 to ~ 100 ka and ~ 95 to ~ 30 ka. AFC modelling shows that intermediate and silicic melt compositions, with r-values between 0.1 and 1, are needed to reproduce Tongariro compositional arrays. AFC models also indicate that ~ 20% of the average Tongariro magma comprises assimilated (meta)sedimentary basement material. Locally, Tongariro and adjacent Ruapehu volcanoes attain their most crust-like 87 Sr/ 86 Sr and 143 Nd/ 144 Nd compositions at ~ 100 and ~ 30 ka, paralleling with zircon model-age crystallisation modes at the rhyolitic Taupō volcano ~ 50 km to the NNE. These coincidences suggest that the timing and tempo of magma assembly processes at all three volcanoes were contemporaneous and may have been tectonically influenced since at least 200 ka.

Zinc on the edge—isotopic and geophysical evidence that cratonic edges control world-class shale-hosted zinc-lead deposits - David L. Huston; David C. Champion; Karol Czarnota; Jingming Duan; Matthew Hutchens; Suzanne Paradis; Mark Hoggard; Bryant Ware; George M. Gibson; Michael P. Doublier; Karen Kelley; Anne McCafferty; et al. (Mineralium Deposita, 2023)
The North Australian Zinc Belt is the largest zinc-lead province in the world, containing three of the ten largest known individual deposits (HYC, Hilton-George Fisher, and Mount Isa). The Northern Cordillera in North America is the second largest zinc-lead province, containing a further two of the world’s top ten deposits (Red Dog and Howards Pass). Despite this world-class endowment, exploration in both mineral provinces during the past 2 decades has not been particularly successful, yielding only two significant discoveries (Teena, Australia, and Boundary, Canada). One of the most important aspects of exploration is to choose mineral provinces and districts within geological belts that have the greatest potential for discovery. Here, we present results from these two zinc belts that highlight previously unused datasets for area selection and targeting. Lead isotope mapping using analyses of mineralized material has identified gradients in μ ( 238 U/ 204 Pb) that coincide closely with many major deposits. Locations of these deposits also coincide with a gradient in the depth of the lithosphere-asthenosphere boundary determined from calibrated surface wave tomography models converted to temperature. Furthermore, gradients in upward-continued gravity anomalies and a step in Moho depth correspond to a pre-existing major crustal boundary in both zinc belts. A spatial association of deposits with a linear mid- to lower-crustal resistivity anomaly from magnetotelluric data is also observed in the North Australian Zinc Belt. The change from thicker to thinner lithosphere is interpreted to localize prospective basins for zinc-lead mineralization and to control the gradient in lead isotope and geophysical data. These data, when combined with data indicative of paleoenvironment and changes in plate motion at the time of mineralization, provide new exploration criteria that can be used to identify prospective mineralized basins and define the most favorable parts of these basins.

Mitigation potential and trade-offs for nitrous oxide emissions and carbon balances of irrigated mixed-species and ryegrass-clover pastures - Johannes Laubach; John E. Hunt; Scott L. Graham; Rowan P. Buxton; Graeme N.D. Rogers; Paul L. Mudge; Jordan P. Goodrich; David Whitehead (Agricultural and Forest Meteorology, 2023)

Sediment gravity flow frequency offshore central California diminished significantly following the Last Glacial Maximum - Stephen C. Dobbs; Charles K. Paull; Eve M. Lundsten; Roberto Gwiazda; David W. Caress; Mary McGann; Marianne M. Coholich; Maureen A. L. Walton; Nora M. Nieminski; Tim McHargue; Stephan A. Graham (Frontiers in Marine Science, 2023)
A high-resolution multibeam survey from a portion of the San Simeon Channel (offshore Morro Bay, California) captured a zone of recurring troughs and ridges adjacent to prominent submarine meander bends. Through an integrated study using surveying data, sediment core analysis, radiocarbon dating, and stable isotope measurements, we hypothesize that turbidity current event frequency was higher during the late Pleistocene than at present conditions. We speculate that the rise in sea-level following the Last Glacial Maximum sequestered sedimentation largely to the shelf during the Holocene. This work suggests that the occurrence of sediment gravity flows in this region, particularly away from any submarine channels, is appreciably lower than at times of continental shelf subaerial exposure.

A comparison of meal-related appetite, food reward and eating behaviour traits in people with and without spinal cord injury - Jordan M. Fenton; James A. King; Chris J. McLeod; Sven P. Hoekstra; Graham Finlayson; Victoria L. Goosey-Tolfrey (Appetite, 2023)

Evaluating major anthropogenic VOC emission sources in densely populated Vietnamese cities. - Pamela A. Dominutti; James R. Hopkins; Marvin Shaw; Graham P. Mills; Hoang Anh Le; Duong Huu Huy; Grant L. Forster; Sekou Keita; To Thi Hien; David E. Oram (Environmental Pollution, 2023)

Using Protection Motivation Theory to Predict Intentions for Breast Cancer Risk Management: Intervention Mechanisms from a Randomized Controlled Trial - Claire C. Conley; Karen J. Wernli; Sarah Knerr; Tengfei Li; Kathleen Leppig; Kelly Ehrlich; David Farrell; Hongyuan Gao; Erin J. A. Bowles; Amanda L. Graham; George Luta; Jinani Jayasekera; et al. (Journal of Cancer Education, 2023)
The purpose of this study is to evaluate the direct and indirect effects of a web-based, Protection Motivation Theory (PMT)–informed breast cancer education and decision support tool on intentions for risk-reducing medication and breast MRI among high-risk women. Women with ≥ 1.67% 5-year breast cancer risk ( N = 995) were randomized to (1) control or (2) the PMT-informed intervention. Six weeks post-intervention, 924 (93% retention) self-reported PMT constructs and behavioral intentions. Bootstrapped mediations evaluated the direct effect of the intervention on behavioral intentions and the mediating role of PMT constructs. There was no direct intervention effect on intentions for risk-reducing medication or MRI ( p ’s ≥ 0.12). There were significant indirect effects on risk-reducing medication intentions via perceived risk, self-efficacy, and response efficacy, and on MRI intentions via perceived risk and response efficacy ( p ’s ≤ 0.04). The PMT-informed intervention effected behavioral intentions via perceived breast cancer risk, self-efficacy, and response efficacy. Future research should extend these findings from intentions to behavior. ClinicalTrials.gov Identifier: NCT03029286 (date of registration: January 24, 2017).

Correction to: Partial body cryotherapy exposure drives acute redistribution of circulating lymphocytes: preliminary findings - Catriona L. Rose; Helen McGuire; Kenneth Graham; Jason Siegler; Barbara Fazekas de St Groth; Corinne Caillaud; Kate M. Edwards (European Journal of Applied Physiology, 2023)

Partial body cryotherapy exposure drives acute redistribution of circulating lymphocytes: preliminary findings - Catriona L. Rose; Helen McGuire; Kenneth Graham; Jason Siegler; Barbara Fazekas de St Groth; Corinne Caillaud; Kate M. Edwards (European Journal of Applied Physiology, 2023)
Partial body cryotherapy (PBC) is proposed to alleviate symptoms of exercise-induced muscle damage (EIMD) by reducing associated inflammation. No studies have assessed acute PBC exposure on peripheral blood mononuclear cell mobilisation or compared these with cold water immersion (CWI), which may inform how PBC impacts inflammatory processes. This trial examined the impact of a single PBC exposure on circulating peripheral blood mononuclear cells compared to CWI or a control. 26 males were randomised into either PBC (3 min at − 110 to − 140 °C), CWI (3 min at 9 °C), or control (3 min at 24 °C), with blood samples, heart rate, and blood pressure taken before and after exposure. Cytometric analysis determined that CD8 + T-cell populations were significantly elevated after treatments, with PBC increasing CD8 + T cells to a greater degree than either CWI or CON. Natural killer cell counts were also elevated after PBC, with the increase attributed specifically to the CD56 lo CD16 + cytotoxic subset. This provides the first evidence for the effect of PBC exposure on redistribution of immune cells. An increase in circulating leukocyte subsets such as CD8 + T cells and CD56 lo CD16 + natural killer cells suggests that PBC may induce a transient mobilisation of lymphocytes. PBC may thus enable a more efficient trafficking of these cells from the circulation to the site of initial cellular insult from exercise, potentially accelerating the process of cellular recovery. This provides novel evidence on the use of PBC as a recovery treatment and may also have applicability in other clinical settings involving the recovery of damaged skeletal muscle.

Linking human impacts to community processes in terrestrial and freshwater ecosystems - Ian R. McFadden; Agnieszka Sendek; Morgane Brosse; Peter M. Bach; Marco Baity‐Jesi; Janine Bolliger; Kurt Bollmann; Eckehard G. Brockerhoff; Giulia Donati; Friederike Gebert; Shyamolina Ghosh; Hsi‐Cheng Ho; et al. (Ecology Letters, 2023)
Human impacts such as habitat loss, climate change and biological invasions are radically altering biodiversity, with greater effects projected into the future. Evidence suggests human impacts may differ substantially between terrestrial and freshwater ecosystems, but the reasons for these differences are poorly understood. We propose an integrative approach to explain these differences by linking impacts to four fundamental processes that structure communities: dispersal, speciation, species‐level selection and ecological drift. Our goal is to provide process‐based insights into why human impacts, and responses to impacts, may differ across ecosystem types using a mechanistic, eco‐evolutionary comparative framework. To enable these insights, we review and synthesise (i) how the four processes influence diversity and dynamics in terrestrial versus freshwater communities, specifically whether the relative importance of each process differs among ecosystems, and (ii) the pathways by which human impacts can produce divergent responses across ecosystems, due to differences in the strength of processes among ecosystems we identify. Finally, we highlight research gaps and next steps, and discuss how this approach can provide new insights for conservation. By focusing on the processes that shape diversity in communities, we aim to mechanistically link human impacts to ongoing and future changes in ecosystems.

Boron isotopes in blue diamond record seawater-derived fluids in the lower mantle - Margo E. Regier; Karen V. Smit; Thomas B. Chalk; Thomas Stachel; Richard A. Stern; Evan M. Smith; Gavin L. Foster; Yannick Bussweiler; Chris DeBuhr; Antony D. Burnham; Jeff W. Harris; D. Graham Pearson (Earth and Planetary Science Letters, 2023)

Controls of crystal shape on degassing mechanisms in crystal-rich magmas with rhyolitic groundmass melts - Nathan A. Graham; Jessica F. Larsen; Keir Y. Tasa; Rebecca L. deGraffenried; Katharine V. Cashman; Kelly N. McCartney (Earth and Planetary Science Letters, 2023)

Nature green with avarice and greed - Roger C. Prince; Graham N. George; Amy L. Stevens (Plant Physiology Reports, 2022)

Nonlinear multidecadal trends in organic matter dynamics in Midwest reservoirs are a function of variable hydroclimate - Ruchi Bhattacharya; John R. Jones; Jennifer L. Graham; Daniel V. Obrecht; Anthony P. Thorpe; James D. Harlan; Rebecca L. North (Limnology and Oceanography, 2022)
Dissolved organic matter (DOM) and particulate organic matter (POM) can influence biogeochemical processes in aquatic systems. An understanding, however, of the source, composition, and processes driving inland reservoir organic matter (OM) cycling at a regional scale over the long term is currently unexplored. Here, we quantify decadal patterns (> 20 yr) of DOM quantity and composition and POM in 40 reservoirs in the midcontinent United States. We built 184 Random Forest models to identify how the relative influence of watershed characteristics and limnological parameters on OM dynamics may vary over time and in synchrony with hydroclimatic anomalies. The reservoir OM quantity and composition varied nonmonotonically through time and in contrast to lake browning observed in the northern hemisphere. Reservoir DOM composition switched from humic and aromatic during wet summers to aliphatic, potentially autochthonous DOM during particularly prolonged dry summers in the mid‐2000s. The shift in reservoir DOM quantity and composition could be attributed to the change in time‐varying control of watershed and limnological factors mediated by the hydroclimatic conditions. Watershed control (e.g., percent crops) was predominant during wet summers, while the effect of reservoir morphology (e.g., maximum depth) and water quality parameters (e.g., Secchi depth, chlorophyll a ) were evident during dry summers. Thus, future predictions of drier conditions may promote “greening” with negative implications for reservoir water quality and treated drinking water. Considering the nonlinear nature of reservoir OM dynamics and its controls will help to better mitigate water quality issues in these constructed systems increasingly impacted by global changes.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The movement ecology of fishes - Steven J. Cooke; Jordanna N. Bergman; William M. Twardek; Morgan L. Piczak; Grace A. Casselberry; Keegan Lutek; Lotte S. Dahlmo; Kim Birnie‐Gauvin; Lucas P. Griffin; Jacob W. Brownscombe; Graham D. Raby; Emily M. Standen; et al. (Journal of Fish Biology, 2022)
Movement of fishes in the aquatic realm is fundamental to their ecology and survival. Movement can be driven by a variety of biological, physiological and environmental factors occurring across all spatial and temporal scales. The intrinsic capacity of movement to impact fish individually ( e.g. , foraging) with potential knock‐on effects throughout the ecosystem ( e.g. , food web dynamics) has garnered considerable interest in the field of movement ecology. The advancement of technology in recent decades, in combination with ever‐growing threats to freshwater and marine systems, has further spurred empirical research and theoretical considerations. Given the rapid expansion within the field of movement ecology and its significant role in informing management and conservation efforts, a contemporary and multidisciplinary review about the various components influencing movement is outstanding. Using an established conceptual framework for movement ecology as a guide ( i.e. , Nathan et al. , 2008: 19052), we synthesized the environmental and individual factors that affect the movement of fishes. Specifically, internal ( e.g. , energy acquisition, endocrinology, and homeostasis) and external (biotic and abiotic) environmental elements are discussed, as well as the different processes that influence individual‐level (or population) decisions, such as navigation cues, motion capacity, propagation characteristics and group behaviours. In addition to environmental drivers and individual movement factors, we also explored how associated strategies help survival by optimizing physiological and other biological states. Next, we identified how movement ecology is increasingly being incorporated into management and conservation by highlighting the inherent benefits that spatio‐temporal fish behaviour imbues into policy, regulatory, and remediation planning. Finally, we considered the future of movement ecology by evaluating ongoing technological innovations and both the challenges and opportunities that these advancements create for scientists and managers. As aquatic ecosystems continue to face alarming climate (and other human‐driven) issues that impact animal movements, the comprehensive and multidisciplinary assessment of movement ecology will be instrumental in developing plans to guide research and promote sustainability measures for aquatic resources.

Seropositivity to SARS-CoV-2 in Alberta, Canada in a post-vaccination period (March 2021–July 2021) - Jamil N. Kanji; Leonard T. Nguyen; Sabrina S. Plitt; Carmen L. Charlton; Jayne Fenton; Sheila Braun; Carol Marohn; Cheryl Lau; Lawrence W. Svenson; Deena Hinshaw; Christie Lutsiak; Nathan Zelyas; et al. (Infectious Diseases, 2022)

Mitochondrial ROS signalling requires uninterrupted electron flow and is lost during ageing in flies - Charlotte Graham; Rhoda Stefanatos; Angeline E. H. Yek; Ruth V. Spriggs; Samantha H. Y. Loh; Alejandro Huerta Uribe; Tong Zhang; L. Miguel Martins; Oliver D. K. Maddocks; Filippo Scialo; Alberto Sanz (GeroScience, 2022)
Mitochondrial reactive oxygen species (mtROS) are cellular messengers essential for cellular homeostasis. In response to stress, reverse electron transport (RET) through respiratory complex I generates high levels of mtROS. Suppression of ROS production via RET (ROS-RET) reduces survival under stress, while activation of ROS-RET extends lifespan in basal conditions. Here, we demonstrate that ROS-RET signalling requires increased electron entry and uninterrupted electron flow through the electron transport chain (ETC). We find that in old fruit flies, ROS-RET is abolished when electron flux is decreased and that their mitochondria produce consistently high levels of mtROS. Finally, we demonstrate that in young flies, limiting electron exit, but not entry, from the ETC phenocopies mtROS generation observed in old individuals. Our results elucidate the mechanism by which ROS signalling is lost during ageing.

Delimiting the cryptic diversity and host preferences of Sycophila parasitoid wasps associated with oak galls using phylogenomic data - Yuanmeng M. Zhang; Sofia I. Sheikh; Anna K. G. Ward; Andrew A. Forbes; Kirsten M. Prior; Graham N. Stone; Michael W. Gates; Scott P. Egan; Linyi Zhang; Charles Davis; Kelly L. Weinersmith; George Melika; et al. (Molecular Ecology, 2022)
Cryptic species diversity is a major challenge regarding the species‐rich community of parasitoids attacking oak gall wasps due to a high degree of sexual dimorphism, morphological plasticity, small size and poorly known biology. As such, we know very little about the number of species present, nor the evolutionary forces responsible for generating this diversity. One hypothesis is that trait diversity in the gall wasps, including the morphology of the galls they induce, has evolved in response to selection imposed by the parasitoid community, with reciprocal selection driving diversification of the parasitoids. Using a rare, continental‐scale data set of Sycophila parasitoid wasps reared from 44 species of cynipid galls from 18 species of oak across the USA, we combined mitochondrial DNA barcodes, ultraconserved elements (UCEs), morphological and natural history data to delimit putative species. Using these results, we generate the first large‐scale assessment of ecological specialization and host association in this species‐rich group, with implications for evolutionary ecology and biocontrol. We find most Sycophila target specific subsets of available cynipid host galls with similar morphologies, and generally attack larger galls. Our results suggest that parasitoid wasps such as Sycophila have adaptations allowing them to exploit particular host trait combinations, while hosts with contrasting traits are resistant to attack. These findings support the tritrophic niche concept for the structuring of plant–herbivore–parasitoid communities.

Spatial compositional turnover varies with trophic level and body size in marine assemblages of micro‐ and macroorganisms - Amanda K. Pettersen; Melinda A. Coleman; Guillaume Latombe; Sebastian Vadillo Gonzalez; Nathan L. R. Williams; Justin R. Seymour; Alexandra H. Campbell; Torsten Thomas; Renata Ferrari; Rick D. Stuart‐Smith; Graham J. Edgar; Peter D. Steinberg; et al. (Global Ecology and Biogeography, 2022)
Aim Spatial compositional turnover varies considerably among co‐occurring assemblages of organisms, presumably shaped by common processes related to species traits. We investigated patterns of spatial turnover in a diverse set of marine assemblages using zeta diversity, which extends traditional pairwise measures of turnover to capture the roles of both rare and common species in shaping assemblage turnover. We tested the generality of hypothesized patterns related to ecological traits and provide insights into mechanisms of biodiversity change. Location Temperate pelagic and benthic marine assemblages of micro‐ and macroorganisms along south‐eastern Australia (30–36° S latitude). Time period 2008–2021. Major taxa studied Bacteria, phytoplankton, zooplankton, fish, and macrobenthic groups. Methods Six marine datasets spanning bacteria to fishes were collated for measures of “species” occurrence, with a 1° latitude grain. For each assemblage, ecological traits of body size, habitat and trophic level were analysed for the form and rate of decline in zeta diversity and for the species retention rate. Results Species at higher trophic levels showed two to three times the rate of zeta diversity decline compared with lower trophic levels, indicating an increase in turnover from phytoplankton to carnivorous fishes. Body size showed the hypothesized unimodal relationship with rates of turnover for macroorganisms. Patterns of bacterial turnover contrasted with those found for macroorganisms, with the highest levels of turnover in pelagic habitats compared with benthic (kelp‐associated) habitats. The shape of retention rate curves showed the importance of both rare and common species in driving turnover; a finding that would not have been observable using pairwise (beta diversity) measures of turnover. Main conclusions Our results support theoretical predictions for phytoplankton and macroorganisms, showing an increase in turnover rate with trophic level, but these predictions did not hold for bacteria. Such deviations from theory need to be investigated further to identify underlying processes that govern microbial assemblage dynamics.

Disease surveillance by artificial intelligence links eelgrass wasting disease to ocean warming across latitudes - Lillian R. Aoki; Brendan Rappazzo; Deanna S. Beatty; Lia K. Domke; Ginny L. Eckert; Morgan E. Eisenlord; Olivia J. Graham; Leah Harper; Timothy L. Hawthorne; Margot Hessing‐Lewis; Kevin A. Hovel; Zachary L. Monteith; et al. (Limnology and Oceanography, 2022)
Ocean warming endangers coastal ecosystems through increased risk of infectious disease, yet detection, surveillance, and forecasting of marine diseases remain limited. Eelgrass ( Zostera marina ) meadows provide essential coastal habitat and are vulnerable to a temperature‐sensitive wasting disease caused by the protist Labyrinthula zosterae . We assessed wasting disease sensitivity to warming temperatures across a 3500 km study range by combining long‐term satellite remote sensing of ocean temperature with field surveys from 32 meadows along the Pacific coast of North America in 2019. Between 11% and 99% of plants were infected in individual meadows, with up to 35% of plant tissue damaged. Disease prevalence was 3× higher in locations with warm temperature anomalies in summer, indicating that the risk of wasting disease will increase with climate warming throughout the geographic range for eelgrass. Large‐scale surveys were made possible for the first time by the Eelgrass Lesion Image Segmentation Application, an artificial intelligence (AI) system that quantifies eelgrass wasting disease 5000× faster and with comparable accuracy to a human expert. This study highlights the value of AI in marine biological observing specifically for detecting widespread climate‐driven disease outbreaks.

Managing fisheries for maximum nutrient yield - James P.W. Robinson; Kirsty L. Nash; Julia L. Blanchard; Nis S. Jacobsen; Eva Maire; Nicholas A.J. Graham; M. Aaron MacNeil; Jessica Zamborain‐Mason; Edward H. Allison; Christina C. Hicks (Fish and Fisheries, 2022)
Wild‐caught fish are a bioavailable source of nutritious food that, if managed strategically, could enhance diet quality for billions of people. However, optimising nutrient production from the sea has not been a priority, hindering development of nutrition‐sensitive policies. With fisheries management increasingly effective at rebuilding stocks and regulating sustainable fishing, we can now begin to integrate nutritional outcomes within existing management frameworks. Here, we develop a conceptual foundation for managing fisheries for multispecies Maximum Nutrient Yield (mMNY). We empirically test our approach using size‐based models of North Sea and Baltic Sea fisheries and show that mMNY is predicted by the relative contribution of nutritious species to total catch and their vulnerability to fishing, leading to trade‐offs between catch and specific nutrients. Simulated nutrient yield curves suggest that vitamin D, which is deficient in Northern European diets, was underfished at fishing levels that returned maximum catch weights. Analysis of global catch data shows there is scope for nutrient yields from most of the world's marine fisheries to be enhanced through nutrient‐sensitive fisheries management. With nutrient composition data now widely available, we expect our mMNY framework to motivate development of nutrient‐based reference points in specific contexts, such as data‐limited fisheries. Managing for mMNY alongside policies that promote access to fish could help close nutrient gaps for coastal populations, maximising the contribution of wild‐caught fish to global food and nutrition security.

Persistent viral RNA shedding of SARS-CoV-2 is associated with delirium incidence and six-month mortality in hospitalized COVID-19 patients - Ayush Batra; Jeffrey R. Clark; Anthony K. Kang; Sareen Ali; Tulsi R. Patel; Nathan A. Shlobin; Steven C. Hoffman; Patrick H. Lim; Zachary S. Orban; Lavanya Visvabharathy; Edith L. Graham; David P. Sullivan; et al. (GeroScience, 2022)

Physical activity and glioma: a case–control study with follow-up for survival - Zohreh Basiri; Yi Yang; Fiona J. Bruinsma; Anna K. Nowak; Kerrie L. McDonald; Katharine J. Drummond; Mark A. Rosenthal; Eng-Siew Koh; Rosemary Harrup; Elizabeth Hovey; David Joseph; Geza Benke; et al. (Cancer Causes & Control, 2022)
Purpose High-grade disease accounts for ~ 70% of all glioma, and has a high mortality rate. Few modifiable exposures are known to be related to glioma risk or mortality. Methods We examined associations between lifetime physical activity and physical activity at different ages (15–18 years, 19–29 years, 30–39 years, last 10 years) with the risk of glioma diagnosis, using data from a hospital-based family case–control study (495 cases; 371 controls). We followed up cases over a median of 25 months to examine whether physical activity was associated with all-cause mortality. Physical activity and potential confounders were assessed by self-administered questionnaire. We examined associations between physical activity (metabolic equivalent [MET]-h/wk) and glioma risk using unconditional logistic regression and with all-cause mortality in cases using Cox regression. Results We noted a reduced risk of glioma for the highest (≥ 47 MET-h/wk) versus lowest (< 24 METh/wk) category of physical activity for lifetime activity (OR = 0.58, 95% CI: 0.38–0.89) and at 15–18 years (OR = 0.57, 95% CI: 0.39–0.83). We did not observe any association between physical activity and all-cause mortality (HR for lifetime physical activity = 0.91, 95% CI: 0.64–1.29). Conclusion Our findings are consistent with previous research that suggested physical activity during adolescence might be protective against glioma. Engaging in physical activity during adolescence has many health benefits; this health behavior may also offer protection against glioma.

Invasive bumble bee disrupts a pollination mutualism over space and time - V. R. Chalcoff; Y. Sasal; L. E. Graham; D. P. Vázquez; C. L. Morales (Biological Invasions, 2022)

Zircons from the Wambidgee Serpentinite Belt, southern Lachlan Orogen: evidence for oceanic crust at the Cambrian–Ordovician boundary - E. A. Belousova; I. T. Graham; R. A. Glen; W. L. Griffin; L. Martin (Australian Journal of Earth Sciences, 2022)

Correction to: Retinoid X Receptor: Cellular and Biochemical Roles of Nuclear Receptor with a Focus on Neuropathological Involvement - Samridhi Sharma; Ting Shen; Nitin Chitranshi; Veer Gupta; Devaraj Basavarajappa; Soumalya Sarkar; Mehdi Mirzaei; Yuyi You; Wojciech Krezel; Stuart L. Graham; Vivek Gupta (Molecular Neurobiology, 2022)

Retinoid X Receptor: Cellular and Biochemical Roles of Nuclear Receptor with a Focus on Neuropathological Involvement - Samridhi Sharma; Ting Shen; Nitin Chitranshi; Veer Gupta; Devaraj Basavarajappa; Soumalya Sarkar; Mehdi Mirzaei; Yuyi You; Wojciech Krezel; Stuart L. Graham; Vivek Gupta (Molecular Neurobiology, 2022)
Retinoid X receptors (RXRs) present a subgroup of the nuclear receptor superfamily with particularly high evolutionary conservation of ligand binding domain. The receptor exists in α, β, and γ isotypes that form homo-/heterodimeric complexes with other permissive and non-permissive receptors. While research has identified the biochemical roles of several nuclear receptor family members, the roles of RXRs in various neurological disorders remain relatively under-investigated. RXR acts as ligand-regulated transcription factor, modulating the expression of genes that plays a critical role in mediating several developmental, metabolic, and biochemical processes. Cumulative evidence indicates that abnormal RXR signalling affects neuronal stress and neuroinflammatory networks in several neuropathological conditions. Protective effects of targeting RXRs through pharmacological ligands have been established in various cell and animal models of neuronal injury including Alzheimer disease, Parkinson disease, glaucoma, multiple sclerosis, and stroke. This review summarises the existing knowledge about the roles of RXR, its interacting partners, and ligands in CNS disorders. Future research will determine the importance of structural and functional heterogeneity amongst various RXR isotypes as well as elucidate functional links between RXR homo- or heterodimers and specific physiological conditions to increase drug targeting efficiency in pathological conditions.

Pre-exposure to a variable temperature treatment improves the response of Acropora cervicornis to acute thermal stress - Allyson DeMerlis; Amanda Kirkland; Madeline L. Kaufman; Anderson B. Mayfield; Nathan Formel; Graham Kolodziej; Derek P. Manzello; Diego Lirman; Nikki Traylor-Knowles; Ian C. Enochs (Coral Reefs, 2022)

Joanne Knight Breast Health Cohort at Siteman Cancer Center - Graham A. Colditz; Debbie L. Bennett; Jennifer Tappenden; Courtney Beers; Nicole Ackermann; Ningying Wu; Jingqin Luo; Sarah Humble; Erin Linnenbringer; Kia Davis; Shu Jiang; Adetunji T. Toriola (Cancer Causes & Control, 2022)
Purpose The Joanne Knight Breast Health Cohort was established to link breast cancer risk factors, mammographic breast density, benign breast biopsies and associated tissue markers, and blood markers in a diverse population of women undergoing routine mammographic screening to study risk factors and validate models for breast cancer risk prediction. Methods Women were recruited from November 2008 to April 2012 through the mammography service at the Joanne Knight Breast Health Center at Washington University in St. Louis, Missouri. Baseline questionnaire risk factors, blood, and screening mammograms were collected from 12,153 women. Of these, 1,672 were excluded for prior history of any cancer (except non-melanoma skin) or diagnosis of breast cancer within 6 months of blood draw/registration for the study, for a total of 10,481 women. Follow-up is through linking to electronic health records, tumor registry, and death register. Routine screening mammograms are collected every 1–2 years and incident benign breast biopsies and cancers are identified through record linkage to pathology and tumor registries. Formal fixed tissue samples are retrieved and stored for analysis. County-level measures of structural inequality were derived from publicly available resources. Results Cohort Composition: median age at entry was 54.8 years and 26.7% are African American. Through 2020, 74% of participants have had a medical center visit within the past year and 80% within the past 2 years representing an average of 9.7 person-years of follow-up from date of blood draw per participant. 9,997 women are continuing in follow-up. Data collected at baseline include breast cancer risk factors, plasma and white blood cells, and mammograms prior to baseline, at baseline, and during follow-up. Conclusion This cohort assembled and followed in a routine mammography screening and care setting that serves a diverse population of women in the St. Louis region now provides opportunities to integrate study of questionnaire measures, plasma and DNA markers, benign and malignant tissue markers, and repeated breast image features into prospective evaluation for breast cancer etiology and outcomes.

Effect of expansion of human umbilical cord blood CD34 + cells on neurotrophic and angiogenic factor expression and function - Ashalyn P. Watt; Mark Kirkland; Lakshmi Nekkanti; Yen Pham; Courtney McDonald; Atul Malhotra; Guy Moeneclaey; Suzanne L. Miller; Graham Jenkin (Cell and Tissue Research, 2022)
The use of CD34 + cell-based therapies has largely been focused on haematological conditions. However, there is increasing evidence that umbilical cord blood (UCB) CD34 + -derived cells have neuroregenerative properties. Due to low cell numbers of CD34 + cells present in UCB, expansion is required to produce sufficient cells for therapeutic purposes, especially in adults or when frequent applications are required. However, it is not known whether expansion of CD34 + cells has an impact on their function and neuroregenerative capacity. We addressed this knowledge gap in this study, via expansion of UCB-derived CD34 + cells using combinations of LDL, UM171 and SR-1 to yield large numbers of cells and then tested their functionality. CD34 + cells expanded for 14 days in media containing UM171 and SR-1 resulted in over 1000-fold expansion. The expanded cells showed an up-regulation of the neurotrophic factor genes BDNF, GDNF, NTF-3 and NTF-4, as well as the angiogenic factors VEGF and ANG. In vitro functionality testing showed that these expanded cells promoted angiogenesis and, in brain glial cells, promoted cell proliferation and reduced production of reactive oxygen species (ROS) during oxidative stress. Collectively, this study showed that our 14-day expansion protocol provided a robust expansion that could produce enough cells for therapeutic purposes. These expanded cells, when tested in in vitro, maintained functionality as demonstrated through promotion of cell proliferation, attenuation of ROS production caused by oxidative stress and promotion of angiogenesis.

Tracking the early stages of an invasion with biotelemetry: behaviour of round goby (Neogobius melanostomus) in Canada’s historic Rideau Canal - Jordanna N. Bergman; Graham D. Raby; Kate L. Neigel; Colin D. Rennie; Sigal Balshine; Joseph R. Bennett; Aaron T. Fisk; Steven J. Cooke (Biological Invasions, 2022)

Safeguarding marine life: conservation of biodiversity and ecosystems - Delphi Ward; Jessica Melbourne-Thomas; Gretta T. Pecl; Karen Evans; Madeline Green; Phillipa C. McCormack; Camilla Novaglio; Rowan Trebilco; Narissa Bax; Madeleine J. Brasier; Emma L. Cavan; Graham Edgar; et al. (Reviews in Fish Biology and Fisheries, 2022)
Marine ecosystems and their associated biodiversity sustain life on Earth and hold intrinsic value. Critical marine ecosystem services include maintenance of global oxygen and carbon cycles, production of food and energy, and sustenance of human wellbeing. However marine ecosystems are swiftly being degraded due to the unsustainable use of marine environments and a rapidly changing climate. The fundamental challenge for the future is therefore to safeguard marine ecosystem biodiversity, function, and adaptive capacity whilst continuing to provide vital resources for the global population. Here, we use foresighting/hindcasting to consider two plausible futures towards 2030: a business-as-usual trajectory (i.e. continuation of current trends), and a more sustainable but technically achievable future in line with the UN Sustainable Development Goals. We identify key drivers that differentiate these alternative futures and use these to develop an action pathway towards the desirable, more sustainable future. Key to achieving the more sustainable future will be establishing integrative (i.e. across jurisdictions and sectors), adaptive management that supports equitable and sustainable stewardship of marine environments. Conserving marine ecosystems will require recalibrating our social, financial, and industrial relationships with the marine environment. While a sustainable future requires long-term planning and commitment beyond 2030, immediate action is needed to avoid tipping points and avert trajectories of ecosystem decline. By acting now to optimise management and protection of marine ecosystems, building upon existing technologies, and conserving the remaining biodiversity, we can create the best opportunity for a sustainable future in 2030 and beyond.

Connecting to the oceans: supporting ocean literacy and public engagement - Rachel Kelly; Karen Evans; Karen Alexander; Silvana Bettiol; Stuart Corney; Coco Cullen-Knox; Christopher Cvitanovic; Kristy de Salas; Gholam Reza Emad; Liam Fullbrook; Carolina Garcia; Sierra Ison; et al. (Reviews in Fish Biology and Fisheries, 2022)

Intradialytic cycling does not exacerbate microparticles or circulating markers of systemic inflammation in haemodialysis patients - Patrick J. Highton; Daniel S. March; Darren R. Churchward; Charlotte E. Grantham; Hannah M. L. Young; Matthew P. M. Graham-Brown; Seila Estruel; Naomi Martin; Nigel J. Brunskill; Alice C. Smith; James O. Burton; Nicolette C. Bishop (European Journal of Applied Physiology, 2022)
Purpose Patients receiving haemodialysis (HD) display elevated circulating microparticle (MP) concentration, tissue factor (TF) expression and markers of systemic inflammation, though regular intradialytic cycling (IDC) may have a therapeutic effect. This study investigated the impact of regular, moderate-intensity IDC on circulating MPs and inflammatory markers in unit-based HD patients. Methods Patients were cluster-randomised to intervention ( n = 20, age: 51.4 ± 18.1 years, body mass: 77.6 ± 18.3 kg, mean ± SD) or no-exercise control ( n = 20, 56.8 ± 14.0 years, 80.5 ± 26.5 kg). Intervention participants completed 30 min of moderate intensity (rating of perceived exertion [RPE] of 12–14) IDC, thrice weekly for 6 months. Pre-dialysis venous blood samples were obtained at 0, 3 and 6 months. Circulating MP phenotypes, cytokines, chemokine and MP TF expression were quantified using flow cytometry and cytometric bead array assays. Results Despite high exercise compliance (82%), no IDC-dependent effects were observed for any MP, cytokine or chemokine measure ( p ≥ 0.051, η ρ 2 ≤ 0.399) other than TNF-α ( p = 0.001, η ρ 2 = 0.186), though no significance was revealed upon post hoc analysis. Conclusion Six months of regular, moderate-intensity IDC had no effect on MPs, cytokines or chemokines. This suggests that the exercise did not exacerbate thrombotic or inflammatory status, though further functional assays are required to confirm this. Trial registration ISRCTN1129707, prospectively registered on 05/03/2015.

Attributing Controlling Factors of Acidification and Hypoxia in a Deep, Nutrient-Enriched Estuarine Embayment - John R. Zeldis; Kim I. Currie; Scott L. Graham; Mark P. Gall (Frontiers in Marine Science, 2022)
Measuring and attributing controlling factors of acidification and hypoxia are essential for management of coastal ecosystems affected by those stressors. We address this using surveys in the Firth of Thames, a deep, seasonally stratified estuarine embayment adjoing the Hauraki Gulf in northern Aotearoa/New Zealand. The Firth’s catchment has undergone historic land-use intensification transforming it from native forest cover to dominance by pastoral use, increasing its riverine total nitrogen loading by ∼82% over natural levels and switching it’s predominate loading source from offshore to the catchment. We hypothesised that seasonal variation in net ecosystem metabolism [NEM: dissolved inorganic carbon (DIC) uptake/release] will be a primary factor determining carbonate and oxic responses in the Firth, and that organic matter involved in the metabolism will originate primarily by fixation within the Firth system and be driven by catchment dissolved inorganic nitrogen (DIN) loading. Seasonal ship-based and biophysical mooring surveys across the Hauraki Gulf and Firth showed depressed pH and O 2 reaching pH ∼7.8 and O 2 ∼4.8 mg L –1 in autumn in the inner Firth, matched by shoreward increasing nutrient loading, phytoplankton, organic matter, gross primary production (GPP) and apparent O 2 utilization. A carbonate system deconvolution of the ship survey data, combined with other ship survey and mooring results, showed how CO 2 partial pressure responded to seasonal shifts in temperature, NEM, phytoplankton sinking and mineralisation and water column stratification, that underlay the late-season expression of acidification and hypoxia. This aligned with seasonal shifts in net DIC fluxes determined in a coincident nutrient mass-balance analysis, showing near-neutral fluxes from spring to summer, but respiratory NEM from summer to autumn. Particulate C:N and ratios of organic C fixed by Firth GPP to that from river inputs (∼29- to 100-fold in summer and autumn) showed that the dominant source of organic matter fuelling heterotrophy in autumn was autochthonous GPP, driven by riverine DIN loading. The results signified the sensitivity of deep, long-residence time, seasonally stratifying estuaries to acidification and hypoxia, and are important for coastal resource management, including aquaculture developments and catchment runoff limit-setting for maintenance of ecosystem health.

Modelling the effects of cold temperature during the reproductive stage on the yield of chickpea (Cicer arietinum L.) - Muhuddin Rajin Anwar; David J. Luckett; Yashvir S. Chauhan; Ryan H. L. Ip; Lancelot Maphosa; Marja Simpson; Annie Warren; Rosy Raman; Mark F. Richards; Georgina Pengilley; Kristy Hobson; Neroli Graham (International Journal of Biometeorology, 2022)
During the reproductive stage, chilling temperatures and frost reduce the yield of chickpea and limit its adaptation. The adverse effects of chilling temperature and frost in terms of the threshold temperatures, impact of cold duration, and genotype-by-environment-by-management interactions are not well quantified. Crop growth models that predict flowering time and yield under diverse climates can identify combinations of cultivars and sowing time to reduce frost risk in target environments. The Agricultural Production Systems Simulator (APSIM-chickpea) model uses daily temperatures to model basic crop growth but does not include penalties for either frost damage or cold temperatures during flowering and podding stages. Regression analysis overcame this limitation of the model for chickpea crops grown at 95 locations in Australia using 70 years of historic data incorporating three cultivars and three sowing times (early, mid, and late). We modified model parameters to include the effect of soil water on thermal time calculations, which significantly improved the prediction of flowering time. Simulated data, and data from field experiments grown in Australia (2013 to 2019), showed robust predictions for flowering time ( n = 29; R 2 = 0.97), and grain yield ( n = 22; R 2 = 0.63–0.70). In addition, we identified threshold cold temperatures that significantly affected predicted yield, and combinations of locations, variety, and sowing time where the overlap between peak cold temperatures and peak flowering was minimal. Our results showed that frost and/or cold temperature–induced yield losses are a major limitation in some unexpected Australian locations, e.g., inland, subtropical latitudes in Queensland. Intermediate sowing maximise yield, as it avoids cold temperature, late heat, and drought stresses potentially limiting yield in early and late sowing respectively.

Body composition of American Woodcock during fall staging: a validation of the non-invasive deuterium dilution method - Clayton L. Graham; Scott R. McWilliams (Journal of Ornithology, 2022)

From anecdotes to quantification: advances in characterizing volcanic eruption impacts on the built environment - Natalia Irma Deligne; Susanna F. Jenkins; Elinor S. Meredith; George T. Williams; Graham S. Leonard; Carol Stewart; Thomas M. Wilson; Sébastien Biass; Daniel M. Blake; Russell J. Blong; Costanza Bonadonna; Rodrigo Calderon B.; et al. (Bulletin of Volcanology, 2022)

Wave exposure shapes reef community composition and recovery trajectories at a remote coral atoll - Ines D. Lange; Cassandra E. Benkwitt; Jamie M. McDevitt-Irwin; Kristina L. Tietjen; Brett Taylor; Mark Chinkin; Rachel L. Gunn; Melissa Palmisciano; Margaux Steyaert; Bry Wilson; Holly K. East; John Turner; et al. (Coral Reefs, 2021)
In a time of unprecedented ecological change, understanding natural biophysical relationships between reef resilience and physical drivers is of increasing importance. This study evaluates how wave forcing structures coral reef benthic community composition and recovery trajectories after the major 2015/2016 bleaching event in the remote Chagos Archipelago, Indian Ocean. Benthic cover and substrate rugosity were quantified from digital imagery at 23 fore reef sites around a small coral atoll (Salomon) in 2020 and compared to data from a similar survey in 2006 and opportunistic surveys in intermediate years. Cluster analysis and principal component analysis show strong separation of community composition between exposed (modelled wave exposure > 1000 J m −3 ) and sheltered sites (< 1000 J m −3 ) in 2020. This difference is driven by relatively high cover of Porites sp., other massive corals, encrusting corals, soft corals, rubble and dead table corals at sheltered sites versus high cover of pavement and sponges at exposed sites. Total coral cover and rugosity were also higher at sheltered sites. Adding data from previous years shows benthic community shifts from distinct exposure-driven assemblages and high live coral cover in 2006 towards bare pavement, dead Acropora tables and rubble after the 2015/2016 bleaching event. The subsequent recovery trajectories at sheltered and exposed sites are surprisingly parallel and lead communities towards their respective pre-bleaching communities. These results demonstrate that in the absence of human stressors, community patterns on fore reefs are strongly controlled by wave exposure, even during and after widespread coral loss from bleaching events.

Phytoplankton and cyanobacteria abundances in mid‐21st century lakes depend strongly on future land use and climate projections - Karan Kakouei; Benjamin M. Kraemer; Orlane Anneville; Laurence Carvalho; Heidrun Feuchtmayr; Jennifer L. Graham; Scott Higgins; Francesco Pomati; Lars G. Rudstam; Jason D. Stockwell; Stephen J. Thackeray; Michael J. Vanni; et al. (Global Change Biology, 2021)
Land use and climate change are anticipated to affect phytoplankton of lakes worldwide. The effects will depend on the magnitude of projected land use and climate changes and lake sensitivity to these factors. We used random forests fit with long‐term (1971–2016) phytoplankton and cyanobacteria abundance time series, climate observations (1971–2016), and upstream catchment land use (global Clumondo models for the year 2000) data from 14 European and 15 North American lakes basins. We projected future phytoplankton and cyanobacteria abundance in the 29 focal lake basins and 1567 lakes across focal regions based on three land use (sustainability, middle of the road, and regional rivalry) and two climate (RCP 2.6 and 8.5) scenarios to mid‐21st century. On average, lakes are expected to have higher phytoplankton and cyanobacteria due to increases in both urban land use and temperature, and decreases in forest habitat. However, the relative importance of land use and climate effects varied substantially among regions and lakes. Accounting for land use and climate changes in a combined way based on extensive data allowed us to identify urbanization as the major driver of phytoplankton development in lakes located in urban areas, and climate as major driver in lakes located in remote areas where past and future land use changes were minimal. For approximately one‐third of the studied lakes, both drivers were relatively important. The results of this large scale study suggest the best approaches for mitigating the effects of human activity on lake phytoplankton and cyanobacteria will depend strongly on lake sensitivity to long‐term change and the magnitude of projected land use and climate changes at a given location. Our quantitative analyses suggest local management measures should focus on retaining nutrients in urban landscapes to prevent nutrient pollution from exacerbating ongoing changes to lake ecosystems from climate change.

Reef communities show predictable undulations in linear abundance size spectra from copepods to sharks - Freddie J. Heather; Rick D. Stuart‐Smith; Julia L. Blanchard; Kate M. Fraser; Graham J. Edgar (Ecology Letters, 2021)
Among the more widely accepted general hypotheses in ecology is that community relationships between abundance and body size follow a log‐linear size spectrum, from the smallest consumers to the largest predators (i.e. ‘bacteria to whales’). Nevertheless, most studies only investigate small subsets of this spectrum, and note that extreme size classes in survey data deviate from linear expectations. In this study, we fit size spectra to field data from 45 rocky and coral reef sites along a 28° latitudinal gradient, comprising individuals from 0.125 mm to 2 m in body size. We found that 96% of the variation in abundance along this ‘extended’ size gradient was described by a single linear function across all sites. However, consistent ‘wobbles’ were also observed, with subtle peaks and troughs in abundance along the spectrum, which varied with sea temperature, as predicted by theory relating to trophic cascades.

Climate warming threatens the persistence of a community of disturbance‐adapted native annual plants - Paul B. Reed; Scott D. Bridgham; Laurel E. Pfeifer‐Meister; Megan L. DeMarche; Bart R. Johnson; Bitty A. Roy; Graham T. Bailes; Aaron A. Nelson; William F. Morris; Daniel F. Doak (Ecology, 2021)
With ongoing climate change, populations are expected to exhibit shifts in demographic performance that will alter where a species can persist. This presents unique challenges for managing plant populations and may require ongoing interventions, including in situ management or introduction into new locations. However, few studies have examined how climate change may affect plant demographic performance for a suite of species, or how effective management actions could be in mitigating climate change effects. Over the course of two experiments spanning 6 yr and four sites across a latitudinal gradient in the Pacific Northwest, United States, we manipulated temperature, precipitation, and disturbance intensity, and quantified effects on the demography of eight native annual prairie species. Each year we planted seeds and monitored germination, survival, and reproduction. We found that disturbance strongly influenced demographic performance and that seven of the eight species had increasingly poor performance with warmer conditions. Across species and sites, we observed 11% recruitment (the proportion of seeds planted that survived to reproduction) following high disturbance, but just 3.9% and 2.3% under intermediate and low disturbance, respectively. Moreover, mean seed production following high disturbance was often more than tenfold greater than under intermediate and low disturbance. Importantly, most species exhibited precipitous declines in their population growth rates (λ) under warmer‐than‐ambient experimental conditions and may require more frequent disturbance intervention to sustain populations. Aristida oligantha , a C4 grass, was the only species to have λ increase with warmer conditions. These results suggest that rising temperatures may cause many native annual plant species to decline, highlighting the urgency for adaptive management practices that facilitate their restoration or introduction to newly suitable locations. Frequent and intense disturbances are critical to reduce competitors and promote native annuals’ persistence, but even such efforts may prove futile under future climate regimes.

Pliocene origins, Pleistocene refugia, and postglacial range expansions in southern devil scorpions (Vaejovidae: Vaejovis carolinianus) - Matthew R. Graham; Erika L. Garcia; Brent E. Hendrixson; Alyssa M. Sampognaro; Paula E. Cushing (Organisms Diversity & Evolution, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Far-Field Effects of Impulsive Noise on Coastal Bottlenose Dolphins - Oihane Fernandez-Betelu; Isla M. Graham; Kate L. Brookes; Barbara J. Cheney; Tim R. Barton; Paul M. Thompson (Frontiers in Marine Science, 2021)
Increasing levels of anthropogenic underwater noise have caused concern over their potential impacts on marine life. Offshore renewable energy developments and seismic exploration can produce impulsive noise which is especially hazardous for marine mammals because it can induce auditory damage at shorter distances and behavioral disturbance at longer distances. However, far-field effects of impulsive noise remain poorly understood, causing a high level of uncertainty when predicting the impacts of offshore energy developments on marine mammal populations. Here we used a 10-year dataset on the occurrence of coastal bottlenose dolphins over the period 2009–2019 to investigate far-field effects of impulsive noise from offshore activities undertaken in three different years. Activities included a 2D seismic survey and the pile installation at two offshore wind farms, 20–75 km from coastal waters known to be frequented by dolphins. We collected passive acoustic data in key coastal areas and used a Before-After Control-Impact design to investigate variation in dolphin detections in areas exposed to different levels of impulsive noise from these offshore activities. We compared dolphin detections at two temporal scales, comparing years and days with and without impulsive noise. Passive acoustic data confirmed that dolphins continued to use the impact area throughout each offshore activity period, but also provided evidence of short-term behavioral responses in this area. Unexpectedly, and only at the smallest temporal scale, a consistent increase in dolphin detections was observed at the impact sites during activities generating impulsive noise. We suggest that this increase in dolphin detections could be explained by changes in vocalization behavior. Marine mammal protection policies focus on the near-field effects of impulsive noise; however, our results emphasize the importance of investigating the far-field effects of anthropogenic disturbances to better understand the impacts of human activities on marine mammal populations.

In silico analysis revealing CsrA roles in motility-sessility switching and tuning VBNC cells in Vibrio parahaemolyticus - Dan Wang; Steve H. Flint; Dragana Gagic; Jon S. Palmer; Graham C. Fletcher; Stephen L. W. On (Biofouling, 2021)

FRAMe: Familial Risk Assessment of Melanoma—a risk prediction tool to guide CDKN2A germline mutation testing in Australian familial melanoma - Elizabeth A. Holland; Serigne Lo; Blake Kelly; Helen Schmid; Anne E. Cust; Jane M. Palmer; Martin Drummond; Nicholas K. Hayward; Antonia L. Pritchard; Graham J. Mann (Familial Cancer, 2021)

Traits related to efficient acquisition and use of phosphorus promote diversification in Proteaceae in phosphorus‐impoverished landscapes - Patrick E. Hayes; Francis J. Nge; Michael D. Cramer; Patrick M. Finnegan; Peili Fu; Stephen D. Hopper; Rafael S. Oliveira; Benjamin L. Turner; Graham Zemunik; Hongtao Zhong; Hans Lambers (Plant and Soil, 2021)

The extent and variability of storm‐induced temperature changes in lakes measured with long‐term and high‐frequency data - Jonathan P. Doubek; Orlane Anneville; Gaël Dur; Aleksandra M. Lewandowska; Vijay P. Patil; James A. Rusak; Nico Salmaso; Christian Torsten Seltmann; Dietmar Straile; Pablo Urrutia‐Cordero; Patrick Venail; Rita Adrian; et al. (Limnology and Oceanography, 2021)
The intensity and frequency of storms are projected to increase in many regions of the world because of climate change. Storms can alter environmental conditions in many ecosystems. In lakes and reservoirs, storms can reduce epilimnetic temperatures from wind‐induced mixing with colder hypolimnetic waters, direct precipitation to the lake's surface, and watershed runoff. We analyzed 18 long‐term and high‐frequency lake datasets from 11 countries to assess the magnitude of wind‐ vs. rainstorm‐induced changes in epilimnetic temperature. We found small day‐to‐day epilimnetic temperature decreases in response to strong wind and heavy rain during stratified conditions. Day‐to‐day epilimnetic temperature decreased, on average, by 0.28°C during the strongest windstorms (storm mean daily wind speed among lakes: 6.7 ± 2.7 m s −1 , 1 SD) and by 0.15°C after the heaviest rainstorms (storm mean daily rainfall: 21.3 ± 9.0 mm). The largest decreases in epilimnetic temperature were observed ≥2 d after sustained strong wind or heavy rain (top 5 th percentile of wind and rain events for each lake) in shallow and medium‐depth lakes. The smallest decreases occurred in deep lakes. Epilimnetic temperature change from windstorms, but not rainstorms, was negatively correlated with maximum lake depth. However, even the largest storm‐induced mean epilimnetic temperature decreases were typically

A shift from phenol to silica‐based leaf defences during long‐term soil and ecosystem development - Felix de Tombeur; Etienne Laliberté; Hans Lambers; Michel‐Pierre Faucon; Graham Zemunik; Benjamin L. Turner; Jean‐Thomas Cornelis; Grégory Mahy (Ecology Letters, 2021)
The resource availability hypothesis predicts that plants adapted to infertile soils have high levels of anti‐herbivore leaf defences. This hypothesis has been mostly explored for secondary metabolites such as phenolics, whereas it remains underexplored for silica‐based defences. We determined leaf concentrations of total phenols and silicon (Si) in plants growing along the 2‐million‐year Jurien Bay chronosequence, exhibiting an extreme gradient of soil fertility. We found that nitrogen (N) limitation on young soils led to a greater expression of phenol‐based defences, whereas old, phosphorus (P)‐impoverished soils favoured silica‐based defences. Both defence types were negatively correlated at the community and individual species level. Our results suggest a trade‐off among these two leaf defence strategies based on the strength and type of nutrient limitation, thereby opening up new perspectives for the resource availability hypothesis and plant defence research. This study also highlights the importance of silica‐based defences under low P supply.

Creating leadership collectives for sustainability transformations - O. Care; M. J. Bernstein; M. Chapman; I. Diaz Reviriego; G. Dressler; M. R. Felipe-Lucia; C. Friis; S. Graham; H. Hänke; L. J. Haider; M. Hernández-Morcillo; H. Hoffmann; et al. (Sustainability Science, 2021)
Enduring sustainability challenges requires a new model of collective leadership that embraces critical reflection, inclusivity and care. Leadership collectives can support a move in academia from metrics to merits, from a focus on career to care, and enact a shift from disciplinary to inter- and trans-disciplinary research. Academic organisations need to reorient their training programs, work ethics and reward systems to encourage collective excellence and to allow space for future leaders to develop and enact a radically re-imagined vision of how to lead as a collective with care for people and the planet.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Globally consistent reef size spectra integrating fishes and invertebrates - Freddie J. Heather; Julia L. Blanchard; Graham J. Edgar; Rowan Trebilco; Rick D. Stuart‐Smith (Ecology Letters, 2021)
The frequency distribution of individual body sizes in animal communities (i.e. the size spectrum) provides powerful insights for understanding the energy flux through food webs. However, studies of size spectra in rocky and coral reef communities typically focus only on fishes or invertebrates due to taxonomic and data constraints, and consequently ignore energy pathways involving the full range of macroscopic consumer taxa. We analyse size spectra with co‐located fish and mobile macroinvertebrate data from 3369 reef sites worldwide, specifically focusing on how the addition of invertebrate data alters patterns. The inclusion of invertebrates steepens the size spectrum, more so in temperate regions, resulting in a consistent size spectrum slope across latitudes, and bringing slopes closer to theoretical expectations based on energy flow through the system. These results highlight the importance of understanding contributions of both invertebrates and fishes to reef food webs worldwide.

Lung abnormalities do not influence aerobic capacity in school children born preterm - Christopher A. O’Dea; Karla Logie; Andrew C. Wilson; J. Jane Pillow; Conor Murray; Georgia Banton; Shannon J. Simpson; Graham L. Hall; Andrew Maiorana (European Journal of Applied Physiology, 2021)

Caught in a bottleneck: Habitat loss for woolly mammoths in central North America and the ice‐free corridor during the last deglaciation - Yue Wang; Chris Widga; Russell W. Graham; Jenny L. McGuire; Warren Porter; David Wårlind; John W. Williams (Global Ecology and Biogeography, 2021)
Aim Identifying how climate change, habitat loss, and corridors interact to influence species survival or extinction is critical to understanding macro‐scale biodiversity dynamics under changing environments. In North America, the ice‐free corridor was the only major pathway for northward migration by megafaunal species during the last deglaciation. However, the timing and interplay among the late Quaternary megafaunal extinctions, climate change, habitat structure, and the opening and reforestation of the ice‐free corridor have been unclear. Location North America. Time period 15–10 ka. Major taxa studied Woolly mammoth ( Mammuthus primigenius ). Methods For central North America and the ice‐free corridor between 15 and 10 ka, we used a series of models and continental‐scale datasets to reconstruct habitat characteristics and assess habitat suitability. The models and datasets include biophysical and statistical niche models Niche Mapper and Maxent, downscaled climate simulations from CCSM3 SynTraCE, LPJ‐GUESS simulations of net primary productivity (NPP) and woody cover, and woody cover based upon fossil pollen from Neotoma. Results The ice‐free corridor may have been of limited suitability for traversal by mammoths and other grazers due to persistently low productivity by herbaceous plants and quick reforestation after opening 14 ka. Simultaneously, rapid reforestation and decreased forage productivity may have led to declining habitat suitability in central North America. This was possibly amplified by a positive feedback loop driven by reduced herbivory pressures, as mammoth population decline led to the further loss of open habitat. Main conclusions Declining habitat availability south of the Laurentide Ice Sheet and limited habitat availability in the ice‐free corridor were contributing factors in North American extinctions of woolly mammoths and other large grazers that likely operated synergistically with anthropogenic pressures. The role of habitat loss and attenuated corridor suitability for the woolly mammoth extinction reinforce the critical importance of protected habitat connectivity during changing climates, particularly for large vertebrates.

Drivers of deforestation and degradation for 28 tropical conservation landscapes - H. Manjari Jayathilake; Graham W. Prescott; L. Roman Carrasco; Madhu Rao; William S. Symes (Ambio, 2021)

Legacy Effects of Russian Olive (Elaeagnus angustifolia L.) in a Riparian Ecosystem Three Years Post-Removal - Gabrielle L. Katz; Graham M. Tuttle; Michael W. Denslow; Andrew P. Norton (Wetlands, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Caveolin-1 Ablation Imparts Partial Protection Against Inner Retinal Injury in Experimental Glaucoma and Reduces Apoptotic Activation - Mojdeh Abbasi; Vivek K. Gupta; Nitin Chitranshi; Veer B. Gupta; Mehdi Mirzaei; Yogita Dheer; Linda Garthwaite; Thiri Zaw; Robert G. Parton; Yuyi You; Stuart L. Graham (Molecular Neurobiology, 2020)

Toxic effects of soil manganese on tropical trees - Graham Zemunik; Klaus Winter; Benjamin L. Turner (Plant and Soil, 2020)

Accelerated Forced Degradation of Therapeutic Peptides in Levitated Microdroplets - Yangjie Li; Yanyang Hu; David L. Logsdon; Yong Liu; Yuejie Zhao; R. Graham Cooks (Pharmaceutical Research, 2020)

Differences in cancer survival by remoteness of residence: an analysis of data from a population-based cancer registry - Nina Afshar; Dallas R. English; James A. Chamberlain; Tony Blakely; Vicky Thursfield; Helen Farrugia; Graham G. Giles; Roger L. Milne (Cancer Causes & Control, 2020)

Mismatch repair gene pathogenic germline variants in a population-based cohort of breast cancer - Tu Nguyen-Dumont; Jason A. Steen; Ingrid Winship; Daniel J. Park; Bernard J. Pope; Fleur Hammet; Maryam Mahmoodi; Helen Tsimiklis; Derrick Theys; Mark Clendenning; Graham G. Giles; John L. Hopper; et al. (Familial Cancer, 2020)

Oophila is monophyletic within a three-taxon eukaryotic microbiome in egg masses of the salamander Ambystoma maculatum - E. Jurga; L. Graham; C.D. Bishop (Symbiosis, 2020)

Horizon scanning for South African biodiversity: A need for social engagement as well as science - Colleen L. Seymour; Lindsey Gillson; Matthew F. Child; Krystal A. Tolley; Jock C. Curie; Jessica M. da Silva; Graham J. Alexander; Pippin Anderson; Colleen T. Downs; Benis N. Egoh; David A. Ehlers Smith; Yvette C. Ehlers Smith; et al. (Ambio, 2020)

A comparison of neutral genetic differentiation and genetic diversity among migratory and resident populations of Golden-crowned-Kinglets (Regulus satrapa) - B. A. Graham; A. M. Carpenter; V. L. Friesen; T. M. Burg (Journal of Ornithology, 2020)

Carbon on the Northwest European Shelf: Contemporary Budget and Future Influences - Oliver Legge; Martin Johnson; Natalie Hicks; Tim Jickells; Markus Diesing; John Aldridge; Julian Andrews; Yuri Artioli; Dorothee C. E. Bakker; Michael T. Burrows; Nealy Carr; Gemma Cripps; et al. (Frontiers in Marine Science, 2020)

Cheetah communication at scent-marking sites can be inhibited or delayed by predators - Kristina L. Cornhill; Graham I. H. Kerley (Behavioral Ecology and Sociobiology, 2020)

Triassic to Neogene tectono-magmatic events within Lorne Basin evolution, coastal New South Wales, eastern Australia - F. L. Sutherland; I. T. Graham; H. Zwingmann; D. J. Och; C. J. Gardner; R. E. Pogson; R. J. Griffiths; A. Lay (Australian Journal of Earth Sciences, 2020)

Microbial genomes retrieved from High Arctic lake sediments encode for adaptation to cold and oligotrophic environments - Matti O. Ruuskanen; Graham Colby; Kyra A. St.Pierre; Vincent L. St.Louis; Stéphane Aris‐Brosou; Alexandre J. Poulain (Limnology and Oceanography, 2020)
The Arctic is currently warming at an unprecedented rate, which may affect environmental constraints on the freshwater microbial communities found there. Yet, our knowledge of the community structure and functional potential of High Arctic freshwater microbes remains poor, even though they play key roles in nutrient cycling and other ecosystem services. Here, using high‐throughput metagenomic sequencing and genome assembly, we show that sediment microbial communities in the High Arctic's largest lake by volume, Lake Hazen, are phylogenetically diverse, ranging from Proteobacteria, Verrucomicrobia, Planctomycetes, to members of the newly discovered Candidate Phyla Radiation groups. These genomes displayed a high prevalence of pathways involved in lipid chemistry, and a low prevalence of nutrient uptake pathways, which might represent adaptations to the specific, cold (∼ 3.5°C) and extremely oligotrophic conditions in Lake Hazen. Despite these potential adaptations, it is unclear how ongoing environmental changes will affect microbial communities, the makeup of their genomic idiosyncrasies, as well as the possible implications at higher trophic levels.

Body size and dietary risk factors for aggressive prostate cancer: a case–control study - Mikaela Pal; Allison M. Hodge; Nathan Papa; Robert J. MacInnis; Julie K. Bassett; Damien Bolton; Ian D. Davis; Jeremy Millar; Dallas R. English; John L. Hopper; Gianluca Severi; Melissa C. Southey; et al. (Cancer Causes & Control, 2019)

Skeletal muscle fibre swelling contributes to force depression in rats and humans: a mechanically-skinned fibre study - Daiki Watanabe; Travis L. Dutka; Cedric R. Lamboley; Graham D. Lamb (Journal of Muscle Research and Cell Motility, 2019)

Age and composition of dykes emplaced before and during the opening of the Tasman Sea—source implications - R. Offler; H. Zwingmann; J. Foden; F. L. Sutherland; I. T. Graham (Australian Journal of Earth Sciences, 2019)

Seasonal changes in basking shark vertical space use in the north-east Atlantic - P. D. Doherty; J. M. Baxter; B. J. Godley; R. T. Graham; G. Hall; J. Hall; L. A. Hawkes; S. M. Henderson; L. Johnson; C. Speedie; M. J. Witt (Marine Biology, 2019)
Mobile marine species can exhibit vast movements both horizontally and vertically. Spatial analysis of vertical movements may help improve an understanding of the processes that influence space use. Previously, vertical space use of basking sharks ( Cetorhinus maximus ) in the north-east Atlantic described movements largely within waters of the continental shelf during summer and autumn months, with few records of detailed vertical behaviour during winter. We use archival satellite telemetry data from 32 basking sharks (12 females, 6 males, and 14 of unknown sex measuring 4–5 m ( n = 6), 5–6 m ( n = 10), 6–7 m ( n = 7), 7–8 m ( n = 8), and 8–9 m ( n = 1) estimated total length) tracked over 4 years (2012–2015). The satellite tags provided depth and temperature data for a cumulative 4489 days (mean 140 ± 97 days per shark, range 10–292 days) to describe vertical space use and thermal range of basking sharks in the north-east Atlantic. Basking sharks exhibit seasonality in vertical space use, revealing repeated ‘yo-yo’ movement behaviour with periods of occupancy at depths greater than 1000 m in late winter/early spring. Describing seasonal vertical space use in marine megavertebrates can increase knowledge of movements throughout their environment including physiological and morphological constraints to movement, nutrient transfer, and overlap with anthropogenic threats to inform future conservation strategies.

Review of Australian east coast low pressure systems and associated extremes - Andrew J. Dowdy; Acacia Pepler; Alejandro Di Luca; Leone Cavicchia; Graham Mills; Jason P. Evans; Simon Louis; Kathleen L. McInnes; Kevin Walsh (Climate Dynamics, 2019)

Ability of known susceptibility SNPs to predict colorectal cancer risk for persons with and without a family history - Mark A. Jenkins; Aung K. Win; James G. Dowty; Robert J. MacInnis; Enes Makalic; Daniel F. Schmidt; Gillian S. Dite; Mirosl Kapuscinski; Mark Clendenning; Christophe Rosty; Ingrid M. Winship; Jon D. Emery; et al. (Familial Cancer, 2019)

Overexpression of the MYB29 transcription factor affects aliphatic glucosinolate synthesis in Brassica oleracea - Diana L. Zuluaga; Neil S. Graham; Annett Klinder; A. E. Elaine van Ommen Kloeke; Angelo R. Marcotrigiano; Carol Wagstaff; Ruud Verkerk; Gabriella Sonnante; Mark G. M. Aarts (Plant Molecular Biology, 2019)

Snapshot transient absorption spectroscopy: toward in vivo investigations of nonphotochemical quenching mechanisms - Soomin Park; Collin J. Steen; Alexandra L. Fischer; Graham R. Fleming (Photosynthesis Research, 2019)

Upregulation of Proteolytic Pathways and Altered Protein Biosynthesis Underlie Retinal Pathology in a Mouse Model of Alzheimer’s Disease - Mehdi Mirzaei; Kanishka Pushpitha; Liting Deng; Nitin Chitranshi; Veer Gupta; Rashi Rajput; Abu Bakr Mangani; Yogita Dheer; Angela Godinez; Matthew J. McKay; Karthik Kamath; Dana Pascovici; et al. (Molecular Neurobiology, 2019)

Toward more robust plant–soil feedback research: Comment - François P. Teste; Paul Kardol; Benjamin L. Turner; David A. Wardle; Graham Zemunik; Michael Renton; Etienne Laliberté (Ecology, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

A review of the areoligeracean dinoflagellate cyst Cyclonephelium and morphologically similar genera - Robert A. Fensome; Graham L. Williams; Stephanie E. L. Wood; James B. Riding (Palynology, 2019)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Conducting groundwater monitoring studies in Europe for pesticide active substances and their metabolites in the context of Regulation (EC) 1107/2009 - Anne Louise Gimsing; Jutta Agert; Nicole Baran; Arnaud Boivin; Federico Ferrari; Richard Gibson; Lisa Hammond; Florian Hegler; Russell L. Jones; Wolfram König; Jenny Kreuger; Ton van der Linden; et al. (Journal of Consumer Protection and Food Safety, 2019)

Hot and bothered? Associations between temperature and crime in Australia - Heather R. Stevens; Paul J. Beggs; Petra L. Graham; Hsing-Chung Chang (International Journal of Biometeorology, 2019)

Modeling groundwater contaminant transport in the presence of large heterogeneity: a case study comparing MT3D and RWhet - Zhilin Guo; Graham E. Fogg; Mark L. Brusseau; Eric M. LaBolle; Jose Lopez (Hydrogeology Journal, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Lifetime alcohol intake and pancreatic cancer incidence and survival: findings from the Melbourne Collaborative Cohort Study - Harindra Jayasekara; Dallas R. English; Allison M. Hodge; Robin Room; John L. Hopper; Roger L. Milne; Graham G. Giles; Robert J. MacInnis (Cancer Causes & Control, 2019)

Opportunities for better use of collective action theory in research and governance for invasive species management - Sonia Graham; Alexander L. Metcalf; Nicholas Gill; Rebecca Niemiec; Carlo Moreno; Thomas Bach; Victoria Ikutegbe; Lars Hallstrom; Zhao Ma; Alice Lubeck (Conservation Biology, 2019)
Controlling invasive species presents a public‐good dilemma. Although environmental, social, and economic benefits of control accrue to society, costs are borne by only a few individuals and organizations. For decades, policy makers have used incentives and sanctions to encourage or coerce individual actors to contribute to the public good, with limited success. Diverse, subnational efforts to collectively manage invasive plants, insects, and animals provide effective alternatives to traditional command‐and‐control approaches. Despite this work, there has been little systematic evaluation of collective efforts to determine whether there are consistent principles underpinning success. We reviewed 32 studies to identify the extent to which collective‐action theories from related agricultural and environmental fields explain collaborative invasive species management approaches; describe and differentiate emergent invasive species collective‐action efforts; and provide guidance on how to enable more collaborative approaches to invasive species management. We identified 4 types of collective action aimed at invasive species—externally led, community led, comanaged, and organizational coalitions—that provide blueprints for future invasive species management. Existing collective‐action theories could explain the importance attributed to developing shared knowledge of the social‐ecological system and the need for social capital. Yet, collection action on invasive species requires different types of monitoring, sanctions, and boundary definitions. We argue that future government policies can benefit from establishing flexible boundaries that encourage social learning and enable colocated individuals and organizations to identify common goals, pool resources, and coordinate efforts.

Molecular changes to the rat renal cotransporters PEPT1 and PEPT2 due to ageing - Othman A. Alghamdi; Nicola King; Nicholas M. Andronicos; Graham L. Jones; Belal Chami; Paul K. Witting; Pierre D. J. Moens (Molecular and Cellular Biochemistry, 2019)

Presence of an invasive species reverses latitudinal clines of multiple traits in a native species - Christopher J. Thawley; Mark Goldy‐Brown; Gail L. McCormick; Sean P. Graham; Tracy Langkilde (Global Change Biology, 2019)
Understanding the processes driving formation and maintenance of latitudinal clines has become increasingly important in light of accelerating global change. Many studies have focused on the role of abiotic factors, especially temperature, in generating clines, but biotic factors, including the introduction of non‐native species, may also drive clinal variation. We assessed the impact of invasion by predatory fire ants on latitudinal clines in multiple fitness‐relevant traits—morphology, physiological stress responsiveness, and antipredator behavior—in a native fence lizard. In areas invaded by fire ants, a latitudinal cline in morphology is opposite both the cline found in museum specimens from historical populations across the species’ full latitudinal range and that found in current populations uninvaded by fire ants. Similarly, clines in stress‐relevant hormone response to a stressor and in antipredator behavior differ significantly between the portions of the fence lizard range invaded and uninvaded by fire ants. Changes in these traits within fire ant‐invaded areas are adaptive and together support increased and more effective antipredator behavior that allows escape from attacks by this invasive predator. However, these changes may mismatch lizards to the environments under which they historically evolved. This research shows that novel biotic pressures can alter latitudinal clines in multiple traits within a single species on ecological timescales. As global change intensifies, a greater understanding of novel abiotic and biotic pressures and how affected organisms adapt to them across space and time will be central to predicting and managing our changing environment.

Early‐breeding females experience greater telomere loss - Jessica L. Graham; Carolyn M. Bauer; Britt J. Heidinger; Ellen D. Ketterson; Timothy J. Greives (Molecular Ecology, 2019)
Annual reproductive success is often highest in individuals that initiate breeding early, yet relatively few individuals start breeding during this apparently optimal time. This suggests that individuals, particularly females who ultimately dictate when offspring are born, incur costs by initiating reproduction early in the season. We hypothesized that increases in the ageing rate of somatic cells may be one such cost. Telomeres, the repetitive DNA sequences on the ends of chromosomes, may be good proxies of biological wear and tear as they shorten with age and in response to stress. Using historical data from a long‐term study population of dark‐eyed juncos ( Junco hyemalis ), we found that telomere loss between years was greater in earlier breeding females, regardless of chronological age. There was no relationship between telomere loss and the annual number of eggs laid or chicks that reached independence. However, telomere loss was greater when temperatures were cooler, and cooler temperatures generally occur early in the season. This suggests that environmental conditions could be the primary cause of accelerated telomere loss in early breeders.

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

Bexarotene Modulates Retinoid-X-Receptor Expression and Is Protective Against Neurotoxic Endoplasmic Reticulum Stress Response and Apoptotic Pathway Activation - Yogita Dheer; Nitin Chitranshi; Veer Gupta; Mojdeh Abbasi; Mehdi Mirzaei; Yuyi You; Roger Chung; Stuart L. Graham; Vivek Gupta (Molecular Neurobiology, 2018)

Soil drivers of local‐scale tree growth in a lowland tropical forest - Graham Zemunik; Stuart J. Davies; Benjamin L. Turner (Ecology, 2018)
Soil nutrients influence the distribution of tree species in lowland tropical forests, but their effect on productivity, especially at local scales, remains unclear. We used tree census, canopy occupancy, and soil data from the Barro Colorado Island (BCI; Panama) 50‐ha forest dynamics plot to investigate the influence of soil nutrients and potential toxins on aboveground tree productivity. Growth was calculated as the increase in diameter of 150,000 individual stems ≥1 cm diameter at breast height, representing 207 species. The effects of soil variables and other strong predictors of growth (e.g., light) were estimated using hierarchical, linear, mixed‐effects models. Growth was weakly positively associated with phosphorus (P), particularly for understory tree species that are typically considered to be limited by light. In contrast, growth was strongly negatively related to manganese (Mn) and aluminum (Al), although the latter effect was confounded by strong correlations between Al and other soil variables. The negative response to increasing Mn (and Al) suggests a toxicity effect due to solubilization and uptake of amorphous pools of metal oxides in the soil. These results show that P limits tropical tree growth at local scale on BCI, but that toxic metals represent an even greater constraint on productivity.

Memory impairment during a climbing traverse: implications for search and rescue climbing - Samantha L. Epling; Megan J. Blakely; Graham K. Edgar; Paul N. Russell; William S. Helton (Experimental Brain Research, 2018)

Chemical and microbial characteristics of municipal drinking water supply systems in the Canadian Arctic - Kiley Daley; Lisbeth Truelstrup Hansen; Rob C. Jamieson; Jenny L. Hayward; Greg S. Piorkowski; Wendy Krkosek; Graham A. Gagnon; Heather Castleden; Kristen MacNeil; Joanna Poltarowicz; Emmalina Corriveau; Amy Jackson; et al. (Environmental Science and Pollution Research, 2018)

Correction to: Differences in cancer survival by sex: a population-based study using cancer registry data - Nina Afshar; Dallas R. English; Vicky Thursfield; Paul L. Mitchell; Luc Te Marvelde; Helen Farrugia; Graham G. Giles; Roger L. Milne (Cancer Causes & Control, 2018)

Differences in cancer survival by sex: a population-based study using cancer registry data - Nina Afshar; Dallas R. English; Vicky Thursfield; Paul L. Mitchell; Luc Te Marvelde; Helen Farrugia; Graham G. Giles; Roger L. Milne (Cancer Causes & Control, 2018)

The role of managed natural spaces in connecting people with urban nature: a comparison of local user, researcher, and provider views - Siân de Bell; Hilary Graham; Piran C. L. White (Urban Ecosystems, 2018)

Performance Assessment of a Radiofrequency Powered Guidewire for Crossing Peripheral Arterial Occlusions Based on Lesion Morphology - Mohammad A. Tavallaei; James J. Zhou; Trisha L. Roy; Graham A. Wright (Annals of Biomedical Engineering, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Environmental exposure and parental collection does not affect detection or semi-quantitative load assessment of bacteria in nasal swab specimens from children - Nada Townsi; Shannon J. Simpson; Chisha T. Sikazwe; Glenys R. Chidlow; Graham L. Hall; J. Jane Pillow; Andrew C. Wilson; David W. Smith; Ingrid A. Laing (Infectious Diseases, 2018)

Socio-environmental consideration of phosphorus flows in the urban sanitation chain of contrasting cities - Geneviève S. Metson; Steve M. Powers; Rebecca L. Hale; Jesse S. Sayles; Gunilla Öberg; Graham K. MacDonald; Yusuke Kuwayama; Nathaniel P. Springer; Anthony J. Weatherley; Kelly L. Hondula; Kristal Jones; Rubel B. Chowdhury; et al. (Regional Environmental Change, 2018)

Competing for blood: the ecology of parasite resource competition in human malaria–helminth co‐infections - Sarah A. Budischak; Aprilianto E. Wiria; Firdaus Hamid; Linda J. Wammes; Maria M. M. Kaisar; Lisette van Lieshout; Erliyani Sartono; Taniawati Supali; Maria Yazdanbakhsh; Andrea L. Graham (Ecology Letters, 2018)
Ecological theory suggests that co‐infecting parasite species can interact within hosts directly, via host immunity and/or via resource competition. In mice, competition for red blood cells ( RBC s) between malaria and bloodsucking helminths can regulate malaria population dynamics, but the importance of RBC competition in human hosts was unknown. We analysed infection density (i.e. the concentration of parasites in infected hosts), from a 2‐year deworming study of over 4000 human subjects. After accounting for resource‐use differences among parasites, we find evidence of resource competition, priority effects and a competitive hierarchy within co‐infected individuals. For example reducing competition via deworming increased Plasmodium vivax densities 2.8‐fold, and this effect is limited to bloodsucking hookworms. Our ecological, resource‐based perspective sheds new light into decades of conflicting outcomes of malaria–helminth co‐infection studies with significant health and transmission consequences. Beyond blood, investigating within‐human resource competition may bring new insights for improving human health.

High abundance of non-mycorrhizal plant species in severely phosphorus-impoverished Brazilian campos rupestres - Graham Zemunik; Hans Lambers; Benjamin L. Turner; Etienne Laliberté; Rafael S. Oliveira (Plant and Soil, 2018)

Landslide databases in the Geological Surveys of Europe - Gerardo Herrera; Rosa María Mateos; Juan Carlos García-Davalillo; Gilles Grandjean; Eleftheria Poyiadji; Raluca Maftei; Tatiana-Constantina Filipciuc; Mateja Jemec Auflič; Jernej Jež; Laszlo Podolszki; Alessandro Trigila; Carla Iadanza; et al. (Landslides, 2018)

Profiling differential microRNA expression between in situ, infiltrative and lympho-vascular space invasive breast cancer: a pilot study - Patsy S. Soon; Pamela J. Provan; Edward Kim; Nirmala Pathmanathan; Dinny Graham; Christine L. Clarke; Rosemary L. Balleine (Clinical & Experimental Metastasis, 2018)

Designing connected marine reserves in the face of global warming - Jorge G. Álvarez‐Romero; Adrián Munguía‐Vega; Maria Beger; Maria del Mar Mancha‐Cisneros; Alvin N. Suárez‐Castillo; Georgina G. Gurney; Robert L. Pressey; Leah R. Gerber; Hem Nalini Morzaria‐Luna; Héctor Reyes‐Bonilla; Vanessa M. Adams; Melanie Kolb; et al. (Global Change Biology, 2018)
Marine reserves are widely used to protect species important for conservation and fisheries and to help maintain ecological processes that sustain their populations, including recruitment and dispersal. Achieving these goals requires well‐connected networks of marine reserves that maximize larval connectivity, thus allowing exchanges between populations and recolonization after local disturbances. However, global warming can disrupt connectivity by shortening potential dispersal pathways through changes in larval physiology. These changes can compromise the performance of marine reserve networks, thus requiring adjusting their design to account for ocean warming. To date, empirical approaches to marine prioritization have not considered larval connectivity as affected by global warming. Here, we develop a framework for designing marine reserve networks that integrates graph theory and changes in larval connectivity due to potential reductions in planktonic larval duration ( PLD ) associated with ocean warming, given current socioeconomic constraints. Using the Gulf of California as case study, we assess the benefits and costs of adjusting networks to account for connectivity, with and without ocean warming. We compare reserve networks designed to achieve representation of species and ecosystems with networks designed to also maximize connectivity under current and future ocean‐warming scenarios. Our results indicate that current larval connectivity could be reduced significantly under ocean warming because of shortened PLD s. Given the potential changes in connectivity, we show that our graph‐theoretical approach based on centrality (eigenvector and distance‐weighted fragmentation) of habitat patches can help design better‐connected marine reserve networks for the future with equivalent costs. We found that maintaining dispersal connectivity incidentally through representation‐only reserve design is unlikely, particularly in regions with strong asymmetric patterns of dispersal connectivity. Our results support previous studies suggesting that, given potential reductions in PLD due to ocean warming, future marine reserve networks would require more and/or larger reserves in closer proximity to maintain larval connectivity.

Early-onset baldness and the risk of aggressive prostate cancer: findings from a case–control study - Nathan P. Papa; Robert J. MacInnis; Dallas R. English; Damien Bolton; Ian D. Davis; Nathan Lawrentschuk; Jeremy L. Millar; Gianluca Severi; John L. Hopper; Graham G. Giles (Cancer Causes & Control, 2018)

Somatic mutations of the coding microsatellites within the beta-2-microglobulin gene in mismatch repair-deficient colorectal cancers and adenomas - Mark Clendenning; Alvin Huang; Harindra Jayasekara; Marie Lorans; Susan Preston; Neil O’Callaghan; Bernard J. Pope; Finlay A. Macrae; Ingrid M. Winship; Roger L. Milne; Graham G. Giles; Dallas R. English; et al. (Familial Cancer, 2018)

Kinetic Measurements of Di- and Tripeptide and Peptidomimetic Drug Transport in Different Kidney Regions Using the Fluorescent Membrane Potential-Sensitive Dye, DiS-C3-(3) - Othman A. Alghamdi; Nicola King; Graham L. Jones; Pierre D. J. Moens (The Journal of Membrane Biology, 2017)

Implications of afforestation for bird communities: the importance of preceding land-use type - Conor T. Graham; Mark W. Wilson; Tom Gittings; Thomas C. Kelly; Sandra Irwin; John L. Quinn; John O’Halloran (Biodiversity and Conservation, 2017)

Vocal foragers and silent crowds: context-dependent vocal variation in Northeast Atlantic long-finned pilot whales - Fleur Visser; Annebelle C.M. Kok; Machiel G. Oudejans; Lindesay A.S. Scott-Hayward; Stacy L. DeRuiter; Ana C. Alves; Ricardo N. Antunes; Saana Isojunno; Graham J. Pierce; Hans Slabbekoorn; Jef Huisman; Patrick J. O. Miller (Behavioral Ecology and Sociobiology, 2017)

Untangling the proximate causes and underlying drivers of deforestation and forest degradation in Myanmar - Cheng Ling Lim; Graham W. Prescott; Jose Don T. De Alban; Alan D. Ziegler; Edward L. Webb (Conservation Biology, 2017)
Political transitions often trigger substantial environmental changes. In particular, deforestation can result from the complex interplay among the components of a system—actors, institutions, and existing policies—adapting to new opportunities. A dynamic conceptual map of system components is particularly useful for systems in which multiple actors, each with different worldviews and motivations, may be simultaneously trying to alter different facets of the system, unaware of the impacts on other components. In Myanmar, a global biodiversity hotspot with the largest forest area in mainland Southeast Asia, ongoing political and economic reforms are likely to change the dynamics of deforestation drivers. A fundamental conceptual map of these dynamics is therefore a prerequisite for interventions to reduce deforestation. We used a system‐dynamics approach and causal‐network analysis to determine the proximate causes and underlying drivers of forest loss and degradation in Myanmar from 1995 to 2016 and to articulate the linkages among them. Proximate causes included infrastructure development, timber extraction, and agricultural expansion. These were stimulated primarily by formal agricultural, logging, mining, and hydropower concessions and economic investment and social issues relating to civil war and land tenure. Reform of land laws, the link between natural resource extraction and civil war, and the allocation of agricultural concessions will influence the extent of future forest loss and degradation in Myanmar. The causal‐network analysis identified priority areas for policy interventions, for example, creating a public registry of land‐concession holders to deter corruption in concession allocation. We recommend application of this analytical approach to other countries, particularly those undergoing political transition, to inform policy interventions to reduce forest loss and degradation.

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Peripheral Brain-Derived Neurotrophic Factor Levels in Alzheimer’s Disease and Mild Cognitive Impairment: a Comprehensive Systematic Review and Meta-analysis - Bo Yi Kim; Seon Heui Lee; Petra L. Graham; Francesco Angelucci; Alejandro Lucia; Helios Pareja-Galeano; Thomas Leyhe; Yuda Turana; I Re Lee; Ji Hye Yoon; Jae Il Shin (Molecular Neurobiology, 2017)

Associations between lobster phyllosoma and gelatinous zooplankton in relation to oceanographic properties in the northern Gulf of Mexico - Adam T. Greer; Christian Briseño‐Avena; Alison L. Deary; Robert K. Cowen; Frank J. Hernandez; William M. Graham (Fisheries Oceanography, 2017)
Lobster phyllosoma are known to associate with large cnidarian medusae; however, direct quantitative observations are difficult because gelatinous zooplankton are extremely fragile, and the phyllosoma easily detach from their host when sampled by plankton nets. We provide the first large scale quantitative information of the distribution of this association using an in situ imaging system, with synoptic measurements of water column properties. All phyllosoma were identified as slipper lobsters ( Scyllarus chacei ) and were associated with previously unreported “hosts” such as small hydromedusae, doliolids, and siphonophores in the northern Gulf of Mexico. Along the shelf, phyllosoma were more likely to be present at greater depths and higher salinities. Approximately 30% of the 347 lobster phyllosoma imaged were attached to at least one gelatinous organism, and salinity and depth were positively related to the probability of attachment on 30 October, but did not show a significant relationship for the other days of sampling. Many of the phyllosoma were larger than the gelatinous organisms to which they were attached, and some gelatinous zooplankton showed damage likely from feeding by the phyllosoma. In this coastal environment, gelatinous zooplankton tended to be more abundant in the same offshore region where phyllosoma occurred, so these gelatinous “hosts” may provide a steady food supply in the more oligotrophic waters on the outer shelf. Similar complex interactions among zooplankton may influence the life histories of other species, hindering our ability to forecast ecosystem level processes until the population level consequences of species interactions are fully understood.

The missing half of the subduction factory: shipboard results from the Izu rear arc, IODP Expedition 350 - Cathy J. Busby; Yoshihiko Tamura; Peter Blum; Gilles Guèrin; Graham D. M. Andrews; Abigail K. Barker; Julien L. R. Berger; Everton M. Bongiolo; Manuela Bordiga; Susan M. DeBari; James B. Gill; Cedric Hamelin; et al. (International Geology Review, 2017)

Regional climate changes drive increased scaled-chrysophyte abundance in lakes downwind of Athabasca Oil Sands nitrogen emissions - Graham R. Mushet; Kathleen R. Laird; Biplob Das; Brittany Hesjedal; Peter R. Leavitt; Kenneth A. Scott; Gavin L. Simpson; Björn Wissel; Jared D. Wolfe; Brian F. Cumming (Journal of Paleolimnology, 2017)

Physiological proteins in resource-limited herbivores experiencing a population die-off - R. Garnier; A. I. Bento; C. Hansen; J. G. Pilkington; J. M. Pemberton; A. L Graham (The Science of Nature, 2017)

A dosing algorithm for metformin based on the relationships between exposure and renal clearance of metformin in patients with varying degrees of kidney function - Janna K. Duong; M. Y. A. M. Kroonen; S. S. Kumar; H. L. Heerspink; C. M. Kirkpatrick; G. G. Graham; K. M. Williams; R. O. Day (European Journal of Clinical Pharmacology, 2017)

Exposure to predators reduces collective foraging aggressiveness and eliminates its relationship with colony personality composition - Colin M. Wright; James L. L. Lichtenstein; Graham A. Montgomery; Lauren P. Luscuskie; Noa Pinter-Wollman; Jonathan N. Pruitt (Behavioral Ecology and Sociobiology, 2017)

A response to ‘Comment to Wetzeliella and its allies – the ‘hole’ story: a taxonomic revision of the Paleogene dinoflagellate subfamily Wetzelielloideae by Williams et al. (2015)’ - Graham L. Williams; Sarah P. Damassa; Robert A. Fensome; G. Raquel Guerstein (Palynology, 2017)

Multi-criteria correlation of tephra deposits to source centres applied in the Auckland Volcanic Field, New Zealand - Jenni L. Hopkins; Colin J. N. Wilson; Marc-Alban Millet; Graham S. Leonard; Christian Timm; Lucy E. McGee; Ian E. M. Smith; Euan G. C. Smith (Bulletin of Volcanology, 2017)

Bradyrhizobium centrolobii and Bradyrhizobium macuxiense sp. nov. isolated from Centrolobium paraense grown in soil of Amazonia, Brazil - Daniele C. Michel; Samuel R. Passos; Jean L. Simões-Araujo; Alexandre C. Baraúna; Krisle da Silva; Marcia M. Parma; Itamar S. Melo; Sofie E. De Meyer; Graham O’Hara; Jerri E. Zilli (Archives of Microbiology, 2017)

The within‐host dynamics of infection in trans‐generationally primed flour beetles - Ann T. Tate; Peter Andolfatto; Jeffery P. Demuth; Andrea L. Graham (Molecular Ecology, 2017)
Many taxa exhibit plastic immune responses initiated after primary microbial exposure that provide increased protection against disease‐induced mortality and the fitness costs of infection. In several arthropod species, this protection can even be passed from parents to offspring through a phenomenon called trans‐generational immune priming. Here, we first demonstrate that trans‐generational priming is a repeatable phenomenon in flour beetles ( Tribolium castaneum ) primed and infected with Bacillus thuringiensis (Bt). We then quantify the within‐host dynamics of microbes and host physiological responses in infected offspring from primed and unprimed mothers by monitoring bacterial density and using mRNA ‐seq to profile host gene expression, respectively, over the acute infection period. We find that priming increases inducible resistance against Bt around a critical temporal juncture where host septicaemic trajectories, and consequently survival, may be determined in unprimed individuals. Our results identify a highly differentially expressed biomarker of priming, containing an EIF 4‐e domain, in uninfected individuals, as well as several other candidate genes. Moreover, the induction and decay dynamics of gene expression over time suggest a metabolic shift in primed individuals. The identified bacterial and gene expression dynamics are likely to influence patterns of bacterial fitness and disease transmission in natural populations.

Bioremediation efficacy—comparison of nutrient removal from an anaerobic digest waste-based medium by an algal consortium before and after cryopreservation - Alla Silkina; Graham D. Nelson; Catherine E. Bayliss; Craig L. Pooley; John G. Day (Journal of Applied Phycology, 2017)

Relationships between structural complexity, coral traits, and reef fish assemblages - Emily S. Darling; Nicholas A. J. Graham; Fraser A. Januchowski-Hartley; Kirsty L. Nash; Morgan S. Pratchett; Shaun K. Wilson (Coral Reefs, 2017)

Interspecific hybridization causes long‐term phylogenetic discordance between nuclear and mitochondrial genomes in freshwater fishes - Graham P. Wallis; Sophia R. Cameron‐Christie; Hannah L. Kennedy; Gemma Palmer; Tessa R. Sanders; David J. Winter (Molecular Ecology, 2017)
Classification, phylogeography and the testing of evolutionary hypotheses rely on correct estimation of species phylogeny. Early molecular phylogenies often relied on mt DNA alone, which acts as a single linkage group with one history. Over the last decade, the use of multiple nuclear sequences has often revealed conflict among gene trees. This observation can be attributed to hybridization, lineage sorting, paralogy or selection. Here, we use 54 groups of fishes from 48 studies to estimate the degree of concordance between mitochondrial and nuclear gene trees in two ecological grades of fishes: marine and freshwater. We test the hypothesis that freshwater fish phylogenies should, on average, show more discordance because of their higher propensity for hybridization in the past. In keeping with this idea, concordance between mitochondrial and nuclear gene trees (as measured by proportion of components shared) is on average 50% higher in marine fishes. We discuss why this difference almost certainly results from introgression caused by greater historical hybridization among lineages in freshwater groups, and further emphasize the need to use multiple nuclear genes, and identify conflict among them, in estimation of species phylogeny.

A new genus and two new species of Thyasiridae associated with methane seeps off Svalbard, Arctic Ocean - Emmelie K.L. Åström; P. Graham Oliver; Michael L. Carroll (Marine Biology Research, 2017)

All in the family? Analyzing the impact of family history in addition to genotype on medullary thyroid carcinoma aggressiveness in MEN2A patients - Kristin L. Long; Carol Etzel; Thereasa Rich; Samuel Hyde; Nancy D. Perrier; Paul H. Graham; Jeffrey E. Lee; Mimi I. Hu; Gilbert J. Cote; Robert Gagel; Elizabeth G. Grubbs (Familial Cancer, 2017)

Uncoupling temperature-dependent mortality from lipid depletion for scleractinian coral larvae - E. M. Graham; A. H. Baird; S. R. Connolly; M. A. Sewell; B. L. Willis (Coral Reefs, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

Effectiveness of baseline corticosterone as a monitoring tool for fitness: a meta-analysis in seabirds - Graham H. Sorenson; Cody J. Dey; Christine L. Madliger; Oliver P. Love (Oecologia, 2017)

Effects of Neonatal Methamphetamine and Stress on Brain Monoamines and Corticosterone in Preweanling Rats - Sarah A. Jablonski; Devon L. Graham; Charles V. Vorhees; Michael T. Williams (Neurotoxicity Research, 2017)

Variability of hydrological extreme events in East Asia and their dynamical control: a comparison between observations and two high-resolution global climate models - N. Freychet; A. Duchez; C.-H. Wu; C.-A. Chen; H.-H. Hsu; J. Hirschi; A. Forryan; B. Sinha; A. L. New; T. Graham; M. B. Andrews; C.-Y. Tu; et al. (Climate Dynamics, 2017)

Sexual response of male Drosophila to honey bee queen mandibular pheromone: implications for genetic studies of social insects - Justin R. Croft; Tom Liu; Alison L. Camiletti; Anne F. Simon; Graham J. Thompson (Journal of Comparative Physiology A, 2017)

Joint associations of blood plasma proteins with overwinter survival of a large mammal - Romain Garnier; Christopher K. Cheung; Kathryn A. Watt; Jill G. Pilkington; Josephine M. Pemberton; Andrea L. Graham (Ecology Letters, 2017)
In many wild animal populations, hosts are at risk of parasites and malnutrition and resource costs of defence may be difficult to afford. We postulate that proteins, important in homeostasis and immunity, play a complex but central role in condition dependence and resource costs of mammalian immune defence. To test this, we measured plasma concentrations of albumin, total proteins. Self‐reactive antibodies and parasite‐specific IgG in female Soay sheep. Using a principal component analysis, we found a new metric of condition reflecting individual variation in acquisition, assimilation and/or recycling of plasma proteins that predicted overwinter survival. Controlling for this metric, an age‐dependent trade‐off between antibody titres and protein reserves emerged, indicating costs of mounting an antibody response: younger individuals survived best when prioritising immunity while older individuals fared better when maintaining high‐protein nutritional plane. These findings suggest fascinating roles for protein acquisition and allocation in influencing survival in wild animal populations.

Mainstreaming the social sciences in conservation - Nathan J. Bennett; Robin Roth; Sarah C. Klain; Kai M. A. Chan; Douglas A. Clark; Georgina Cullman; Graham Epstein; Michael Paul Nelson; Richard Stedman; Tara L. Teel; Rebecca E. W. Thomas; Carina Wyborn; et al. (Conservation Biology, 2017)
Despite broad recognition of the value of social sciences and increasingly vocal calls for better engagement with the human element of conservation, the conservation social sciences remain misunderstood and underutilized in practice. The conservation social sciences can provide unique and important contributions to society's understanding of the relationships between humans and nature and to improving conservation practice and outcomes. There are 4 barriers—ideological, institutional, knowledge, and capacity—to meaningful integration of the social sciences into conservation. We provide practical guidance on overcoming these barriers to mainstream the social sciences in conservation science, practice, and policy. Broadly, we recommend fostering knowledge on the scope and contributions of the social sciences to conservation, including social scientists from the inception of interdisciplinary research projects, incorporating social science research and insights during all stages of conservation planning and implementation, building social science capacity at all scales in conservation organizations and agencies, and promoting engagement with the social sciences in and through global conservation policy‐influencing organizations. Conservation social scientists, too, need to be willing to engage with natural science knowledge and to communicate insights and recommendations clearly. We urge the conservation community to move beyond superficial engagement with the conservation social sciences. A more inclusive and integrative conservation science—one that includes the natural and social sciences—will enable more ecologically effective and socially just conservation. Better collaboration among social scientists, natural scientists, practitioners, and policy makers will facilitate a renewed and more robust conservation. Mainstreaming the conservation social sciences will facilitate the uptake of the full range of insights and contributions from these fields into conservation policy and practice.

Demography and ecology of southern right whales Eubalaena australis wintering at sub-Antarctic Campbell Island, New Zealand - Leigh G. Torres; Will Rayment; Carlos Olavarría; David R. Thompson; Brittany Graham; C. Scott Baker; Nathalie Patenaude; Sarah Jane Bury; Laura Boren; Graham Parker; Emma L. Carroll (Polar Biology, 2017)

Air breathing and aquatic gas exchange during hypoxia in armoured catfish - Graham R. Scott; Victoria Matey; Julie-Anne Mendoza; Kathleen M. Gilmour; Steve F. Perry; Vera M. F. Almeida-Val; Adalberto L. Val (Journal of Comparative Physiology B, 2017)

Detecting spatial regimes in ecosystems - Shana M. Sundstrom; Tarsha Eason; R. John Nelson; David G. Angeler; Chris Barichievy; Ahjond S. Garmestani; Nicholas A.J. Graham; Dean Granholm; Lance Gunderson; Melinda Knutson; Kirsty L. Nash; Trisha Spanbauer; et al. (Ecology Letters, 2017)
Research on early warning indicators has generally focused on assessing temporal transitions with limited application of these methods to detecting spatial regimes. Traditional spatial boundary detection procedures that result in ecoregion maps are typically based on ecological potential (i.e. potential vegetation), and often fail to account for ongoing changes due to stressors such as land use change and climate change and their effects on plant and animal communities. We use Fisher information, an information theory‐based method, on both terrestrial and aquatic animal data (U.S. Breeding Bird Survey and marine zooplankton) to identify ecological boundaries, and compare our results to traditional early warning indicators, conventional ecoregion maps and multivariate analyses such as nMDS and cluster analysis. We successfully detected spatial regimes and transitions in both terrestrial and aquatic systems using Fisher information. Furthermore, Fisher information provided explicit spatial information about community change that is absent from other multivariate approaches. Our results suggest that defining spatial regimes based on animal communities may better reflect ecological reality than do traditional ecoregion maps, especially in our current era of rapid and unpredictable ecological change.

New constraints on the spatial distribution and morphology of the Halimeda bioherms of the Great Barrier Reef, Australia - Mardi A. McNeil; Jody M. Webster; Robin J. Beaman; Trevor L. Graham (Coral Reefs, 2016)

The role of boundary organizations in climate change adaptation from the perspective of municipal practitioners - Alexandra Graham; Carrie L. Mitchell (Climatic Change, 2016)

Development of passive sampling devices for bioavailable contaminants of current and emerging concern: Waitemata Harbour case study - M Stewart; M Cameron; M McMurtry; SG Sander; B Benedict; L Graham; M Hosie; T Green (New Zealand Journal of Marine and Freshwater Research, 2016)
Bioavailable contaminant concentrations are an important component in assessing environmental effects as they directly affect ecosystem health. Shellfish contaminant monitoring programmes have traditionally filled this requirement but are being phased out in some jurisdictions. Passive sampling devices (PSDs) have the potential to replace shellfish monitoring; however, there are still knowledge gaps to address before this can occur. This study assessed the suitability of three different PSDs in providing the required information to replace shellfish monitoring. PSDs were deployed at three historic mussel monitoring sites with different levels of urban influence in the Waitemata Harbour, Auckland, New Zealand. Contaminants of interest were urban heavy metals, plus current and emerging organic contaminants. PSDs provided extremely low detection limits and, for some contaminants, very strong correlations to shellfish. PSDs can currently complement shellfish in monitoring, but it is premature to make conclusions as to the suitability of PSDs in replacing shellfish monitoring until more information is available.

Ecological indicators for coral reef fisheries management - Kirsty L Nash; Nicholas A J Graham (Fish and Fisheries, 2016)
Coral reef fisheries are of great importance both economically and for food security, but many reefs are showing evidence of overfishing, with significant ecosystem‐level consequences for reef condition. In response, ecological indicators have been developed to assess the state of reef fisheries and their broader ecosystem‐level impacts. To date, use of fisheries indicators for coral reefs has been rather piecemeal, with no overarching understanding of their performance with respect to highlighting fishing effects. Here, we provide a review of multispecies fishery‐independent indicators used to evaluate fishing impacts on coral reefs. We investigate the consistency with which indicators highlight fishing effects on coral reefs. We then address questions of statistical power and uncertainty, type of fishing gradient, scale of analysis, the influence of other variables and the need for more work to set reference points for empirical, fisheries‐independent indicators on coral reefs. Our review provides knowledge that will help underpin the assessment of the ecological effects of fishing, offering essential support for the development and implementation of coral reef fisheries management plans.

Developmental Trajectory of Beta Cortical Oscillatory Activity During a Knee Motor Task - Max J. Kurz; Amy L. Proskovec; James E. Gehringer; Katherine M. Becker; David J. Arpin; Elizabeth Heinrichs-Graham; Tony W. Wilson (Brain Topography, 2016)

Stable AMOC off state in an eddy-permitting coupled climate model - J. V. Mecking; S. S. Drijfhout; L. C. Jackson; T. Graham (Climate Dynamics, 2016)

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Is breast cancer risk associated with alcohol intake before first full-term pregnancy? - Harindra Jayasekara; Robert J. MacInnis; Allison M. Hodge; Robin Room; Roger L. Milne; John L. Hopper; Graham G. Giles; Dallas R. English (Cancer Causes & Control, 2016)

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

A Global-Scale Evaluation of Primate Exposure and Vulnerability to Climate Change - Tanya L. Graham; H. Damon Matthews; Sarah E. Turner (International Journal of Primatology, 2016)

Determining the familial risk distribution of colorectal cancer: a data mining approach - Rowena Chau; Mark A. Jenkins; Daniel D. Buchanan; Driss Ait Ouakrim; Graham G. Giles; Graham Casey; Steven Gallinger; Robert W. Haile; Loic Le Marchand; Polly A. Newcomb; Noralane M. Lindor; John L. Hopper; et al. (Familial Cancer, 2016)

Demographic buffering and compensatory recruitment promotes the persistence of disease in a wildlife population - Jenni L. McDonald; Trevor Bailey; Richard J. Delahay; Robbie A. McDonald; Graham C. Smith; Dave J. Hodgson (Ecology Letters, 2016)
Demographic buffering allows populations to persist by compensating for fluctuations in vital rates, including disease‐induced mortality. Using long‐term data on a badger ( Meles meles Linnaeus, 1758) population naturally infected with Mycobacterium bovis , we built an integrated population model to quantify impacts of disease, density and environmental drivers on survival and recruitment. Badgers exhibit a slow life‐history strategy, having high rates of adult survival with low variance, and low but variable rates of recruitment. Recruitment exhibited strong negative density‐dependence, but was not influenced by disease, while adult survival was density independent but declined with increasing prevalence of diseased individuals. Given that reproductive success is not depressed by disease prevalence, density‐dependent recruitment of cubs is likely to compensate for disease‐induced mortality. This combination of slow life history and compensatory recruitment promotes the persistence of a naturally infected badger population and helps to explain the badger's role as a persistent reservoir of M. bovis .

Fossil dinoflagellates: nomenclatural proposals in anticipation of a revised DINOFLAJ database - Graham L. Williams; Robert A. Fensome (Palynology, 2016)

Origin of the alkali tonsteins from southwest China: Implications for alkaline magmatism associated with the waning stages of the Emeishan Large Igneous Province - L. Zhao; I. Graham (Australian Journal of Earth Sciences, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Species specificity of temporal processing in the auditory midbrain of gray treefrogs: long-interval neurons - Jessica L. Hanson; Gary J. Rose; Christopher J. Leary; Jalina A. Graham; Rishi K. Alluri; Gustavo A. Vasquez-Opazo (Journal of Comparative Physiology A, 2016)

Tissue-specific transcriptome analysis within the maturing sugarcane stalk reveals spatial regulation in the expression of cellulose synthase and sucrose transporter gene families - Rosanne E. Casu; Anne L. Rae; Janine M. Nielsen; Jai M. Perroux; Graham D. Bonnett; John M. Manners (Plant Molecular Biology, 2015)

Enhanced anti-fibrogenic effects of novel oridonin derivative CYD0692 in hepatic stellate cells - Fredrick J. Bohanon; Xiaofu Wang; Brittany M. Graham; Anesh Prasai; Sadhashiva J. Vasudevan; Chunyong Ding; Ye Ding; Geetha L. Radhakrishnan; Cristiana Rastellini; Jia Zhou; Ravi S. Radhakrishnan (Molecular and Cellular Biochemistry, 2015)

A Community Coalition to Address Cancer Disparities: Transitions, Successes and Challenges - Vetta L. Sanders Thompson; Bettina Drake; Aimee S. James; Monique Norfolk; Melody Goodman; Leon Ashford; Sherrill Jackson; Miranda Witherspoon; Mikki Brewster; Graham Colditz (Journal of Cancer Education, 2015)

Global and European climate impacts of a slowdown of the AMOC in a high resolution GCM - L. C. Jackson; R. Kahana; T. Graham; M. A. Ringer; T. Woollings; J. V. Mecking; R. A. Wood (Climate Dynamics, 2015)

Risk of colorectal cancer for people with a mutation in both a MUTYH and a DNA mismatch repair gene - Aung Ko Win; Jeanette C. Reece; Daniel D. Buchanan; Mark Clendenning; Joanne P. Young; Sean P. Cleary; Hyeja Kim; Michelle Cotterchio; James G. Dowty; Robert J. MacInnis; Katherine M. Tucker; Ingrid M. Winship; et al. (Familial Cancer, 2015)

Childhood cancers in families with and without Lynch syndrome - John A. Heath; Jeanette C. Reece; Daniel D. Buchanan; Graham Casey; Carol A. Durno; Steven Gallinger; Robert W. Haile; Polly A. Newcomb; John D. Potter; Stephen N. Thibodeau; Loïc Le Marchand; Noralane M. Lindor; et al. (Familial Cancer, 2015)

Bottom‐up regulation of malaria population dynamics in mice co‐infected with lung‐migratory nematodes - Emily C. Griffiths; Karen Fairlie‐Clarke; Judith E. Allen; C. Jessica E. Metcalf; Andrea L. Graham (Ecology Letters, 2015)
When and how populations are regulated by bottom up vs. top down processes, and how those processes are affected by co‐occurring species, are poorly characterised across much of ecology. We are especially interested in the community ecology of parasites that must share a host. Here, we quantify how resources and immunity affect parasite propagation in experiments in near‐replicate ‘mesocosms’’ – i.e. mice infected with malaria ( Plasmodium chabaudi ) and nematodes ( Nippostrongylus brasiliensis ). Nematodes suppressed immune responses against malaria, and yet malaria populations were smaller in co‐infected hosts. Further analyses of within‐host epidemiology revealed that nematode co‐infection altered malaria propagation by suppressing target cell availability. This is the first demonstration that bottom‐up resource regulation may have earlier and stronger effects than top‐down immune mechanisms on within‐host community dynamics. Our findings demonstrate the potential power of experimental ecology to disentangle mechanisms of population regulation in complex communities.

Dependence of Two-Photon eGFP Bleaching on Femtosecond Pulse Spectral Amplitude and Phase - David J. L. Graham; Shu-Fen Tseng; Jer-Tsong Hsieh; David J. Chen; George Alexandrakis (Journal of Fluorescence, 2015)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Male orang-utan bimaturism and reproductive success at Camp Leakey in Tanjung Puting National Park, Indonesia - Graham L. Banes; Biruté M. F. Galdikas; Linda Vigilant (Behavioral Ecology and Sociobiology, 2015)

Effect of ageing and oxidative stress on antioxidant enzyme activity in different regions of the rat kidney - Noor Riyadh Thiab; Nicola King; Graham L. Jones (Molecular and Cellular Biochemistry, 2015)

Effects of ageing on metabolite and oxidant concentrations in different regions of rat kidney under normal and stress conditions - Noor Riyadh Thiab; Nicola King; Graham L. Jones (Molecular and Cellular Biochemistry, 2015)

Wetzeliella and its allies – the ‘hole’ story: a taxonomic revision of the Paleogene dinoflagellate subfamily Wetzelielloideae - Graham L. Williams; Sarah P. Damassa; Robert A. Fensome; G. Raquel Guerstein (Palynology, 2015)

Thermogeographic variation in body size of Carcinus maenas, the European green crab - Amanda L. Kelley; Catherine E. de Rivera; Edwin D. Grosholz; Gregory M. Ruiz; Sylvia Behrens Yamada; Graham Gillespie (Marine Biology, 2015)

Quinolinic acid/tryptophan ratios predict neurological disease in SIV-infected macaques and remain elevated in the brain under cART - Julia L. Drewes; Kelly A. Meulendyke; Zhaohao Liao; Kenneth W. Witwer; Lucio Gama; Ceereena Ubaida-Mohien; Ming Li; Francesca M. Notarangelo; Patrick M. Tarwater; Robert Schwarcz; David R. Graham; M. Christine Zink (Journal of NeuroVirology, 2015)

Supplementary feeding of wild birds indirectly affects ground beetle populations in suburban gardens - Melanie E. Orros; Rebecca L. Thomas; Graham J. Holloway; Mark D. E. Fellowes (Urban Ecosystems, 2015)

Controlled Extraction Studies Applied to Polyvinyl Chloride and Polyethylene Materials: Conclusions from the ELSIE Controlled Extraction Pilot Study - Andrew Teasdale; Michael Jahn; Simon Bailey; Andrew Feilden; Graham Taylor; Marta L. Corcoran; Robert Malick; Dennis Jenke; Cheryl L. M. Stults; Lee M. Nagao (AAPS PharmSciTech, 2015)

Species-specificity of temporal processing in the auditory midbrain of gray treefrogs: interval-counting neurons - Gary J. Rose; Jessica L. Hanson; Christopher J. Leary; Jalina A. Graham; Rishi K. Alluri; Gustavo A. Vasquez-Opazo (Journal of Comparative Physiology A, 2015)

Setting the stage for a global-scale trophic analysis of marine top predators: a multi-workshop review - J. W. Young; R. J. Olson; F. Ménard; P. M. Kuhnert; L. M. Duffy; V. Allain; J. M. Logan; A. Lorrain; C. J. Somes; B. Graham; N. Goñi; H. Pethybridge; et al. (Reviews in Fish Biology and Fisheries, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Lifetime alcohol consumption and upper aero-digestive tract cancer risk in the Melbourne Collaborative Cohort Study - Harindra Jayasekara; Robert J. MacInnis; Allison M. Hodge; John L. Hopper; Graham G. Giles; Robin Room; Dallas R. English (Cancer Causes & Control, 2015)

Home-range allometry in coral reef fishes: comparison to other vertebrates, methodological issues and management implications - Kirsty L. Nash; Justin Q. Welsh; Nicholas A. J. Graham; David R. Bellwood (Oecologia, 2015)

Intakes of fat and micronutrients between ages 13 and 18 years and the incidence of proliferative benign breast disease - Xuefen Su; Caroline E. Boeke; Laura C. Collins; Heather J. Baer; Walter C. Willett; Stuart J. Schnitt; James L. Connolly; Bernard Rosner; Graham A. Colditz; Rulla M. Tamimi (Cancer Causes & Control, 2015)

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Impact of minocycline on cerebrospinal fluid markers of oxidative stress, neuronal injury, and inflammation in HIV-seropositive individuals with cognitive impairment - Ned Sacktor; Sachiko Miyahara; Scott Evans; Giovanni Schifitto; Bruce Cohen; Norman Haughey; Julia L. Drewes; David Graham; M.Christine Zink; Caroline Anderson; Avindra Nath; Carlos A. Pardo; et al. (Journal of NeuroVirology, 2014)

Combination fluconazole/paroxetine treatment is neuroprotective despite ongoing neuroinflammation and viral replication in an SIV model of HIV neurological disease - Kelly A. Meulendyke; Suzanne E. Queen; Elizabeth L. Engle; Erin N. Shirk; Jiayang Liu; Joseph P. Steiner; Avindra Nath; Patrick M. Tarwater; David R. Graham; Joseph L. Mankowski; M. Christine Zink (Journal of NeuroVirology, 2014)

Life history of harbor porpoises ( Phocoena phocoena ) in Scottish ( UK ) waters - Jennifer A. Learmonth; Sinead Murphy; Patricia L. Luque; Robert J. Reid; I. Anthony P. Patterson; Andrew Brownlow; Harry M. Ross; Jason P. Barley; M. Begoña Santos; Graham J. Pierce (Marine Mammal Science, 2014)
Life history parameters were determined for stranded and bycaught harbor porpoises ( Phocoena phocoena ) from Scottish ( UK ) waters (1992–2005). Fetal growth rate was 84.4 mm/mo and mean size at birth was 76.4 cm (range 65–88 cm). Males and females had a similar range of body lengths (65–170 cm and 66–173 cm, respectively), although asymptotic lengths were higher in females than males (approximately 158 cm and 147 cm, respectively). Nonpregnant females were significantly lighter, in relation to their length than males. Maximum estimated age was 20 yr for both sexes. Age at sexual maturity ( ASM ) was estimated as 4.35 yr in females and 5.00 yr in males. Conception occurred mainly in July and August although reproductively active males were recorded during April to July. Gestation lasted 10–11 mo, with calving mainly between May and July. Lactating females were recorded during June to November, while small calves with solid food in their stomachs were found mainly during February to May. Estimated pregnancy rate (0.34–0.40) is lower than recorded elsewhere, but is likely underestimated due to the prevalence of mature females of poor health status in the sample. Nevertheless, cetacean strandings can be an essential source of data on demographic parameters.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Sugarcane Flowering Genes and Pathways in Relation to Vegetative Regression - Donna Glassop; Anne L. Rae; Graham D. Bonnett (Sugar Tech, 2014)

Improved hydrograph prediction through subsurface characterization: conditional stochastic hillslope simulations - Steven B. Meyerhoff; Reed M. Maxwell; Wendy D. Graham; John L. Williams (Hydrogeology Journal, 2014)

Simulation of the West African monsoon onset using the HadGEM3-RA regional climate model - Ismaïla Diallo; Caroline L. Bain; Amadou T. Gaye; Wilfran Moufouma-Okia; Coumba Niang; Mame D. B. Dieng; Richard Graham (Climate Dynamics, 2014)

Gelatinous zooplankton biomass in the global oceans: geographic variation and environmental drivers - Cathy H. Lucas; Daniel O. B. Jones; Catherine J. Hollyhead; Robert H. Condon; Carlos M. Duarte; William M. Graham; Kelly L. Robinson; Kylie A. Pitt; Mark Schildhauer; Jim Regetz (Global Ecology and Biogeography, 2014)
Aim Scientific debate regarding the future trends, and subsequent ecological, biogeochemical and societal impacts, of gelatinous zooplankton ( GZ ) in a changing ocean is hampered by lack of a global baseline and an understanding of the causes of biogeographic patterns. We address this by using a new global database of GZ records to test hypotheses relating to environmental drivers of biogeographic variation in the multidecadal baseline of epipelagic GZ biomass in the world's oceans. Location Global oceans. Methods Over 476,000 global GZ data and metadata items were assembled from a variety of published and unpublished sources. From this, a total of 91,765 quantitative abundance data items from 1934 to 2011 were converted to carbon biomass using published biometric equations and species‐specific average sizes. Total GZ , Cnidaria, Ctenophora and Chordata (Thaliacea) biomass was mapped into 5° grid cells and environmental drivers of geographic variation were tested using spatial linear models. Results We present JeDI (the J ellyfish D atabase I nitiative), a publically accessible database available at http://jedi.nceas.ucsb.edu . We show that: (1) GZ are present throughout the world's oceans; (2) the global geometric mean and standard deviation of total gelatinous biomass is 0.53 ± 16.16 mg C m −3 , corresponding to a global biomass of 38.3 Tg C in the mixed layer of the ocean; (3) biomass of all gelatinous phyla is greatest in the subtropical and boreal Northern Hemisphere; and (4) within the North Atlantic, dissolved oxygen, apparent oxygen utilization and sea surface temperature are the principal drivers of biomass distribution. Main conclusions JeDI is a unique global dataset of GZ taxa which will provide a benchmark against which future observations can be compared and shifting baselines assessed. The presence of GZ throughout the world's oceans and across the complete global spectrum of environmental variables indicates that evolution has delivered a range of species able to adapt to all available ecological niches.

Macroalgal herbivory on recovering versus degrading coral reefs - K. M. Chong-Seng; K. L. Nash; D. R. Bellwood; N. A. J. Graham (Coral Reefs, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Plant–animal diversity relationships in a rocky intertidal system depend on invertebrate body size and algal cover - Rebecca J. Best; Ambre L. Chaudoin; Matthew E. S. Bracken; Michael H. Graham; John J. Stachowicz (Ecology, 2014)
Considerable research has examined the influence of herbivores on the maintenance of plant diversity, but fewer studies have examined the reciprocal effect of plant diversity on the animals that use the plant community for food and shelter, particularly in marine systems. Several mechanisms could underlie such effects. Animal diversity and abundance could be increased by complementary use of different plants by different animals, or by an indirect effect of plant diversity on plant production that results in more total plant biomass in high plant‐diversity communities. Alternatively, plant species identity could play a dominant role leading to sampling effects or no effect of diversity at all. We conducted a six‐year field manipulation of the richness of rocky shore seaweeds in northern California and measured the effects of algal richness and identity on the invertebrate community, from meiofauna to macrofauna. We found that diverse algal communities hosted more species of both large and small invertebrates than the average algal monoculture but that the mechanisms underlying this pattern differed substantially for organisms of different size. More species of macrofauna occurred in the polycultures than in any of the monocultures, likely due to the greater total cover of algae produced in polycultures. Rare and common macrofaunal taxa responded to host plant species richness in opposite ways, with more occurrences of rare taxa and lower abundance of very common taxa in the polycultures. In contrast, meiofaunal richness in polycultures was no different than that of monocultures of finely branched species, leading to strong effects of algal identity. Our findings are similar to those from terrestrial systems in that the effects of plant diversity we observed were most related to the greater amount of habitat in polycultures as a result of overyielding in algal biomass. However, our findings differ from those in terrestrial systems in that the primary mechanisms for both richness and identity effects appear related to the value of plants as shelter from harsh abiotic conditions or predation rather than food, and in that animal body size altered the mechanisms underlying diversity effects.

Mineralogy and major-element geochemistry of the lower Permian Greta Seam, Sydney Basin, Australia - L. Zhao; C. R. Ward; D. French; I. T. Graham (Australian Journal of Earth Sciences, 2014)

Legumes in prairie restoration: evidence for wide cross-nodulation and improved inoculant delivery - Elena Beyhaut; Diane L. Larson; Deborah L. Allan; Peter H. Graham (Plant and Soil, 2014)

Aquatic Macrophytes Alter Metabolism and Nutrient Cycling in Lowland Streams - Jonathan M. O’Brien; Joanna L. Lessard; David Plew; S. Elizabeth Graham; Angus R. McIntosh (Ecosystems, 2014)

Surface antigen profiles of leukocytes and melanoma cells in lymph node metastases are associated with survival in AJCC stage III melanoma patients - Kimberley L. Kaufman; Swetlana Mactier; Nicola J. Armstrong; Duthika Mallawaaratchy; Scott N. Byrne; Lauren E. Haydu; Valerie Jakrot; John F. Thompson; Graham J. Mann; Richard A. Scolyer; Richard I. Christopherson (Clinical & Experimental Metastasis, 2014)

The history and dynamics of a welded pyroclastic dam and its failure - Graham D. M. Andrews; James K. Russell; Martin L. Stewart (Bulletin of Volcanology, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Characterisation of thirteen polymorphic microsatellite markers for the red sea urchin Heliocidaris tuberculata (Lamarck, 1816) developed using a 454-sequencing approach - Mailie L. Gall; Paul Rymer; Graham Edgar; Maria Byrne; Sebastian P. Holmes (Conservation Genetics Resources, 2014)

The ancient B ritons: groundwater fauna survived extreme climate change over tens of millions of years across NW E urope - Caitríona E. McInerney; Louise Maurice; Anne L. Robertson; Lee R. F. D. Knight; Jörg Arnscheidt; Chris Venditti; James S. G. Dooley; Thomas Mathers; Severine Matthijs; Karin Eriksson; Graham S. Proudlove; Bernd Hänfling (Molecular Ecology, 2014)
Global climate changes during the C enozoic (65.5–0 Ma) caused major biological range shifts and extinctions. In northern E urope, for example, a pattern of few endemics and the dominance of wide‐ranging species is thought to have been determined by the P leistocene (2.59–0.01 Ma) glaciations. This study, in contrast, reveals an ancient subsurface fauna endemic to B ritain and I reland. Using a B ayesian phylogenetic approach, we found that two species of stygobitic invertebrates (genus N iphargus ) have not only survived the entire P leistocene in refugia but have persisted for at least 19.5 million years. Other N iphargus species form distinct cryptic taxa that diverged from their nearest continental relative between 5.6 and 1.0 Ma. The study also reveals an unusual biogeographical pattern in the N iphargus genus. It originated in north‐west E urope approximately 87 Ma and underwent a gradual range expansion. Phylogenetic diversity and species age are highest in north‐west E urope, suggesting resilience to extreme climate change and strongly contrasting the patterns seen in surface fauna. However, species diversity is highest in south‐east E urope, indicating that once the genus spread to these areas (approximately 25 Ma), geomorphological and climatic conditions enabled much higher diversification. Our study highlights that groundwater ecosystems provide an important contribution to biodiversity and offers insight into the interactions between biological and climatic processes.

Discontinuities, cross‐scale patterns, and the organization of ecosystems - Kirsty L. Nash; Craig R. Allen; David G. Angeler; Chris Barichievy; Tarsha Eason; Ahjond S. Garmestani; Nicholas A. J. Graham; Dean Granholm; Melinda Knutson; R. John Nelson; Magnus Nyström; Craig A. Stow; et al. (Ecology, 2014)
Ecological structures and processes occur at specific spatiotemporal scales, and interactions that occur across multiple scales mediate scale‐specific (e.g., individual, community, local, or regional) responses to disturbance. Despite the importance of scale, explicitly incorporating a multi‐scale perspective into research and management actions remains a challenge. The discontinuity hypothesis provides a fertile avenue for addressing this problem by linking measureable proxies to inherent scales of structure within ecosystems. Here we outline the conceptual framework underlying discontinuities and review the evidence supporting the discontinuity hypothesis in ecological systems. Next we explore the utility of this approach for understanding cross‐scale patterns and the organization of ecosystems by describing recent advances for examining nonlinear responses to disturbance and phenomena such as extinctions, invasions, and resilience. To stimulate new research, we present methods for performing discontinuity analysis, detail outstanding knowledge gaps, and discuss potential approaches for addressing these gaps.

Multiple felsic events within post-10 Ma volcanism, Southeast Australia: inputs in appraising proposed magmatic models - F. L. Sutherland; I. T. Graham; J. D. Hollis; S. Meffre; H. Zwingmann; F. Jourdan; R. E. Pogson (Australian Journal of Earth Sciences, 2014)

How flies respond to honey bee pheromone: the role of the foraging gene on reproductive response to queen mandibular pheromone - Alison L. Camiletti; David N. Awde; Graham J. Thompson (The Science of Nature, 2014)

Quantification of seasonal sediment and phosphorus transport dynamics in an agricultural watershed using radiometric fingerprinting techniques - Natalie L. H. Huisman; K. G. Karthikeyan; Jasmeet Lamba; Anita M. Thompson; Graham Peaslee (Journal of Soils and Sediments, 2013)

Diffusional conductances to CO2 as a target for increasing photosynthesis and photosynthetic water-use efficiency - Jaume Flexas; Ülo Niinemets; Alexander Gallé; Margaret M. Barbour; Mauro Centritto; Antonio Diaz-Espejo; Cyril Douthe; Jeroni Galmés; Miquel Ribas-Carbo; Pedro L. Rodriguez; Francesc Rosselló; Raju Soolanayakanahally; et al. (Photosynthesis Research, 2013)

Can synchronizing feather-based measures of corticosterone and stable isotopes help us better understand habitat–physiology relationships? - Graham D. Fairhurst; Matthias Vögeli; David Serrano; Antonio Delgado; José L. Tella; Gary R. Bortolotti (Oecologia, 2013)

Ecological niche segregation among five toothed whale species off the NW Iberian Peninsula using ecological tracers as multi-approach - Paula Méndez-Fernandez; Graham J. Pierce; Paco Bustamante; Tiphaine Chouvelon; Marisa Ferreira; Angel F. González; Alfredo López; Fiona L. Read; M. Begoña Santos; Jérôme Spitz; José V. Vingada; Florence Caurant (Marine Biology, 2013)

Shorea balangeran and Dyera polyphylla (syn. Dyera lowii) as tropical peat swamp forest restoration transplant species: effects of mycorrhizae and level of disturbance - Laura L. B. Graham; Maman Turjaman; Susan E. Page (Wetlands Ecology and Management, 2013)

Effects of delayed settlement on post-settlement growth and survival of scleractinian coral larvae - Erin M. Graham; Andrew H. Baird; Bette L. Willis; Sean R. Connolly (Oecologia, 2013)

Functional Brain Abnormalities During Finger-Tapping in HIV-Infected Older Adults: A Magnetoencephalography Study - Tony W. Wilson; Elizabeth Heinrichs-Graham; Kevin R. Robertson; Uriel Sandkovsky; Jennifer O’Neill; Nichole L. Knott; Howard S. Fox; Susan Swindells (Journal of Neuroimmune Pharmacology, 2013)

Adenosine Triphosphate Released from HIV-Infected Macrophages Regulates Glutamatergic Tone and Dendritic Spine Density on Neurons - Luis B. Tovar-y-Romo; Dennis L. Kolson; Veera Venkata Ratnam Bandaru; Julia L. Drewes; David R. Graham; Norman J. Haughey (Journal of Neuroimmune Pharmacology, 2013)

Replication and fine mapping of asthma-associated loci in individuals of African ancestry - David B. Kantor; Cameron D. Palmer; Taylor R. Young; Yan Meng; Zofia K. Gajdos; Helen Lyon; Alkes L. Price; Samuela Pollack; Stephanie J. London; Laura R. Loehr; Lewis J. Smith; Rajesh Kumar; et al. (Human Genetics, 2013)

Increased Generation of Cyclopentenone Prostaglandins after Brain Ischemia and Their Role in Aggregation of Ubiquitinated Proteins in Neurons - Hao Liu; Wenjin Li; Muzamil Ahmad; Marie E. Rose; Tricia M. Miller; Mei Yu; Jie Chen; Jordan L. Pascoe; Samuel M. Poloyac; Robert W. Hickey; Steven H. Graham (Neurotoxicity Research, 2013)

Dietary intake of B vitamins and methionine and breast cancer risk - Julie K. Bassett; Laura Baglietto; Allison M. Hodge; Gianluca Severi; John L. Hopper; Dallas R. English; Graham G. Giles (Cancer Causes & Control, 2013)

Design and test of a model-assisted participatory process for the formulation of a local climate adaptation plan - Lotta Andersson; Julie Wilk; L. Phil Graham; Michele Warburton (Climate and Development, 2013)

No evidence for cumulative effects in a Dnmt3b hypomorph across multiple generations - Neil A. Youngson; Trevor Epp; Amity R. Roberts; Lucia Daxinger; Alyson Ashe; Edward Huang; Krystal L. Lester; Sarah K. Harten; Graham F. Kay; Timothy Cox; Jacqueline M. Matthews; Suyinn Chong; et al. (Mammalian Genome, 2013)

Rapid declines in metabolism explain extended coral larval longevity - E. M. Graham; A. H. Baird; S. R. Connolly; M. A. Sewell; B. L. Willis (Coral Reefs, 2013)

The importance of structural complexity in coral reef ecosystems - N. A. J. Graham; K. L. Nash (Coral Reefs, 2013)

Allergy and brain tumors in the INTERPHONE study: pooled results from Australia, Canada, France, Israel, and New Zealand - Michelle C. Turner; Daniel Krewski; Bruce K. Armstrong; Angela Chetrit; Graham G. Giles; Martine Hours; Mary L. McBride; Marie-Élise Parent; Siegal Sadetzki; Jack Siemiatycki; Alistair Woodward; Elisabeth Cardis (Cancer Causes & Control, 2013)

Ancient DNA supports southern survival of R ichardson's collared lemming ( D icrostonyx richardsoni ) during the last glacial maximum - Tara L. Fulton; Ryan W. Norris; Russell W. Graham; Holmes A. Semken; Beth Shapiro (Molecular Ecology, 2013)
Collared lemmings (genus D icrostonyx ) are circumpolar A rctic arvicoline rodents associated with tundra. However, during the last glacial maximum ( LGM ), D icrostonyx lived along the southern ice margin of the L aurentide ice sheet in communities comprising both temperate and boreal species. To better understand these communities and the fate of these southern individuals, we compare mitochondrial cytochrome b sequence data from three LGM ‐age D icrostonyx fossils from south of the L aurentide ice sheet to sequences from modern Dicrostonyx sampled from across their present‐day range. We test whether the D icrostonyx populations from LGM ‐age continental USA became extinct at the P leistocene– H olocene transition ~11000 years ago or, alternatively, if they belong to an extant species whose habitat preferences can be used to infer the palaeoclimate along the glacial margin. Our results indicate that LGM ‐age D icrostonyx from I owa and S outh D akota belong to D icrostonyx richardsoni , which currently lives in a temperate tundra environment west of Hudson Bay, Canada. This suggests a palaeoclimate south of the Laurentide ice sheet that contains elements similar to the more temperate shrub tundra characteristic of extant D . richardsoni habitat, rather than the very cold, dry tundra of the N orthern A rctic. While more data are required to determine whether or not the LGM southern population is ancestral to extant D . richardsoni , it seems most probable that the species survived the LGM in a southern refugium.

A road map for molecular ecology - Rose L. Andrew; Louis Bernatchez; Aurélie Bonin; C. Alex. Buerkle; Bryan C. Carstens; Brent C. Emerson; Dany Garant; Tatiana Giraud; Nolan C. Kane; Sean M. Rogers; Jon Slate; Harry Smith; et al. (Molecular Ecology, 2013)
The discipline of molecular ecology has undergone enormous changes since the journal bearing its name was launched approximately two decades ago. The field has seen great strides in analytical methods development, made groundbreaking discoveries and experienced a revolution in genotyping technology. Here, we provide brief perspectives on the main subdisciplines of molecular ecology, describe key questions and goals, discuss common challenges, predict future research directions and suggest research priorities for the next 20 years.

Cross-scale Habitat Structure Drives Fish Body Size Distributions on Coral Reefs - Kirsty L. Nash; Nicholas A. J. Graham; Shaun K. Wilson; David R. Bellwood (Ecosystems, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Diatom-inferred late Pleistocene and Holocene palaeolimnological changes in the Ioannina basin, northwest Greece - Timothy D. Jones; Ian T. Lawson; Jane M. Reed; Graham P. Wilson; Melanie J. Leng; Merle Gierga; Stefano M. Bernasconi; Rienk H. Smittenberg; Irka Hajdas; Charlotte L. Bryant; P. C. Tzedakis (Journal of Paleolimnology, 2013)

Detecting genes for variation in parasite burden and immunological traits in a wild population: testing the candidate gene approach - E. A. Brown; J. G. Pilkington; D. H. Nussey; K. A. Watt; A. D. Hayward; R. Tucker; A. L. Graham; S. Paterson; D. Beraldi; J. M. Pemberton; J. Slate (Molecular Ecology, 2013)
Identifying the genes underlying phenotypic variation in natural populations can provide novel insight into the evolutionary process. The candidate gene approach has been applied to studies of a number of traits in various species, in an attempt to elucidate their genetic basis. Here, we test the application of the candidate gene approach to identify the loci involved in variation in gastrointestinal parasite burden, a complex trait likely to be controlled by many loci, in a wild population of S oay sheep. A comprehensive literature review, G ene O ntology databases, and comparative genomics resources between cattle and sheep were used to generate a list of candidate genes. In a pilot study, these candidates, along with 50 random genes, were then sequenced in two pools of S oay sheep; one with low gastrointestinal nematode burden and the other high, using a N imble G en sequence capture experiment. Further candidates were identified from single nucleotide polymorphisms ( SNP s) that were highly differentiated between high‐ and low‐resistance sheep breeds. A panel of 192 candidate and control SNP s were then typed in 960 individual S oay sheep to examine whether they individually explained variation in parasite burden, as measured as faecal egg count, as well as two immune measures ( T eladorsagia circumcincta ‐specific antibodies and antinuclear antibodies). The cumulative effect of the candidate and control SNP s were estimated by fitting genetic relationship matrices ( GRM s) as random effects in animal models of the three traits. No more significant SNP s were identified in the pilot sequencing experiment and association study than expected by chance. Furthermore, no significant difference was found between the proportions of candidate or control SNP s that were found to be significantly associated with parasite burden/immune measures. No significant effect of the candidate or control gene GRM s was found. There is thus little support for the candidate gene approach to the identification of loci explaining variation in parasitological and immunological traits in this population. However, a number of SNP s explained significant variation in multiple traits and significant correlations were found between the proportions of variance explained by individual SNP s across multiple traits. The significant SNP s identified in this study may still, therefore, merit further investigation.

Protective Effects of 7,8-Dihydroxyflavone on Retinal Ganglion and RGC-5 Cells Against Excitotoxic and Oxidative Stress - Vivek K. Gupta; Yuyi You; Jonathan C. Li; Alexander Klistorner; Stuart L. Graham (Journal of Molecular Neuroscience, 2013)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Long‐term change in the abundances of northern Gulf of Mexico scyphomedusae Chrysaora sp. and Aurelia spp. with links to climate variability - Kelly L. Robinson; William M. Graham (Limnology and Oceanography, 2013)
Variability in northern Gulf of Mexico Chrysaora sp. and Aurelia spp. abundance and distribution over time and in relation to climate forces operating at large and regional scales was analyzed using two multi‐decadal data sets derived from trawl data collected during fisheries‐independent surveys conducted each summer (1987–2007) and fall (1985–2007). Populations exhibited remarkable increases and decreases in size during the past two decades. During peak years, an estimated mean (± 1 SD) total 4.4 (1.5) billion Chrysaora sp. and 9.6 (0.9) billion Aurelia spp. occurred during summer (May–July) and fall (October–November), respectively. Earlier reported increases in jellyfish abundance have not continued; however, the frequency of Chrysaora sp. in trawls has increased with time. Jellyfish “hot spots” are waters southwest of Mobile Bay, west of the Mississippi River outflow, and near the Louisiana‐Texas border. “Cold spots” occurred in waters > 40 m in depth. Annual variations in Chrysaora sp. and Aurelia spp. abundance were temporally coherent, suggesting a common set of environmental drivers. Jellyfish abundance was positively related to the El Niño Southern Oscillation, Atlantic Multi‐decadal Oscillation, and Pacific Decadal Oscillation and was negatively related to the Great Plains Lower Level Jet. Jellyfish were also more abundant when regional sea surface temperatures were cooler than average in spring and warmer than average in summer‐early fall. Increased jellyfish production occurred during years when the northern Gulf experienced wet and warm winters, dry and cool springs, and wet and warm summers and when the Mississippi River watershed experienced dry winters, wet springs, and wet summers.

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Screening practices of Australian men and women categorized as “at or slightly above average risk” of colorectal cancer - Driss Ait Ouakrim; Trevor Lockett; Alex Boussioutas; Louise Keogh; Louisa B. Flander; Ingrid Winship; Graham G. Giles; John L. Hopper; Mark A. Jenkins (Cancer Causes & Control, 2012)

Passive-margin prolonged volcanism, East Australian Plate: outbursts, progressions, plate controls and suggested causes - F. L. Sutherland; I. T. Graham; S. Meffre; H. Zwingmann; R. E. Pogson (Australian Journal of Earth Sciences, 2012)

2,3-Hexanediols as Sex Attractants and a Female-produced Sex Pheromone for Cerambycid Beetles in the Prionine Genus Tragosoma - Ann M. Ray; James D. Barbour; J. Steven McElfresh; Jardel A. Moreira; Ian Swift; Ian M. Wright; Alenka Žunič; Robert F. Mitchell; Elizabeth E. Graham; Ronald L. Alten; Jocelyn G. Millar; Lawrence M. Hanks (Journal of Chemical Ecology, 2012)

Non-invasive Estimation of Cerebrospinal Fluid Pressure Waveforms by Means of Retinal Venous Pulsatility and Central Aortic Blood Pressure - S. Mojtaba Golzan; Mi Ok Kim; Amir Saied Seddighi; Alberto Avolio; Stuart L. Graham (Annals of Biomedical Engineering, 2012)

W olbachia in a major African crop pest increases susceptibility to viral disease rather than protects - Robert I. Graham; David Grzywacz; Wilfred L. Mushobozi; Kenneth Wilson (Ecology Letters, 2012)
W olbachia are common vertically transmitted endosymbiotic bacteria found in S podoptera exempta ), which show that the prevalence and intensity of infection with a nucleopolydrovirus ( SpexNPV ) is positively associated with infection with three strains of W olbachia . We also use laboratory bioassays to demonstrate that infection with one of these strains, a male‐killer, increases host mortality due to SpexNPV by 6–14 times. These findings suggest that rather than protecting their lepidopteran host from viral infection, W olbachia instead make them more susceptible. This finding potentially has implications for the biological control of other insect crop pests.

Genetic analysis of an endemic archipelagic lizard reveals sympatric cryptic lineages and taxonomic discordance - R. Graham Reynolds; Matthew L. Niemiller; Benjamin M. Fitzpatrick (Conservation Genetics, 2012)

Global patterns in the impact of marine herbivores on benthic primary producers - Alistair G. B. Poore; Alexandra H. Campbell; Ross A. Coleman; Graham J. Edgar; Veijo Jormalainen; Pamela L. Reynolds; Erik E. Sotka; John J. Stachowicz; Richard B. Taylor; Mathew A. Vanderklift; J. Emmett Duffy (Ecology Letters, 2012)
Despite the importance of consumers in structuring communities, and the widespread assumption that consumption is strongest at low latitudes, empirical tests for global scale patterns in the magnitude of consumer impacts are limited. In marine systems, the long tradition of experimentally excluding herbivores in their natural environments allows consumer impacts to be quantified on global scales using consistent methodology. We present a quantitative synthesis of 613 marine herbivore exclusion experiments to test the influence of consumer traits, producer traits and the environment on the strength of herbivore impacts on benthic producers. Across the globe, marine herbivores profoundly reduced producer abundance (by 68% on average), with strongest effects in rocky intertidal habitats and the weakest effects on habitats dominated by vascular plants. Unexpectedly, we found little or no influence of latitude or mean annual water temperature. Instead, herbivore impacts differed most consistently among producer taxonomic and morphological groups. Our results show that grazing impacts on plant abundance are better predicted by producer traits than by large‐scale variation in habitat or mean temperature, and that there is a previously unrecognised degree of phylogenetic conservatism in producer susceptibility to consumption.

Untangling the influence of ecological and evolutionary factors on trait variation across hummingbird assemblages - Catherine H. Graham; Juan L. Parra; Boris A. Tinoco; F. Gary Stiles; Jim A. McGuire (Ecology, 2012)
Phylogenetic community ecology combines phylogenetic hypotheses with local species composition and functional‐trait information to evaluate historical and contemporary mechanisms influencing local assemblage structure. Most studies assume that, if functional traits are conserved, then patterns of trait variation should match patterns of phylogenetic structure within local assemblages. Here we evaluated if we could predict trait structure by assuming that environmental filtering or biotic interactions work primarily on phylogenetically conserved functional traits. We investigated patterns of phylogenetic assemblage structure and functional‐trait variation in bill length, wing length, and body mass in 236 hummingbird assemblages (126 species) across two major gradients in northern South America: elevation and precipitation. While mean trait values for assemblages vary predictably based on empirical knowledge of hummingbird biology, the distribution of trait values within assemblages do not correspond to those predicted based on phylogenetic signal and phylogenetic structure. Instead, we were able to identify instances where assemblages have high levels of morphological variation despite their close evolutionary relatedness and vice versa. Our results provide support for both filtering and biotic interactions across gradients, as has been documented in other studies.

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Early Minocycline Treatment Prevents a Decrease in Striatal Dopamine in an SIV Model of HIV-Associated Neurological Disease - Kelly A. Meulendyke; Mikhail V. Pletnikov; Elizabeth L. Engle; Patrick M. Tarwater; David R. Graham; M. Christine Zink (Journal of Neuroimmune Pharmacology, 2012)

Hybridization between two gartersnake species (Thamnophis) of conservation concern: a threat or an important natural interaction? - John S. Placyk; Benjamin M. Fitzpatrick; Gary S. Casper; Randall L. Small; R. Graham Reynolds; Daniel W. A. Noble; Ronald J. Brooks; Gordon M. Burghardt (Conservation Genetics, 2012)

Dietary intake of B vitamins and methionine and prostate cancer incidence and mortality - Julie K. Bassett; Gianluca Severi; Allison M. Hodge; Laura Baglietto; John L. Hopper; Dallas R. English; Graham G. Giles (Cancer Causes & Control, 2012)

An assessment of the utility of regional diatom‐based tidal‐level transfer functions - Graham P. Wilson; Angela L. Lamb (Journal of Quaternary Science, 2012)
In order to understand natural sea‐level variability, and to enhance future predictions, accurate and precise estimates of Holocene tidal levels are required. Although the application of diatom‐based transfer functions can yield such data, these work best when underpinned by local training sets. Urbanized estuaries offer little prospect of obtaining local training sets and, instead, the reliability of regional transfer functions has to be assessed. The performance of a published regional (UK) diatom‐based tidal‐level transfer function applied to fossil assemblages from two contrasting core sites in the Mersey Estuary, UK, is assessed using modern analogue techniques and sediment isotope data. We find that, although estimated tidal levels coincide with changes in organic matter source, the frequent lack of modern analogues mean that palaeotide estimates are without basis. This is likely a consequence of the site‐specific nature of diatom assemblages in higher intertidal and supratidal areas in particular, where local factors are expected to exert a greater control on their ecology. This situation may be partly resolved by constructing and applying much larger regional training sets from multiple higher intertidal and supratidal sites (where intact). Otherwise the application of alternative techniques, such as regional foraminiferal tidal‐level transfer functions, may be more appropriate. Copyright © 2011 John Wiley & Sons, Ltd.

Factors affecting reproduction in rehabilitant female orangutans: young age at first birth and short inter-birth interval - Noko Kuze; David Dellatore; Graham L. Banes; Peter Pratje; Tomoyuki Tajima; Anne E. Russon (Primates, 2012)

Hoarding behavior by ship rats (Rattus rattus) in captivity and its relevance to the effectiveness of pest control operations - Grant A. Morriss; Bruce Warburton; Martin L. Cross; Graham Nugent (European Journal of Wildlife Research, 2012)

Mercury Levels in Sediments and Mangrove Oysters, Crassostrea rizophorae, from the North Coast of Villa Clara, Cuba - S. Olivares-Rieumont; L. Lima; S. Rivero; D. W. Graham; C. Alonso-Hernandez; Y. Bolaño (Bulletin of Environmental Contamination and Toxicology, 2012)

Mapping the biosphere: exploring species to understand the origin, organization and sustainability of biodiversity - Q. D. Wheeler; S. Knapp; D. W. Stevenson; J. Stevenson; S. D. Blum; B. M. Boom; G. G. Borisy; J. L. Buizer; M. R. De Carvalho; A. Cibrian; M. J. Donoghue; V. Doyle; et al. (Systematics and Biodiversity, 2012)

Does lycopene offer human LDL any protection against myeloperoxidase activity? - Poh Yeong Chew; Lucy Riley; Daniel L. Graham; Khalid Rahman; Gordon M. Lowe (Molecular and Cellular Biochemistry, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

What can DNA tell us about biological invasions? - Benjamin M. Fitzpatrick; James A. Fordyce; Matthew L. Niemiller; R. Graham Reynolds (Biological Invasions, 2012)

The effect of material choice on biofilm formation in a model warm water distribution system - Paul L. Waines; Roy Moate; A. John Moody; Mike Allen; Graham Bradley (Biofouling, 2011)

Erasing injury-related cortical synaptic potentiation as a new treatment for chronic pain - Xiang-Yao Li; Hyoung-Gon Ko; Tao Chen; Graham L. Collingridge; Bong-Kiun Kaang; Min Zhuo (Journal of Molecular Medicine, 2011)

Lifetime physical activity and the incidence of proliferative benign breast disease - Michelle M. Jung; Graham A. Colditz; Laura C. Collins; Stuart J. Schnitt; James L. Connolly; Rulla M. Tamimi (Cancer Causes & Control, 2011)

On the information expressed in enzyme structure: more lessons from ribonuclease A - Daniel J. Graham; Jessica L. Greminger (Molecular Diversity, 2011)

The pro-apoptotic BH3-only protein Bid is dispensable for development of insulitis and diabetes in the non-obese diabetic mouse - Zia U. A. Mollah; Jibran Wali; Mark D. McKenzie; Balasubramanian Krishnamurthy; Kate L. Graham; Stacey Fynch; Joshua Szanyi; Pere Santamaria; Thomas Brodnicki; Janette Allison; Andreas Strasser; Thomas W. H. Kay; et al. (Apoptosis, 2011)

Agrobacterium-mediated transient expression in citrus leaves: a rapid tool for gene expression and functional gene assay - Jose F. L. Figueiredo; Patrick Römer; Thomas Lahaye; James H. Graham; Frank F. White; Jeffrey B. Jones (Plant Cell Reports, 2011)

Submarine hydrothermal activity and gold-rich mineralization at Brothers Volcano, Kermadec Arc, New Zealand - Cornel E. J. de Ronde; Gary J. Massoth; David A. Butterfield; Bruce W. Christenson; Junichiro Ishibashi; Robert G. Ditchburn; Mark D. Hannington; Robert L. Brathwaite; John E. Lupton; Vadim S. Kamenetsky; Ian J. Graham; Georg F. Zellmer; et al. (Mineralium Deposita, 2011)

Green tea polyphenols avert chronic inflammation-induced myocardial fibrosis of female rats - Chwan-Li Shen; Christina Samathanam; Owatha L. Tatum; Suzanne Graham; Christine Tubb; Jay J. Cao; Dale M. Dunn; Jia-Sheng Wang (Inflammation Research, 2011)

Lack of effect of hydrochlorothiazide and low-dose aspirin on the renal clearance of urate and oxypurinol after a single dose of allopurinol in normal volunteers - Daniel Y. Ng; Sophie L. Stocker; Garry G. Graham; Kenneth M. Williams; Richard O. Day (European Journal of Clinical Pharmacology, 2011)

Mutational analysis of type III effector genes from Xanthomonas citri subsp. citri - Jose Francisco L. Figueiredo; Gerald V. Minsavage; James H. Graham; Frank F. White; Jeffrey B. Jones (European Journal of Plant Pathology, 2011)

Coral reef recovery dynamics in a changing world - N. A. J. Graham; K. L. Nash; J. T. Kool (Coral Reefs, 2011)

Early-life sun exposure and risk of melanoma before age 40 years - Anne E. Cust; Mark A. Jenkins; Chris Goumas; Bruce K. Armstrong; Helen Schmid; Joanne F. Aitken; Graham G. Giles; Richard F. Kefford; John L. Hopper; Graham J. Mann (Cancer Causes & Control, 2011)

Macrophages from lupus-prone MRL mice have a conditional signaling abnormality that leads to dysregulated expression of numerous genes - Angelika Antoni; Vimal A. Patel; Hanli Fan; Daniel J. Lee; Lee H. Graham; Cristen L. Rosch; Daniel S. Spiegel; Joyce Rauch; Jerrold S. Levine (Immunogenetics, 2011)

Abundance and site fidelity of Indo‐Pacific Humpback dolphins in the Great Sandy Strait, Queensland, Australia - Daniele De Biasi Cagnazzi; Peter L. Harrison; Graham J. B. Ross; Peter Lynch (Marine Mammal Science, 2011)
This study examined the population of Indo‐Pacific humpback dolphins, Sousa chinensis , inhabiting the Great Sandy Strait Marine Park, Queensland, Australia. A total of 106 dolphins were identified during 228 boat‐based surveys, completed between April 2004 and April 2007. Based on the distribution of resighted individuals and the pattern of associations, it was established that this population consists of two largely geographically distinct communities, referred to as the Northern Community (NC) and the Southern Community (SC). The only recorded interaction between the two groups was a single pod composed of one member of the NC and 11 dolphins from the SC. Abundance was estimated for the entire population and by geographical area using open population models. Estimates for the Great Sandy Strait indicate that about 150 dolphins ( N GSS = 148.4, SE = 8.3, 95% CI: 132.5–165.2) used this area during the study. The NC and SC total population sizes was estimated to be 76 ( N NGSS = 75.80, SE = 3.88, 95% CI = 71–86) and 75 ( N SGSS = 74.98, SE = 4.43, 95% CI: 66–83), respectively. Analysis of residence patterns indicates that a majority of the identified dolphins are long‐term residents.

Risso's dolphins alter daily resting pattern in response to whale watching at the Azores - Fleur Visser; Karin L. Hartman; Ente J. J. Rood; Arthur J. E. Hendriks; Daan B. Zult; Wim J. Wolff; Jef Huisman; Graham J. Pierce (Marine Mammal Science, 2011)
Behavioral responses of Risso's dolphins ( Grampus griseus ) to whale watching vessels were studied off Pico Island, Azores. Dolphin behavior was studied from a land‐based lookout, enabling observations of groups in the absence and presence of vessels. The number of whale watching vessels showed a clear seasonal pattern, dividing the whale watching period into a low season and a high season. During the low season, Risso's dolphins rested mainly in the morning and afternoon. During the high season, Risso's dolphins rested less and did so mainly at noon, when the number of active vessels was lowest. Data analysis using a generalized additive mixed model indicated that this change in resting behavior was associated with vessel abundance. When more than five vessels were present, Risso's dolphins spent significantly less time resting and socializing. During the high season, this vessel abundance was exceeded during 20% of observation days. While we cannot be sure that the observed changes in behavior have fitness consequences for Risso's dolphins, reduced resting and socializing rates can have negative impacts on the build‐up of energy reserves and on reproductive success. We suggest the adoption of precautionary management measures to regulate the timing and intensity of whale watching activities.

Cohorts and consortia conference: a summary report (Banff, Canada, June 17–19, 2009) - Paolo Boffetta; Graham A. Colditz; John D. Potter; Laurence Kolonel; Paula J. Robson; Reza Malekzadeh; Daniela Seminara; Ellen L. Goode; Keun-Young Yoo; Paul Demers; Richard Gallagher; Ross Prentice; et al. (Cancer Causes & Control, 2011)

How Clustering Dynamics Influence Lumber Utilization Patterns in the Amish-Based Furniture Industry in Ohio - Matthew S. Bumgardner; Gary W. Graham; P. Charles Goebel; Robert L. Romig (Journal of Forestry, 2011)
Preliminary studies have suggested that the Amish-based furniture and related products manufacturing cluster located in and around Holmes County, Ohio, uses sizeable quantities of hardwood lumber. The number of firms within the cluster has grown even as the broader domestic furniture manufacturing sector has contracted. The present study was undertaken in 2008 (spring/summer) to develop lumber use estimates specific to Amish manufacturing and provide more detail regarding the impacts of clustering on lumber consumption patterns. Results, based on 196 firms responding to a survey, suggested that lumber use ratios (bd ft per employee) differed among firms of different sizes and type of product manufactured, but in aggregate was similar to the broader US furniture industry. Red oak was the most commonly used species. Local suppliers of hardwood lumber and components were used extensively by most firms. The study confirmed that the Holmes County furniture cluster was important to regional hardwood demand, facilitated by well-developed supply chains that enable high specialization and enhance aggregate productivity among the numerous small manufacturers.

Initiation of HAART during acute simian immunodeficiency virus infection rapidly controls virus replication in the CNS by enhancing immune activity and preserving protective immune responses - David R. Graham; Lucio Gama; Suzanne E. Queen; Ming Li; Angela K. Brice; Kathleen M. Kelly; Joseph L. Mankowski; Janice E. Clements; M. Christine Zink (Journal of NeuroVirology, 2011)

The effects of a respiratory warm-up on the physical capacity and ventilatory response in paraplegic individuals - Christof A. Leicht; Paul M. Smith; Graham Sharpe; Claudio Perret; Victoria L. Goosey-Tolfrey (European Journal of Applied Physiology, 2010)

Physical activity, body size and composition, and risk of ovarian cancer - Fiona Chionh; Laura Baglietto; Kavitha Krishnan; Dallas R. English; Robert J. MacInnis; Dorota M. Gertig; John L. Hopper; Graham G. Giles (Cancer Causes & Control, 2010)

On the information expressed in enzyme primary structure: lessons from Ribonuclease A - Daniel J. Graham; Jessica L. Greminger (Molecular Diversity, 2010)

Pooled analyses of 13 prospective cohort studies on folate intake and colon cancer - Dong-Hyun Kim; Stephanie A. Smith-Warner; Donna Spiegelman; Shiaw-Shyuan Yaun; Graham A. Colditz; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Saxon Graham; Lisa Harnack; Eric J. Jacobs; Michael Leitzmann; et al. (Cancer Causes & Control, 2010)

Back to nature: ecological genomics of loblolly pine ( Pinus taeda , Pinaceae) - ANDREW J. ECKERT; ANDREW D. BOWER; SANTIAGO C. GONZÁLEZ‐MARTÍNEZ; JILL L. WEGRZYN; GRAHAM COOP; DAVID B. NEALE (Molecular Ecology, 2010)
Genetic variation is often arrayed in latitudinal or altitudinal clines, reflecting either adaptation along environmental gradients, migratory routes, or both. For forest trees, climate is one of the most important drivers of adaptive phenotypic traits. Correlations of single and multilocus genotypes with environmental gradients have been identified for a variety of forest trees. These correlations are interpreted normally as evidence of natural selection. Here, we use a genome‐wide dataset of single nucleotide polymorphisms (SNPs) typed from 1730 loci in 682 loblolly pine ( Pinus taeda L.) trees sampled from 54 local populations covering the full‐range of the species to examine allelic correlations to five multivariate measures of climate. Applications of a Bayesian generalized linear mixed model, where the climate variable was a fixed effect and an estimated variance–covariance matrix controlled random effects due to shared population history, identified several well‐supported SNPs associating to principal components corresponding to geography, temperature, growing degree‐days, precipitation and aridity. Functional annotation of those genes with putative orthologs in Arabidopsis revealed a diverse set of abiotic stress response genes ranging from transmembrane proteins to proteins involved in sugar metabolism. Many of these SNPs also had large allele frequency differences among populations ( F ST = 0.10–0.35). These results illustrate a first step towards a ecosystem perspective of population genomics for non‐model organisms, but also highlight the need for further integration of the methodologies employed in spatial statistics, population genetics and climate modeling during scans for signatures of natural selection from genomic data.

Interleukin-22 genetic polymorphisms and risk of colon cancer - Cheryl L. Thompson; Sarah J. Plummer; Thomas C. Tucker; Graham Casey; Li Li (Cancer Causes & Control, 2010)

Intake of fiber and nuts during adolescence and incidence of proliferative benign breast disease - Xuefen Su; Rulla M. Tamimi; Laura C. Collins; Heather J. Baer; Eunyoung Cho; Laura Sampson; Walter C. Willett; Stuart J. Schnitt; James L. Connolly; Bernard A. Rosner; Graham A. Colditz (Cancer Causes & Control, 2010)

The Complement of Soluble Sugars in the Saccharum Complex - Donna Glassop; Louise P. Ryan; Graham D. Bonnett; Anne L. Rae (Tropical Plant Biology, 2010)

Prospective longitudinal studies of salmonid alphavirus infections on two Atlantic salmon farms in Ireland; evidence for viral persistence - D A Graham; E Fringuelli; C Wilson; H M Rowley; A Brown; H Rodger; M F McLoughlin; C McManus; E Casey; L J McCarthy; N M Ruane (Journal of Fish Diseases, 2010)
Prospective longitudinal studies of two outbreaks of pancreas disease in Atlantic salmon (AS), Salmo salar L., in Ireland were conducted. Both outbreaks occurred during the marine phase of production, with one caused by salmonid alphavirus subtype 1 (SAV1) and the other by SAV4. In addition to screening a range of tissues by real‐time reverse transcriptase polymerase chain reaction (RRT‐PCR), virological, serological and histopathological examinations were performed along with partial genome sequencing and results were related to environmental and production data and farm history. On Farm 1 (marine sampling only), infection was detected within 3 weeks of smolts being placed on the farm, while on Farm 2 (freshwater and marine sampling), infection was first detected 315 days after transfer to sea. In both outbreaks, RRT‐PCR signals were detected in a range of tissues including gill, heart, kidney, pancreas/pyloric caeca, brain and serum. Persistence of signal was longest in gill and heart (≥265 days on both farms) and shortest in serum. Mortalities on the two farms varied from 10.9% to 30%. In both cases, partial genome sequence of the causative viruses were identical to SAV strains detected in previous populations of AS on each of the study farms, including populations with which the study populations overlapped in time and space.

Disaster vulnerability and evacuation readiness: coastal mobile home residents in Florida - Margarethe Kusenbach; Jason L. Simms; Graham A. Tobin (Natural Hazards, 2010)

The Legacy of Agricultural Reclamation on Channel and Pool Networks of Bay of Fundy Salt Marshes - Graham K. MacDonald; Paula E. Noel; Danika van Proosdij; Gail L. Chmura (Estuaries and Coasts, 2010)

Climate‐related, decadal‐scale assemblage changes of seagrass‐associated fishes in the northern Gulf of Mexico - F. JOEL FODRIE; KENNETH L. HECK; SEAN P. POWERS; WILLIAM M. GRAHAM; KELLY L. ROBINSON (Global Change Biology, 2010)
Global temperatures are rising, and are expected to produce a poleward shift in the distribution of many organisms. We quantified changes in fish assemblages within seagrass meadows of the northern Gulf of Mexico (GOM) between the 1970s and 2006–2007, and observed changes consistent with this forecast. During 2006–2007 we sampled seagrass meadows using the same gears and methods previously employed by R. J. Livingston in coastal waters of northwest Florida throughout the 1970s. Comparisons between datasets revealed numerous additions to the fish fauna during 2006–2007 that were completely absent in the 1970s, including: Lutjanus synagris (lane snapper), Epinephelus morio (red grouper), Chaetodon ocellatus (spotfin butterflyfish), Mycteroperca sp (grouper, non gag), Centropristis philadelphica (rock sea bass), Fistularia tabacaria (bluespotted cornetfish), Ocyurus chrysurus (yellowtail snapper), Thalassoma bifasciatum (bluehead wrasse), Abudefduf saxatilis (sergeant major), Acanthuridae spp. (surgeonfishes) and Sparisoma viride (stoplight parrotfish). Several other species showed large increases in abundance during the interval between 1979 and 2006, including Mycteroperca microlepis (gag grouper, up ∼200 ×), Lutjanus griseus (gray snapper, up ∼105 ×), and Nicholsina usta (emerald parrotfish, up ∼22 ×). All of these are tropical or subtropical species that now make up a greater percentage of seagrass‐associated fish assemblages in the northern GOM than in the past. Additionally, we observed regional increases in air and sea surface temperatures (> 3 °C) during the ∼30 years that separate Livingston's samples and ours that correlate with northern shifts in the distribution of warm‐water fishes. Documenting these range shifts is a critical first step in investigating the consequences of global warming for endemic marine communities and fishery production in the northern GOM.

Gem-corundum megacrysts from east Australian basalt fields: trace elements, oxygen isotopes and origins∗ - F. L. Sutherland; K. Zaw; S. Meffre; G. Giuliani; A. E. Fallick; I. T. Graham; G. B. Webb (Australian Journal of Earth Sciences, 2009)

Photon echo studies of photosynthetic light harvesting - Elizabeth L. Read; Hohjai Lee; Graham R. Fleming (Photosynthesis Research, 2009)

Mass-spectrometric characterization of two posttranslational modifications of cysteine dioxygenase - Torsten Kleffmann; Seino A. K. Jongkees; Graham Fairweather; Sigurd M. Wilbanks; Guy N. L. Jameson (JBIC Journal of Biological Inorganic Chemistry, 2009)

Climate simulations of major estuarine watersheds in the Mid-Atlantic region of the US - R. Najjar; L. Patterson; S. Graham (Climatic Change, 2009)

Vulnerability of national economies to the impacts of climate change on fisheries - Edward H. Allison; Allison L. Perry; Marie‐Caroline Badjeck; W. Neil Adger; Katrina Brown; Declan Conway; Ashley S. Halls; Graham M. Pilling; John D. Reynolds; Neil L. Andrew; Nicholas K. Dulvy (Fish and Fisheries, 2009)
Anthropogenic global warming has significantly influenced physical and biological processes at global and regional scales. The observed and anticipated changes in global climate present significant opportunities and challenges for societies and economies. We compare the vulnerability of 132 national economies to potential climate change impacts on their capture fisheries using an indicator‐based approach. Countries in Central and Western Africa (e.g. Malawi, Guinea, Senegal, and Uganda), Peru and Colombia in north‐western South America, and four tropical Asian countries (Bangladesh, Cambodia, Pakistan, and Yemen) were identified as most vulnerable. This vulnerability was due to the combined effect of predicted warming, the relative importance of fisheries to national economies and diets, and limited societal capacity to adapt to potential impacts and opportunities. Many vulnerable countries were also among the world’s least developed countries whose inhabitants are among the world’s poorest and twice as reliant on fish, which provides 27% of dietary protein compared to 13% in less vulnerable countries. These countries also produce 20% of the world’s fish exports and are in greatest need of adaptation planning to maintain or enhance the contribution that fisheries can make to poverty reduction. Although the precise impacts and direction of climate‐driven change for particular fish stocks and fisheries are uncertain, our analysis suggests they are likely to lead to either increased economic hardship or missed opportunities for development in countries that depend upon fisheries but lack the capacity to adapt.

Functional Specialization of Vacuoles in Sugarcane Leaf and Stem - Anne L. Rae; Mark A. Jackson; Chau H. Nguyen; Graham D. Bonnett (Tropical Plant Biology, 2009)

Mobilisation and Transport of Sediment-Associated Phosphorus by Surface Runoff - Deborah Ballantine; Desmond E. Walling; Graham J. L. Leeks (Water, Air, & Soil Pollution, 2009)

Jellyfish in ecosystems, online databases, and ecosystem models - Daniel Pauly; William Graham; Simone Libralato; Lyne Morissette; M. L. Deng Palomares (Hydrobiologia, 2009)

Assessment of Total Mercury Levels in Clarias gariepinus from the Sagua la Grande River, Cuba - D. De La Rosa; L. Lima; S. Olivares-Rieumont; D. W. Graham; I. Enriquez; O. Diaz; J. M. Bastías; O. Muñoz (Bulletin of Environmental Contamination and Toxicology, 2009)

Dynamic secondary ion mass spectrometry imaging of microbial populations utilizing 13 C‐labelled substrates in pure culture and in soil - Graham M. Pumphrey; Buck T. Hanson; Subhash Chandra; Eugene L. Madsen (Environmental Microbiology, 2009)
Summary We demonstrate that dynamic secondary ion mass spectrometry (SIMS)‐based ion microscopy can provide a means of measuring 13 C assimilation into individual bacterial cells grown on 13 C‐labelled organic compounds in the laboratory and in field soil. We grew pure cultures of Pseudomonas putida NCIB 9816‐4 in minimal media with known mixtures of 12 C‐ and 13 C‐glucose and analysed individual cells via SIMS imaging. Individual cells yielded signals of masses 12, 13, 24, 25, 26 and 27 as negative secondary ions indicating the presence of 12 C – , 13 C – , 24 ( 12 C 2 ) – , 25 ( 12 C 13 C) – , 26 ( 12 C 14 N) – and 27 ( 13 C 14 N) – ions respectively. We verified that ratios of signals taken from the same cells only changed minimally during a ∼4.5 min period of primary O 2 + beam sputtering by the dynamic SIMS instrument in microscope detection mode. There was a clear relationship between mass 27 and mass 26 signals in Psuedomonas putida cells grown in media containing varying proportions of 12 C‐ to 13 C‐glucose: a standard curve was generated to predict 13 C‐enrichment in unknown samples. We then used two strains of Pseudomonas putida able to grow on either all or only a part of a mixture of 13 C‐labelled and unlabelled carbon sources to verify that differential 13 C signals measured by SIMS were due to 13 C assimilation into cell biomass. Finally, we made three key observations after applying SIMS ion microscopy to soil samples from a field experiment receiving 12 C‐ or 13 C‐phenol: (i) cells enriched in 13 C were heterogeneously distributed among soil populations; (ii) 13 C‐labelled cells were detected in soil that was dosed a single time with 13 C‐phenol; and (iii) in soil that received 12 doses of 13 C‐phenol, 27% of the cells in the total community were more than 90% 13 C‐labelled.

Species effects on ecosystem processes are modified by faunal responses to habitat composition - Mark T. Bulling; Martin Solan; Kirstie E. Dyson; Gema Hernandez-Milian; Patricia Luque; Graham J. Pierce; Dave Raffaelli; David M. Paterson; Piran C. L. White (Oecologia, 2008)

Erratum to Functional significance of intramandibular bending in Poeciliid fishes - Alice Gibb; Lara A. Ferry-Graham; L. Patricia Hernandez; Rebecca Romasco; Jessica Blanton (Environmental Biology of Fishes, 2008)

Functional significance of intramandibular bending in Poeciliid fishes - Alice Gibb; Lara A. Ferry-Graham; L. Patricia Hernandez; Rebecca Romansco; Jessica Blanton (Environmental Biology of Fishes, 2008)

A comparative assessment of molecular biological and direct microscopic techniques for assessing aquatic systems - C. W. Knapp; D. L. Findlay; K. A. Kidd; D. W. Graham (Environmental Monitoring and Assessment, 2008)

Quantitative trait loci for grain fructan concentration in wheat (Triticum aestivum L.) - Bao-Lam Huynh; Hugh Wallwork; James C. R. Stangoulis; Robin D. Graham; Kerrie L. Willsmore; Steven Olson; Diane E. Mather (Theoretical and Applied Genetics, 2008)

Historical and contemporary evidence of a mutton snapper (Lutjanus analis Cuvier, 1828) spawning aggregation fishery in decline - R. T. Graham; R. Carcamo; K. L. Rhodes; C. M. Roberts; N. Requena (Coral Reefs, 2008)

Is MSH2 a breast cancer susceptibility gene? - EE Ming Wong; Andrea A. Tesoriero; Gulietta M. Pupo; Margaret R. E. McCredie; Graham G. Giles; John L. Hopper; Graham J. Mann; David E. Goldgar; Melissa C. Southey (Familial Cancer, 2008)

Real options for precautionary fisheries management - Eli P Fenichel; Jean I Tsao; Michael L Jones; Graham J Hickling (Fish and Fisheries, 2008)
The 1996 Food and Agriculture Organization’s (FAO) ‘Guidelines on the Precautionary Approach to Fisheries and Species Introduction’ raise important issues for fisheries managers, but fail to prescribe an approach for risk management. The distinguishing characteristics of the ‘precautionary approach’ are the inclusion of uncertainty and ‘an elaboration on the burden of proof’. The FAO precautionary approach emphasizes that managers should be risk‐averse, but does not provide tools for determining the appropriate degree of risk aversion. Consequently, application of the precautionary approach often leads to decision‐making based on ad hoc safety margins. These safety margins are seldom chosen with explicit consideration of trade‐offs. If the emphasis was shifted to choosing between competing uncertainties, then managers could manage risk. By attempting to avoid risk, managers may gain exposure to other risks and perhaps miss valuable opportunities. We place fishery management problems within the rubric of ‘real investment’ problems, and compare and contrast the consideration of risk by alternative investment frameworks. We show that traditional investment frameworks are inappropriate for fishery management, and furthermore, that traditional precautionary approaches are arbitrary and without basis in decision theory. Quantitative decision‐making techniques, such as formal decision analysis (FDA), enable integration of competing hypotheses that help alleviate burden‐of‐proof issues. These techniques help analysts consider sources of uncertainty. FDA, however, can still be subject to arbitrary safety margins because such analyses often focus on determining which strategies best achieve, or avoid, targets that have been established without complete consideration of trade‐offs. A managerial finance approach, real options analysis (ROA), is an alternative and complementary decision‐making technique that enables managers to compute precautionary adjustments that couple the size of the ‘safety margin’ with the amount of uncertainty, thereby optimizing risk exposure and avoiding the need for arbitrary safety margins. We illustrate the advantages of an approach that combines FDA and ROA, using a heuristic example about a decision to re‐introduce Atlantic salmon ( Salmo salar L.) into Lake Ontario. Finally, we provide guidance on applying ROA to other fishery problems. The precautionary approach requires that managers consider risk, but considering risk is not the same as managing it. Here ROA is useful.

Relationship Between the Endophyte Embellisia spp. and the Toxic Alkaloid Swainsonine in Major Locoweed Species (Astragalus and Oxytropis) - M. H. Ralphs; R. Creamer; D. Baucom; D. R. Gardner; S. L. Welsh; J. D. Graham; C. Hart; D. Cook; B. L. Stegelmeier (Journal of Chemical Ecology, 2008)

Water Hyacinths (Eichhornia crassipes) as Indicators of Heavy Metal Impact of a Large Landfill on the Almendares River near Havana, Cuba - S. Olivares-Rieumont; L. Lima; D. De la Rosa; D. W. Graham; I. Columbie; J. L. Santana; M. J. Sánchez (Bulletin of Environmental Contamination and Toxicology, 2007)

Cotreatment with the kappa opioid agonist U69593 enhances locomotor sensitization to the D2/D3 dopamine agonist quinpirole and alters dopamine D2 receptor and prodynorphin mRNA expression in rats - Melissa L. Perreault; Dawn Graham; Sarah Scattolon; Yufang Wang; Henry Szechtman; Jane A. Foster (Psychopharmacology, 2007)

Fructose Consumption and Moderate Zinc Deficiency Influence Growth and Adipocyte Metabolism in Young Rats Prone to Adult-Onset Obesity - Erin L. Streiff; Kimber L. Stanhope; James Graham; Peter J. Havel; Janet C. King (Biological Trace Element Research, 2007)

Identification of novel small RNAs in tomato (Solanum lycopersicum) - Rachel L. Rusholme Pilcher; Simon Moxon; Nima Pakseresht; Vincent Moulton; Kenneth Manning; Graham Seymour; Tamas Dalmay (Planta, 2007)

Responses of Tuatara ( Sphenodon punctatus ) to Removal of Introduced Pacific Rats from Islands - DAVID R. TOWNS; G. RICHARD PARRISH; CLAUDINE L. TYRRELL; GRAHAM T. USSHER; ALISON CREE; DONALD G. NEWMAN; A. (TONY) H. WHITAKER; IAN WESTBROOKE (Conservation Biology, 2007)
Invasive mammalian predators such as rats are now widespread on islands, but hypotheses about their effects have rarely been tested. Circumstantial evidence from New Zealand indicates that, when introduced to islands, Pacific rats (Rattus exulans) have negative effects on endemic plants, invertebrates, birds, and reptiles, including the tuatara (Sphenodon punctatus). We tested the effects of Pacific rats on tuatara by comparing the demographic structure and body condition of tuatara populations on three islands before and after removal of rats and on a fourth island where rats remained. In the presence of rats, juvenile tuatara constituted on average 0–5% of the sample tuatara populations. When Pacific rats were removed after at least 200 years' occupancy, the proportion of juvenile tuatara increased 3.5‐ to 17‐fold and body condition of adult males and females also improved (sometimes dramatically). We predict that, unless Pacific rats are removed from Taranga Island, the tuatara population will collapse because of low population density and the lack of juvenile recruitment. Our results demonstrate that when invasive species exert subtle effects on recruitment and body condition, the effects on populations of long‐lived endemic species may only become apparent long after the invasion.

Does size matter for dispersal distance? - David G. Jenkins; Camille R. Brescacin; Craig V. Duxbury; Jennifer A. Elliott; Jennafer A. Evans; Katherine R. Grablow; Melissa Hillegass; Boyd N. Lyon; Genevieve A. Metzger; Michelle L. Olandese; Diana Pepe; Greg A. Silvers; et al. (Global Ecology and Biogeography, 2007)
Aim The aim of this study is to answer the questions: (1) do small organisms disperse farther than large, or vice versa; and (2) does the observed pattern differ for passive and active dispersers? These questions are central to several themes in biogeography (including microbial biogeography), macroecology, metacommunity ecology and conservation biology. Location The meta‐analysis was conducted using published data collected worldwide. Methods We collected and analysed 795 data values in the peer‐reviewed literature for direct observations of both maximal dispersal distance and mass of the dispersing organisms (e.g. seeds, not trees). Analysed taxa ranged in size from bacteria to whales. We applied macroecology analyses based on null models (using Monte Carlo randomizations) to test patterns relative to specific hypotheses. Results Collected dispersal distance and mass data spanned 9 and 21 orders of magnitude, respectively. Active dispersers dispersed significantly farther ( P P Conclusions Size is important to maximal dispersal distance for active dispersers, but not for passive dispersers. Claims that microbes disperse widely cannot be tested by current data based on direct observations of dispersal: indirect approaches will need to be applied. Distance–mass relationships should contribute to a resolution of neutral and niche‐based metacommunity theories by helping scale expectations for dispersal limitation. Also, distance–mass relationships should inform analyses of latitudinal species richness and conservation biology topics such as fragmentation, umbrella species and taxonomic homogenization.

Genomic and structural analysis of Syn9, a cyanophage infecting marine Prochlorococcus and Synechococcus - Peter R. Weigele; Welkin H. Pope; Marisa L. Pedulla; Jennifer M. Houtz; Alexis L. Smith; James F. Conway; Jonathan King; Graham F. Hatfull; Jeffrey G. Lawrence; Roger W. Hendrix (Environmental Microbiology, 2007)
Summary Cyanobacteriophage Syn9 is a large, contractile‐tailed bacteriophage infecting the widespread, numerically dominant marine cyanobacteria of the genera Prochlorococcus and Synechococcus . Its 177 300 bp genome sequence encodes 226 putative proteins and six tRNAs. Experimental and computational analyses identified genes likely involved in virion formation, nucleotide synthesis, and DNA replication and repair. Syn9 shows significant mosaicism when compared with related cyanophages S‐PM2, P‐SSM2 and P‐SSM4, although shared genes show strong purifying selection and evidence for large population sizes relative to other phages. Related to coliphage T4 – which shares 19% of Syn9's genes – Syn9 shows evidence for different patterns of DNA replication and uses homologous proteins to assemble capsids with a different overall structure that shares topology with phage SPO1 and herpes virus. Noteworthy bacteria‐related sequences in the Syn9 genome potentially encode subunits of the photosynthetic reaction centre, electron transport proteins, three pentose pathway enzymes and two tryptophan halogenases. These genes suggest that Syn9 is well adapted to the physiology of its photosynthetic hosts and may affect the evolution of these sequences within marine cyanobacteria.

Breastfeeding and risk of ovarian cancer in two prospective cohorts - Kim N. Danforth; Shelley S. Tworoger; Jonathan L. Hecht; Bernard A. Rosner; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2007)

Rotavirus-neutralizing antibodies inhibit virus binding to integrins α2β1 and α4β1 - F. E. Fleming; K. L. Graham; K. Taniguchi; Y. Takada; B. S. Coulson (Archives of Virology, 2007)

Cranial endothermy and a putative brain heater in the most basal tuna species, Allothunnus fallai - C. A. Sepulveda; K. A. Dickson; L. R. Frank; J. B. Graham (Journal of Fish Biology, 2007)
Field studies on the slender tuna Allothunnus fallai revealed cranial temperatures that were 4·8 ± 0·4° C (mean ± s . d .) above the ambient sea surface temperature. Dissections aimed at documenting the cranial heat source revealed a fused extraocular muscle complex positioned beneath the brain of this basal tuna species. The muscle complex is structurally distinct from that documented for any other fish species. In A. fallai , all four extraocular rectus muscle pairs (superior, inferior, medial and lateral rectus) are incorporated into one distinct tissue complex which is positioned between the orbits and in direct contact with the braincase. A combination of morphological, physiological and biochemical techniques were used to characterize the modified muscle tissue, and high‐resolution magnetic resonance imaging was used to illustrate its association with the brain and optic nerves. The modified eye muscles lack organized contractile proteins and are perfused by an extensive vascular counter‐current system that originates from the internal carotid artery. Vessel diameters, artery–vein configuration, and anatomic position between the systemic circulation and the warm eye muscles all suggest that this system is a heat exchanger. Collectively, these findings suggest that A. fallai has evolved extraocular muscles that may function to warm the brain and eye region. This is the first record of a cranial modification comprised of all four rectus muscles and the only documented occurrence of this mechanism for cranial endothermy among the tunas.

On interpreting hydrological change from regional climate models - L. Phil Graham; Stefan Hagemann; Simon Jaun; Martin Beniston (Climatic Change, 2007)

Assessing climate change impacts on hydrology from an ensemble of regional climate models, model scales and linking methods – a case study on the Lule River basin - L. Phil Graham; Johan Andréasson; Bengt Carlsson (Climatic Change, 2007)

Evolution of Hyperactive, Repetitive Antifreeze Proteins in Beetles - Laurie A. Graham; Wensheng Qin; Stephen C. Lougheed; Peter L. Davies; Virginia K. Walker (Journal of Molecular Evolution, 2007)

Differential ability of D1 and D2 dopamine receptor agonists to induce and modulate expression and reinstatement of cocaine place preference in rats - Danielle L. Graham; Regis Hoppenot; April Hendryx; David W. Self (Psychopharmacology, 2007)

Aspects of participatory plant breeding for quinoa in␣marginal areas of Ecuador - Elaine McElhinny; Eduardo Peralta; Nelson Mazón; Daniel L. Danial; Graham Thiele; Pim Lindhout (Euphytica, 2007)

Can cultivars from participatory plant breeding improve seed provision to small-scale farmers? - Conny J. M. Almekinders; Graham Thiele; Daniel L. Danial (Euphytica, 2007)

Development of an Ecologic Marine Classification in the New Zealand Region - Ton H. Snelder; John R. Leathwick; Katie L. Dey; Ashley A. Rowden; Mark A. Weatherhead; Graham D. Fenwick; Malcolm P. Francis; Richard M. Gorman; Janet M. Grieve; Mark G. Hadfield; Judi E. Hewitt; Ken M. Richardson; et al. (Environmental Management, 2007)

Body size and composition and risk of rectal cancer (Australia) - Robert J. MacInnis; Dallas R. English; Andrew M. Haydon; John L. Hopper; Dorota M. Gertig; Graham G. Giles (Cancer Causes & Control, 2006)

Multiple anthropogenic stressors cause ecological surprises in boreal lakes - MICHAEL R. CHRISTENSEN; MARK D. GRAHAM; ROLF D. VINEBROOKE; DAVID L. FINDLAY; MICHAEL J. PATERSON; MICHAEL A. TURNER (Global Change Biology, 2006)
The number of combinations of anthropogenic stressors affecting global change is increasing; however, few studies have empirically tested for their interactive effects on ecosystems. Most importantly, interactions among ecological stressors generate nonadditive effects that cannot be easily predicted based on single‐stressor studies. Here, we corroborate findings from an in situ mesocosm experiment with evidence from a whole‐ecosystem manipulation to demonstrate for the first time that interactions between climate and acidification determine their cumulative impact on the food‐web structure of coldwater lakes. Interactions among warming, drought, and acidification, rather than the sum of their individual effects, best explained significant changes in planktonic consumer and producer biomass over a 23‐year period. Further, these stressors interactively exerted significant synergistic and antagonistic effects on consumers and producers, respectively. The observed prevalence of long‐ and short‐term ecological surprises involving the cumulative impacts of multiple anthropogenic stressors highlights the high degree of uncertainty surrounding current forecasts of the consequences of global change.

The Introduction of Transgenes to Control Blackheart in Pineapple (Ananas Comosus L.) cv. Smooth Cayenne by Microprojectile Bombardment - H. L. Ko; P. R. Campbell; M. P. Jobin-Décor; K. L. Eccleston; M. W. Graham; M. K. Smith (Euphytica, 2006)

Frequent Tanning Bed Use, Weight Concerns, and Other Health Risk Behaviors in Adolescent Females (United States) - David L. O’Riordan; Alison E. Field; Alan C. Geller; Daniel R. Brooks; Gideon Aweh; Graham A. Colditz; A. Lindsay Frazier (Cancer Causes & Control, 2006)

The importance of cysteine cathepsin proteases for placental development - Aikaterini Varanou; Sarah L. Withington; Lorin Lakasing; Catherine Williamson; Graham J. Burton; Myriam Hemberger (Journal of Molecular Medicine, 2006)

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)

Effects of the freshwater aquarium trade on wild fish populations in differentially‐fished areas of the Peruvian Amazon - C. L. Gerstner; H. Ortega; H. Sanchez; D. L. Graham (Journal of Fish Biology, 2006)
Base‐line data were collected to examine the possible effects of the aquarium trade on Amazon fish populations in differentially‐fished locations in the Departmento of Loreto, Peru. Fish abundance, species diversity (richness) and biomass were quantified at three locations with differential fishing pressure, including the Rio Nanay (high pressure), Rio Apayacu and Rio Arambassa (medium) and Rio Yanayacu –Pacaya‐Samiria National Reserve (low). Seining results indicated that the location with the highest fishing pressure had reduced fish abundance, species diversity and biomass compared to the other locations. A similar trend was seen using minnow traps. There was no significant difference in abundance, diversity and biomass between the medium and low fishing pressure locations. Habitat differences (pH and conductivity) among the three locations accounted for

Changes in New Zealand pan evaporation since the 1970s - Michael L. Roderick; Graham D. Farquhar (International Journal of Climatology, 2005)

Domain Formation in DODAB–Cholesterol Mixed Systems Monitored via Nile Red Anisotropy - Graham Hungerford; Elisabete M. S. Castanheira; Adelina L. F. Baptista; Paulo J. G. Coutinho; M. Elisabete C. D. Real Oliveira (Journal of Fluorescence, 2005)

Assignment of sockeye salmon (Oncorhynchus nerka) to spawning sites using DNA markers - Graham E. Corley-Smith; Liv Wennerberg; Joy A. Schembri; Chinten J. Lim; Karen L. Cooper; Bruce P. Brandhorst (Marine Biotechnology, 2005)

An assessment of European pig diversity using molecular markers: Partitioning of diversity among breeds - Louis Ollivier; Lawrence Alderson; Gustavo C. Gandini; Jean-Louis Foulley; Chris S. Haley; Ruth Joosten; Annemieke P. Rattink; Barbara Harlizius; Martien A. M. Groenen; Yves Amigues; Marie-Yvonne Boscher; Geraldine Russell; et al. (Conservation Genetics, 2005)

Characterization of Condensed Tannins Purified From Legume Forages: Chromophore Production, Protein Precipitation, and Inhibitory Effects on Cellulose Digestion - Tim A. McAllister; Tomas Martinez; Hee Dong Bae; Alister D. Muir; L. Jay Yanke; Graham A. Jones (Journal of Chemical Ecology, 2005)

SNPs in the neural cell adhesion molecule 1 gene (NCAM1) may be associated with human neural tube defects - Kristen L. Deak; Abee L. Boyles; Heather C. Etchevers; Elizabeth C. Melvin; Deborah G. Siegel; Felicia L. Graham; Susan H. Slifer; David S. Enterline; Timothy M. George; Michel Vekemans; David McClay; Alexander G. Bassuk; et al. (Human Genetics, 2005)

Sugarcane biotechnology: The challenges and opportunities - Prakash Lakshmanan; R. Jason Geijskes; Karen S. Aitken; Christopher L. P. Grof; Graham D. Bonnett; Grant R. Smith (In Vitro Cellular & Developmental Biology - Plant, 2005)

Spawning aggregations of Lutjanus cyanopterus (Cuvier) on the Belize Barrier Reef over a 6 year period - W. D. Heyman; B. Kjerfve; R. T. Graham; K. L. Rhodes; L. Garbutt (Journal of Fish Biology, 2005)
Cubera snapper Lutjanus cyanopterus aggregated to spawn at Gladden Spit, a salient sub‐surface reef promontory seaward of the emergent reef and near the continental shelf edge of Belize. Their spawning aggregations typically formed 2 days before to 12 days after full moon from March to September 1998–2003 within a 45 000 m 2 reef area. Peak abundance of 4000 to 10 000 individuals was observed between April and July each year, while actual spawning was most frequently observed in May. Spawning was observed consistently from 40 min before to 10 min after sunset within a confined area ≤1000 m 2 . Data suggested that cubera snapper consistently formed seasonal spawning aggregations in relation to location, photoperiod, water temperature and lunar cycle, and that spawning was cued by time of day but not tides. The cubera snapper aggregation site was included within the Gladden Spit Marine Reserve, a conditional no‐take fishing zone.

Locomotor activity detects subunit-selective effects of agonists and decahydroisoquinoline antagonists at AMPA/kainic acid ionotropic glutamate receptors in adult rats - Michael F. O’Neill; Graham Sanger; Paul L. Ornstein; David J. Osborne; Sandra M. Woodhouse (Psychopharmacology, 2005)

Factors Affecting the Fate of Ciprofloxacin in Aquatic Field Systems - L. A. Cardoza; C. W. Knapp; C. K. Larive; J. B. Belden; M. Lydy; D. W. Graham (Water, Air, & Soil Pollution, 2005)

Non-coordinate expression of peroxisome biogenesis, ?-oxidation and glyoxylate cycle genes in mature Arabidopsis plants - Wayne L. Charlton; Barbara Johnson; Ian A. Graham; Alison Baker (Plant Cell Reports, 2005)

Cataract Extraction and Risk of Breast Cancer - Shumin M. Zhang; Walter C. Willett; Frank B. Hu; Edward L. Giovannucci; JoAnn E. Manson; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2004)

First observation of herpes‐like virus particles in northern pike, Esox lucius L., associated with bluespot‐like disease in Ireland - D A Graham; W L Curran; F Geoghegan; F McKiernan; K L Foyle (Journal of Fish Diseases, 2004)
Circular whitish granular lesions, 5–12 mm in diameter, were observed on the skin and fins of a wild northern pike, Esox lucius , caught in a lake in the Republic of Ireland. Histological examination of the lesions revealed hypertrophied cells in the epidermis with deeply basophilic enlarged nuclei and dark‐staining granular material in the cytoplasm. Transmission electron microscopy of these cells revealed naked hexagonal herpes‐like virus nucleocapsids (97 ± 7 nm) in their nuclei while the cytoplasm contained multiple aggregates of enveloped viral particles. This is the first report of herpes‐like virus particles in northern pike originating outside North America, where esocid herpesvirus‐1 (EsHV‐1) has previously been reported. Shared clinical, histological, morphological and epidemiological findings suggest that the observed particles in this report may also be EsHV‐1.

The construction of a genetic linkage map of red raspberry (Rubus idaeus subsp. idaeus) based on AFLPs, genomic-SSR and EST-SSR markers - J. Graham; K. Smith; K. MacKenzie; L. Jorgenson; C. Hackett; W. Powell (Theoretical and Applied Genetics, 2004)

Changes in Australian pan evaporation from 1970 to 2002 - Michael L. Roderick; Graham D. Farquhar (International Journal of Climatology, 2004)
Contrary to expectations, measurements of pan evaporation show decreases in many parts of the Northern Hemisphere over the last 50 years. When combined with rainfall measurements, these data show that much of the Northern Hemisphere's terrestrial surface has become less arid over the last 50 years. However, whether the decrease in pan evaporation is a phenomenon limited to the Northern Hemisphere has until now been unknown because there have been no reports from the Southern Hemisphere. Here, we report a decrease in pan evaporation rate over the last 30 years across Australia of the same magnitude as the Northern Hemisphere trends (approximately −4 mm a −2 ). The results show that the terrestrial surface in Australia has, on average, become less arid over the recent past, just like much of the Northern Hemisphere. Copyright © 2004 Royal Meteorological Society.

UVA Light-Induced Toxic Effects of 1-Hydroxypyrene on Human Jurkat T-Cells - L. Wang; H. Cohly; J. Yan; B. Graham-Evans; H.-M. Hwang; H. Yu (Bulletin of Environmental Contamination and Toxicology, 2004)

Effect of Carnosine on Excitation–Contraction Coupling in Mechanically-Skinned Rat Skeletal Muscle - Travis L. Dutka; Graham D. Lamb (Journal of Muscle Research and Cell Motility, 2004)

Assessment of Lumiracoxib Bioavailability from Targeted Sites in the Human Intestine Using Remotely Activated Capsules and Gamma Scintigraphy - Ian R. Wilding; Alyson L. Connor; Polly Carpenter; Christiane Rordorf; Janice Branson; Slavica Milosavljev; Graham Scott (Pharmaceutical Research, 2004)

Multi-scale comparisons of cliff vegetation in Colorado - Liza Graham; Richard L. Knight (Plant Ecology, 2004)

Foods, nutrients and prostate cancer - Allison M. Hodge; Dallas R. English; Margaret R.E. McCredie; Gianluca Severi; Peter Boyle; John L. Hopper; Graham G. Giles (Cancer Causes & Control, 2004)

European climate in the late twenty-first century: regional simulations with two driving global models and two forcing scenarios - J. Räisänen; U. Hansson; A. Ullerstig; R. Döscher; L. P. Graham; C. Jones; H. E. M. Meier; P. Samuelsson; U. Willén (Climate Dynamics, 2004)

Comparative effects of a vasopeptidase inhibitor vs. an angiotensin convertin enzyme inhibitor on cardiomyocyte apoptosis in rats with heart failure - Nathalie Lapointe; James N. Tsoporis; Thomas G. Parker; Charles Blais; Albert Adam; Dominique Rouleau; Graham Slaughter; Robert Clément; Christian F. Deschepper; Jean L. Rouleau (Molecular and Cellular Biochemistry, 2003)

Ulrich Schwarz-Schampera, Peter M. Herzig: Indium: geology, mineralogy, and economics - L. Graham Closs (Mineralium Deposita, 2003)

Production of multiple shoots from thidiazuron-treated mature embryos and leaf-base/apical meristems of barley (Hordeum vulgare) - Seedhabadee Ganeshan; Monica Båga; Bryan L. Harvey; Brian G. Rossnagel; Graham J. Scoles; Ravindra N. Chibbar (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Ecological and economic implications of a tropical jellyfish invader in the Gulf of Mexico - William M. Graham; Daniel L. Martin; Darryl L. Felder; Vernon L. Asper; Harriet M. Perry (Biological Invasions, 2003)

Mechanisms of benthic prey capture in wrasses (Labridae) - L. A. Ferry-Graham; P. C. Wainwright; M. W. Westneat; D. R. Bellwood (Marine Biology, 2002)

Caspase-9 Inhibition after Focal Cerebral Ischemia Improves Outcome following Reversible Focal Ischemia - Graham Mouw; Jennifer L. Zechel; Yifang Zhou; W. David Lust; Warren R. Selman; Robert A. Ratcheson (Metabolic Brain Disease, 2002)

PCR Sampling of disease resistance-like sequences from a disease resistance gene cluster in soybean - M. Graham; L. Marek; R. Shoemaker (Theoretical and Applied Genetics, 2002)

Rare earth element diffusion in a natural pyrope single crystal at 2.8 GPa - James A. Van Orman; Timothy L. Grove; Nobumichi Shimizu; Graham D. Layne (Contributions to Mineralogy and Petrology, 2002)

Antibiotic resistance in bacteria from magpies ( Pica pica ) and rabbits ( Oryctolagus cuniculus ) from west Wales - David M. Livermore; Marina Warner; Lucinda M. C. Hall; Virve I. Enne; Stephen J. Projan; Paul M. Dunman; Sarah L. Wooster; Graham Harrison (Environmental Microbiology, 2001)
Summary The prevalence of antibiotic‐resistant bacteria in wild animal and bird populations is largely unknown, with little consistency among the few published reports. We therefore examined intestinal bacteria from magpies ( Pica pica ) and rabbits ( Oryctolagus cuniculus ) collected in rural west Wales. Escherichia coli isolates resistant to multiple antibiotics were grown from eight of 20 magpies trapped in spring, 1999 and one of 17 in spring, 2000; the most prevalent resistance trait among these isolates was to tetracycline, but resistances to ampicillin, chloramphenicol, kanamycin, sulphonamide, tetracycline and trimethoprim were also found. Tetracycline‐resistant Enterococcus spp. were found in one of 20 magpies in 1999 and three of 17 in 2000. Only one resistant E. coli isolate was detected among gut bacteria from 13 rabbits, and this strain was resistant only to tetracycline. Differences in the prevalence of resistance between bacteria from rabbits and magpies may reflect differences in diet: rabbits graze field edges, whereas magpies are omnivorous and opportunistic. The resistance genes found in E. coli isolates from magpies mostly corresponded to those common among human isolates, but those conferring tetracycline resistance were unique.

Water balance modelling in the Baltic Sea drainage basin - analysis of meteorological and hydrological approaches - L. P. Graham; S. Bergstrm (Meteorology and Atmospheric Physics, 2001)

A comprehensive model inter-comparison study investigating the water budget during the BALTEX-PIDCAP period - D. Jacob; B. J. J. M. Van den Hurk; U. Andr; G. Elgered; C. Fortelius; L. P. Graham; S. D. Jackson; U. Karstens; Chr. Kpken; R. Lindau; R. Podzun; B. Rockel; et al. (Meteorology and Atmospheric Physics, 2001)

On the direct effect of clouds and atmospheric particles on the productivity and structure of vegetation - Michael L. Roderick; Graham D. Farquhar; Sandra L. Berry; Ian R. Noble (Oecologia, 2001)

Scanning for telomeric deletions and duplications and uniparental disomy using genetic markers in 120 children with malformations - M. Rosenberg; C. Killoran; L. Dziadzio; S. Chang; D. Stone; J. Meck; D. Aughton; L. Bird; J. Bodurtha; S. Cassidy; J. Graham; A. Grix; et al. (Human Genetics, 2001)

The distribution and population structure of the temperate mistletoe lleostylus micranthus in the Northern Cemetery, Dunedin, New Zealand - Peter Bannister; Graham L. Strong (New Zealand Journal of Botany, 2001)
The endemic mistletoe, Ileostylus micrunrhus , growing in the Northern Cemetery (Dunedin, New Zealand), was examined with respect to both its OCCUrrenCe on different host species and its distribution on the trunk and within the canopy of its hosts. Only 3.5% of trees were infected and the mistletoe was absent from hosts with trunk diameters of more than 70 cm. The most frequently infected hosts were Erica Iiisitanica, Betula pendiifa , and Pittosporum tenuifofium. Larger hosts generally supported mOre mistletoe infections than smaller hosts. Most individual infections were small or medium‐sized. Mistletoe plants were distributed throughout the canopy of infected hosts but were least frequent on the trunk and most frequent in the middle and lower thirds of the canopy. Large mistletoes tended to be found more frequently on the outer parts of the canopy and on the trunk than juvenile, small, and medium‐sized mistletoes.

New Zealand mistletoes have equal or lower capacities for electron transport than their hosts - Graham L. Strong; Peter Bannister; David J. Burritt (New Zealand Journal of Botany, 2001)
previous work on the New Zealand mistletoes Ileostylus micranthus and Tupeia antarctica indicates that these mistletoes have lower maximum electron transport rates (ETR max ) than their hosts. We extend this research by testing Seven of the eight extant endemic New Zealand mistletoes using chlorophyll fluorescence measurements. In addition, we examined whether loranthaceous (Alepis flavida & Ileostylus micranthus, peraxilla Colensoi p. tetra‐petala Tupeia antarctica) and viscaceous mistletoes (Korthalsella Iindsayi, K. salicornioides) differed in their capacities for electron transport. Electron transport rates were significantly related to photosyn‐thetically active Photon flux densities (PPFD). Overall, mistletoes had significantly lower (110 ± 18 mol m ‐ s ‐1 ) ETR max than their hosts (219 ± 43 mol m ‐2 S ‐1 ) but Some specific host‐mistletoes Pairs showed no significant difference in ETR max There was no clear distinction in ETR max between mistletoe families. We conclude that New Zealand mistletoes generally have lower electron transport rates at the same PPFD and, usually, lower photosynthetic capacities than their hosts.

Carbon and nitrogen isotope ratios, nitrogen content and heterotrophy in New Zealand mistletoes - Peter Bannister; Graham L. Strong (Oecologia, 2001)

Hepatic Disposition of Fexofenadine: Influence of the Transport Inhibitors Erythromycin and Dibromosulphothalein - Robert W. Milne; Linda A. Larsen; Klaus L. Jørgensen; Jesper Bastlund; Graham R. Stretch; Allan M. Evans (Pharmaceutical Research, 2000)

Patterns of development and succession of vegetated hummocks in slacks of the Alexandria coastal dune field, South Africa - Bridget L. Elliott; Graham I. H. Kerley; Anton McLachlan (Journal of Coastal Conservation, 2000)

Bowel movement, use of laxatives and risk of colorectal adenomatous polyps among women (United States) - Laurent Elizabeth A. Dukas; Graham A. Colditz; Walter C. Willett; Edward L. Giovannucci (Cancer Causes & Control, 2000)

Diet in the epidemiology of endometrial cancer in Western New York (United States) - Susan E. McCann; Jo L. Freudenheim; James R. Marshall; John R. Brasure; Mya K. Swanson; Saxon Graham (Cancer Causes & Control, 2000)

Wheat responses to aggressive and non-aggressive arbuscular mycorrhizal fungi - J. H. Graham; L. K. Abbott (Plant and Soil, 2000)

The correlation of reaction and isotope fronts and the mechanism of metamorphic fluid flow - A. D. L. Skelton; J. W. Valley; C. M. Graham; M. J. Bickle; A. E. Fallick (Contributions to Mineralogy and Petrology, 2000)

The effect of suramin on the resorption of bovine nasal cartilage - Claire L. Lewis; Astrid Frazer; R. Graham G. Russell; Rowena A. D. Bunning (Inflammopharmacology, 1999)

Alcohol dehydrogenase 3 genotype modification of the associationof alcohol consumption with breast cancer risk - Jo L. Freudenheim; Christine B. Ambrosone; Kirsten B. Moysich; John E. Vena; Saxon Graham; James R. Marshall; Paola Muti; Rosemary Laughlin; Takuma Nemoto; Lea C. Harty; G. Adam Crits; Arthur W.K. Chan; et al. (Cancer Causes & Control, 1999)

ADRENAL FUNCTION IN WILD AND REHABILITATED PACIFIC HARBOR SEALS ( PHOCA VITULINA RICHARDII ) AND IN SEALS WITH PHOCINE HERPESVIRUS‐ASSOCIATED ADRENAL NECROSIS - F. M. D. Gulland; M. Haulena; L. J. Lowenstine; C. Munro; P. A. Graham; J. Bauman; J. Harvey (Marine Mammal Science, 1999)
A bstract Adrenal function in harbor seals ( Phoca vitulina richardii ) was evaluated using adrenocorticotrophic hormone (ACTH) stimulation tests and fecal cortisol levels. The effect of ACTH administration on plasma cortisol and aldosterone levels in five free‐living and 14 rehabilitated harbor seal pups was determined using enzyme immunoassay and radioimmunoassay, respectively. In free‐living seals, injection of ACTH caused a significant increase in mean plasma cortisol but not of mean aldosterone levels 60 min postinjection. In these seals, mean initial plasma aldosterone was significantly higher than initial levels in rehabilitated seals, while initial cortisol levels were similar. Of the rehabilitated seals, eight died with adrenal cortical necrosis associated with herpesvirus inclusions, while six lived to be released. In the seals that were released, both mean initial cortisol levels and response to ACTH decreased through rehabilitation. In the seals that died, mean initial cortisol and response to ACTH increased through rehabilitation. The differences between initial cortisol levels in seals that lived and those that died were significant at weeks two and four of rehabilitation but not at the week of admission. There was considerable individual variation in initial plasma aldosterone levels and responses to ACTH, although initial aldosterone levels were significantly higher in rehabilitated seals that died than in seals that lived. Seals with adrenal necrosis associated with herpesvirus infection did not have decreased adrenal hormone responses to ACTH. Differences between initial hormone levels and responses to ACTH in different groups of seals may be associated with differing stress levels. Fecal cortisol assays were not a useful method of assessing adrenal function in these seals, as measured levels did not correlate with plasma cortisol levels.

Trophic interactions in open systems: Effects of predators and nutrients on stream food chains - Graham E. Forrester; Tom L. Dudley; Nancy B. Grimm (Limnology and Oceanography, 1999)
Theory and empirical work on food chains has focused primarily on closed, equilibrial environments. We tested the combined effects of secondary consumers (fish) and limiting nutrients (nitrogen) on intermediate trophic levels in an open stream environment, where flow redistributes organisms and materials among patches of streambed habitat. Fish reduced the biomass of the dominant herbivore (baetid mayflies) within habitat patches both by direct predation and by causing increased emigration from the patches. The resulting decrease in herbivory caused an increase in the growth and biomass of primary producers (algae) in areas containing fish. Independent of the effect of fish, algal growth and biomass was increased by augmenting the nutrient supply to patches. Nutrient‐enriched areas (with high algal biomass) also supported greater populations of herbivores because they either grew faster in these areas or emigrated less frequently from them. Controlling influences on trophic structure came from both the top and the bottom of the food chain, and these influences were not conditional upon one another. Trophic structure in this system was determined by a mix of behavioral and trophic interactions between the major taxa, most of which were specific to open systems and not predicted by conventional theory.

Neutral lipids in macroalgal spores and their role in swimming - D. C. Reed; M. A. Brzezinski; D. A. Coury; W. M. Graham; R. L. Petty (Marine Biology, 1999)

Effects of Nitrogen and Phosphorus Supply on Hexadecane Biodegradation in Soil Systems - D. W. Graham; V. H. Smith; D. L. Cleland; K. P. Law (Water, Air, & Soil Pollution, 1999)

Expression of early hippocampal CA1 LTP does not lead to changes in AMPA-EPSC kinetics or sensitivity to cyclothiazide - Gerhard Rammes; Hanns Ulrich Zeilhofer; Graham L. Collingridge; Chris G. Parsons; Dieter Swandulla (Pflügers Archiv - European Journal of Physiology, 1999)

Hydrodynamic properties of mucins secreted by primary cultures of Guinea-pig tracheal epithelial cells: determination of diffusion coefficients by analytical ultracentrifugation and kinetic analysis of mucus gel hydration and dissolution - Sara Dodd; Graham A. Place; R. L. Hall; Stephen E. Harding (European Biophysics Journal, 1998)

A Comparison of Aerial and Ground Level Measurements of 137Cs in the Marshall Islands - S. L. Simon; J. C. Graham (Environmental Monitoring and Assessment, 1998)

The Effect of High Dose Endotoxin on CYP3A2 Expression in the Rat - Amy L. Roe; Graham Warren; Guoqiang Hou; Georgette Howard; Steven I. Shedlofsky; Robert A. Blouin (Pharmaceutical Research, 1998)

Screening endoscopy and risk of colorectal cancer in United States men - Charles S. Fuchs; Edward L. Giovannucci; Graham A. Colditz; Anne M. Kavanagh (Cancer Causes & Control, 1998)

Feeding kinematics of hatchling swellsharks, Cephaloscyllium ventriosum (Scyliorhinidae): the importance of predator size - L. A. Ferry-Graham (Marine Biology, 1998)

Inflammation-associated lysyl oxidase protein expression in vivo, and modulation by FGF-2 plus IGF-1 - P. C. Trackman; Rudolph J. Graham; Howard K. Bittner; David L. Carnes; James A. Gilles; Dana T. Graves (Histochemistry and Cell Biology, 1998)

Cytokinesis and nodal anatomy in the charophycean green alga Chara zeylanica - M. E. Cook; L. E. Graham; C. A. Lavin (Protoplasma, 1998)

Breast cancer in Australian women under the age of 40 - Margaret R.E. McCredie; Gillian S. Dite; Graham G. Giles; John L. Hopper (Cancer Causes & Control, 1998)

Nutritional Aspects of Dissimilatory Sulfate Reduction in the Human Large Intestine - Caroline L. Willis; John H. Cummings; Graham Neale; Glenn R. Gibson (Current Microbiology, 1997)

Diet and alcohol consumption and lung cancer risk in the New York State Cohort (United States) - Elisa V. Bandera; Jo L. Freudenheim; James R. Marshall; Maria Zielezny; Roger L. Priore; John Brasure; Mark Baptiste; Saxon Graham (Cancer Causes & Control, 1997)

Promoter sequences from two different Brassica napus tapetal oleosin-like genes direct tapetal expression of β-glucuronidase in transgenic Brassica plants - Hai Ping Hong; Joanne H.E. Ross; Jean L. Gerster; Stamatis Rigas; Raju S.S. Datla; Polydefkis Hatzopoulos; Graham Scoles; Wilf Keller; Denis J. Murphy; Laurian S. Robert (Plant Molecular Biology, 1997)

Diversity of alpha and beta subunits of T-cell receptors specific for the H4 minor histocompatibility antigen - Sean L. Johnston; Donna Graham; P. J. Wettstein (Immunogenetics, 1997)

Novel approach to investigate a source of microbial contamination of central venous catheters - T. S. J. Elliott; H. A. Moss; S. E. Tebbs; I. C. Wilson; R. S. Bonser; T. R. Graham; L. P. Burke; M. H. Faroqui (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

FORUM: The Converging Dynamics of Interest Representation in Resources Management - L. GRAHAM SMITH; CARLA Y. NELL (Environmental Management, 1997)

The Calculation of Frequency-Shift Functions for Chains of Coupled Oscillators, with Application to a Network Model of the Lamprey Locomotor Pattern Generator - Thelma L. Williams; Graham Bowtell (Journal of Computational Neuroscience, 1997)

Book reviews - David L. Hawksworth; Clem Tisdell; J. H. Graham (Biodiversity and Conservation, 1995)

Elevated serum silicon levels in women with silicone gel breast implants - Suzanne S. Teuber; Robert L. Saunders; Georges M. Halpern; Robert F. Brucker; Victor Conte; Brian D. Goldman; Edward E. Winger; W. Graham Wood; M. Eric Gershwin (Biological Trace Element Research, 1995)

Effect of carbon:nitrogen ratio on kinetics of phenol biodegradation byAcinetobacter johnsonii in saturated sand - Blythe L. Hoyle; Kate M. Scow; Graham E. Fogg; Jeannie L. Darby (Biodegradation, 1995)

Speed of nodulation and competitive ability among strains of Rhizobium leguminosarum bv phaseoli - L. A. de Oliveira; P. H. Graham (Archives of Microbiology, 1990)

Worker exposure during aerial application of a liquid and a granular formulation of Ordram Selective Herbicide to rice - R. D. Knarr; G. L. Cooper; E. A. Brian; M. G. Kleinschmidt; D. G. Graham (Archives of Environmental Contamination and Toxicology, 1985)

The delayed neuropathic effects of nerve agents and some other organophosphorus compounds - James J. Gordon; Robert H. Inns; Martin K. Johnson; Levence Leadbeater; Michael P. Maidment; David G. Upshall; Graham H. Cooper; Robert L. Rickard (Archives of Toxicology, 1983)

Chemical and enzymological characterization of an indonesian variant of human erythrocyte carbonic anhydrase II, CAIIJogjakarta (17 Lys ? Glu) - Graham L. Jones; A. Salam M. Sofro; Denis C. Shaw (Biochemical Genetics, 1982)

A polymorphic variant of human erythrocyte carbonic anhydrase I with a widespread distribution in Australian aborigines, CAIAustralia-9 (8 Asp ? Gly): Purification, properties, amino acid substitution, and possible physiological significance of the variant enzyme - Graham L. Jones; Denis C. Shaw (Biochemical Genetics, 1982)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

The effect of mirex on reproduction of Japanese quail and on characteristics of eggs from Japanese quail and chickens - K. L. Davison; J. H. Cox; C. K. Graham (Archives of Environmental Contamination and Toxicology, 1975)

Report of committee on the genetics and cytology of tuber-bearingSolanums - R. W. Hougas; K. M. Graham; A. E. Kehr; P. Grun; S. J. Peloquin; F. I. Lauer; R. Plaisted; R. W. Buck; D. A. Young; F. L. Haynes; L. A. Dionne (American Journal of Potato Research, 1959)

Report of the late blight investigating committee - John Niederhauser; W. R. Mills; R. Bonde; J. L. Howatt; L. C. Peterson; Keith Graham; M. E. Gallegly; C. J. Eide (American Journal of Potato Research, 1958)